Roll

By applying material to the outer peripheral surface of the core and filling the gap, the step difference problem during the diaphragm sheet is solved, manufacturing efficiency and product stability are improved, and deformation is reduced.

CN119142929APending Publication Date: 2024-12-17DAI NIPPON PRINTING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411468623.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-01-21
Filing Date
2020-07-09
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The prior art cannot effectively alleviate the step difference caused by the winding start end and the fixing member when the diaphragm sheet is wound, resulting in sheet deformation and low manufacturing efficiency.

Method used

By applying a material on the outer peripheral surface of the core, the winding start end of the sheet in the long side direction is arranged on the outer peripheral surface, and the coating material is filled in the first gap, or the sheet is fixed using a fixing member. And apply material on its outer peripheral surface to fill the gap, ensuring that the coating material comes into contact with the winding start end to alleviate the step difference.

Benefits of technology

The step difference caused by the beginning end of the sheet winding and the fixed parts is effectively alleviated, the manufacturing efficiency of the coil and the stability of the product are improved, and the deformation phenomenon is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119142929A_ABST
    Figure CN119142929A_ABST
Patent Text Reader

Abstract

The present invention relates to a roll body provided with a winding core and a long sheet wound around the outer peripheral surface of the winding core, the roll body being provided with: a fixing member for fixing a part of the sheet to the winding core, the fixing member being provided between the winding core and the sheet of a first circle and having a first end surface extending in the width direction of the winding core and a second end surface on the opposite side to the first end surface; a second gap that is located between the winding core and the sheet of the first circle and that is in contact with the first end surface of the fixing member; a third gap which is located between the winding core and the sheet of the first circle and is in contact with the second end surface of the fixing member; and at least one of a second sandwiching portion and a third sandwiching portion, the second sandwiching portion being provided in a second region corresponding to the second gap between the first and subsequent sheets and extending in the width direction of the winding core, and the third sandwiching portion being provided in a third region corresponding to the third gap between the first and subsequent sheets and extending in the width direction of the winding core.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application. The Chinese national application number of the original application is 202080054223.X, the application date is July 9, 2020, and the name of the invention is “Method for manufacturing a roll and a roll”.

[0002] Reference to related applications

[0003] This application enjoys the benefit of priority of Japanese Patent Application No. 2019-127551 (filing date: July 9, 2019) and Japanese Patent Application No. 2020-7594 (filing date: January 21, 2020), which are prior Japanese applications, and the disclosures of these applications are incorporated herein by reference in their entirety. Technical Field

[0004] The invention relates to a method for manufacturing a roll and a roll. Background Art

[0005] For sheet materials such as films, from the perspective of manufacturing efficiency, a certain amount of them are often manufactured in a concentrated manner, and then wound around a winding core and stored as a roll. In such a roll, a step difference is generated due to the end of the sheet material at the beginning of winding. Specifically, a step difference is generated when the sheet material of the first week changes to the second week, and this step difference also appears after the second week. In addition, depending on the type of sheet material, when this step difference occurs, there is a case where the sheet material is deformed and cannot be restored.

[0006] At present, the following technologies have been proposed: by sticking or embedding a cushioning tape with high cushioning properties such as polyurethane resin on the outer peripheral surface of the core and embedding the sheet in the cushioning tape, the above-mentioned step difference is alleviated (for example, refer to patent document 1); by using a core with rubber on the outer peripheral surface and embedding the sheet in the rubber, the step difference is alleviated; or, a cushioning member with elastic force is provided on the outer peripheral surface of the core along the end of the winding start end of the sheet (for example, refer to patent document 2).

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2005-75521

[0010] Patent Document 2: Japanese Patent Application Publication No. 2013-199355 Summary of the invention

[0011] Problems to be solved by the invention

[0012] However, the current situation is that any of the above-mentioned technologies cannot effectively alleviate the step difference.

[0013] When the sheet is wound around a core, first, a fixing member such as double-sided tape is attached to the outer peripheral surface of the core to fix a portion of the sheet (for example, the end portion where winding starts), but there are cases where a step difference is generated by the fixing member.

[0014] The present invention is made to solve the above-mentioned problems. That is, the purpose of the present invention is to provide a method for manufacturing a roll that can effectively alleviate the step difference caused by the winding start end of the sheet and such a roll. In addition, the purpose of the present invention is to provide a method for manufacturing a roll that can effectively alleviate the step difference caused by the fixing member and such a roll.

[0015] Means for solving problems

[0016] The present invention includes the following inventions.

[0017] [1] A method for manufacturing a roll, the roll comprising a core and a long strip of sheet material wound on the outer peripheral surface of the core, wherein the method for manufacturing a roll comprises: a step of applying a coating material to the outer peripheral surface of the core along the width direction of the core; a step of arranging the winding start end of the sheet material in the long side direction on the outer peripheral surface; and a step of winding the sheet material on the core and filling the coating material in at least a first gap, wherein the coating of the coating material or the arrangement of the winding start end is performed in a manner that the coating material is in contact with or close to the end face of the winding start end in the long side direction, and the first gap is a gap located between the core and the sheet material of the first week and in contact with the end face.

[0018] [2] A method for manufacturing a roll, the roll comprising a core and a long strip of sheet material wound on the outer peripheral surface of the core, wherein the method for manufacturing a roll comprises: a step of arranging the starting end of the sheet material in the long side direction on the outer peripheral surface; a step of winding the sheet material on the core for at least one circle to obtain an intermediate roll having a first gap; a step of applying a coating material on the front side of the sheet material constituting the outer peripheral surface of the intermediate roll along the width direction of the core; and a step of winding the sheet material on the core again after applying the coating material so that the coating material is interposed between the sheets, the first gap being a gap located between the core and the sheet material of the first circle and connected to the end face of the winding starting end located in the long side direction, the coating material being applied to a first area corresponding to the first gap on the front side of the sheet material constituting the outer peripheral surface of the intermediate roll.

[0019] [3] A method for manufacturing a roll, the roll comprising a core and a long strip of sheet material wound around the outer circumference of the core, wherein the method for manufacturing a roll comprises: a step of disposing a fixing component on the outer circumference of the core along the width direction of the core for fixing a portion of the sheet material to the core, the fixing component having a first end face extending along the width direction of the core and a second end face on the side opposite to the first end face; a step of applying a coating material on the outer circumference of the core along the width direction of the core; a step of fixing a portion of the sheet material to the core by the fixing component; and a step of fixing the sheet material to the core after the coating material is applied and a portion of the sheet material is fixed to the core. The process of winding the sheet material around the winding core and filling at least one of the second gap and the third gap with the coating material, wherein the coating material is applied or the fixing component is arranged in a manner that the coating material is located on the first end face side or the second end face side and the coating material is in contact with or close to the first end face or the second end face, or the coating material is located on the first end face side and the second end face side respectively and the coating material is in contact with or close to the first end face and the second end face, the second gap is a gap between the winding core and the sheet material of the first week and connected to the first end face, and the third gap is a gap between the winding core and the sheet material of the first week and connected to the second end face.

[0020] [4] A method for manufacturing a roll, the roll comprising a core and a long strip of sheet material wound on the outer peripheral surface of the core, wherein the method for manufacturing a roll comprises: a step of arranging a fixing component on the outer peripheral surface of the core along the width direction of the core for fixing a portion of the sheet material to the core, the fixing component having a first end face extending along the width direction of the core and a second end face on the side opposite to the first end face; a step of fixing a portion of the sheet material to the core by means of the fixing component; a step of winding the sheet material on the core for at least one turn to obtain an intermediate roll having a second gap and a third gap; a step of forming the intermediate roll by means of the fixing component. The process of applying a coating material to the front side of the sheet material on the outer peripheral surface along the width direction of the core; and the process of winding the sheet material around the core again after applying the coating material, the second gap being a gap located between the core and the sheet material of the first week and connected to the first end face of the fixing component, the third gap being a gap located between the core and the sheet material of the first week and connected to the second end face of the fixing component, the coating material is applied to at least one of a second area corresponding to the second gap and a third area corresponding to the third gap in the front side of the sheet material constituting the outer peripheral surface of the intermediate roll.

[0021] [5] The production method according to any one of [1] to [4] above, wherein the coating material has fluidity.

[0022] [6] The production method according to any one of [1] to [5] above, wherein the coating material is a curable polymer composition.

[0023] [7] The manufacturing method according to any one of [1] to [6] above, wherein the coating material contains a coloring material or a luminescent material.

[0024] [8] The production method according to any one of [1] to [6] above, wherein the sheet has a resin film.

[0025] [9] The production method according to any one of [1] to [7] above, wherein the sheet comprises an acrylic resin, a polyester resin, or a cycloolefin polymer resin.

[0026]

[10] The production method according to [8] or [9] above, wherein the thickness of the sheet is greater than or equal to 15 μm and less than or equal to 300 μm.

[0027]

[11] The production method according to any one of [1] to

[10] above, wherein the sheet is a laminate having a substrate and one or more functional layers laminated on the substrate.

[0028]

[12] The production method according to any one of [1] to

[11] above, wherein the sheet is used for an optical film, a polarizing plate, or a display device.

[0029]

[13] A roll body comprising a core and a long strip of sheet material wound on the outer peripheral surface of the core, wherein the roll body comprises: a first gap located between the core and the sheet material of the first week and connected to the end surface of the long side direction of the winding starting end of the sheet material of the first week; and a first filling portion filled in the first gap and extending along the width direction of the core.

[0030]

[14] The roll according to the above-mentioned

[11] , wherein the roll further comprises: a fixing component for fixing a portion of the sheet relative to the core, which is arranged between the core and the sheet of the first week, and has a first end face extending along the width direction of the core and a second end face on the side opposite to the first end face; a second gap, which is located between the core and the sheet of the first week and is connected to the first end face of the fixing component; a third gap, which is located between the core and the sheet of the first week and is connected to the second end face of the fixing component; and at least one of a second filling portion filled in the second gap and extending along the width direction of the core, and a third filling portion filled in the third gap and extending along the width direction of the core.

[0031]

[15] A roll body comprising a core and a long strip of sheet material wound on the outer peripheral surface of the core, wherein the roll body comprises: a first gap located between the core and the sheet material of the first week and connected to the end surface of the long side direction of the winding start end of the sheet material of the first week; and a first clamping portion, which is arranged in a first area between the sheets after the first week corresponding to at least the first gap and extends along the width direction of the core.

[0032]

[16] A roll body comprising a core and a long strip of sheet material wound around the outer peripheral surface of the core, wherein the roll body comprises: a fixing component for fixing a portion of the sheet material relative to the core, the fixing component being arranged between the core and the sheet material of the first week, and having a first end face extending along the width direction of the core and a second end face on the side opposite to the first end face; a second gap being located between the core and the sheet material of the first week and connected to the first end face of the fixing component; a third gap being located between the core and the sheet material of the first week and connected to the second end face of the fixing component; and at least one of a second filling portion filled in the second gap and extending along the width direction of the core, and a third filling portion filled in the third gap and extending along the width direction of the core.

[0033]

[17] A roll body comprising a core and a long strip of sheet material wound around the outer peripheral surface of the core, wherein the roll body comprises: a fixing component for fixing a portion of the sheet material relative to the core, the fixing component being arranged between the core and the sheet material of the first cycle, and having a first end face extending along the width direction of the core and a second end face on the side opposite to the first end face; a second gap being located between the core and the sheet material of the first cycle and in contact with the first end face of the fixing component; and a second gap being arranged between the core and the sheet material of the first cycle and in contact with the first end face of the fixing component. 3 gaps, which are located between the core and the sheets of the first week and are connected to the second end surface of the fixing member; and at least one of a second clamping portion and a third clamping portion, wherein the second clamping portion is arranged in a second area corresponding to the second gap between the sheets after the first week and extends along the width direction of the core, and the third clamping portion is arranged in a third area corresponding to the third gap between the sheets after the first week and extends along the width direction of the core.

[0034]

[18] The roll according to

[13] or

[14] above, wherein the roll further comprises a fourth sandwiching portion, the fourth sandwiching portion being continuously arranged with the first filling portion and sandwiched between the sheet of the first week and the sheet of the second week.

[0035]

[19] A roll according to the above-mentioned

[13] or

[14] , wherein, in the absence of a fourth clamping portion which is continuously arranged with the first filling portion and clamped between the sheet of the first week and the sheet of the second week, the ratio of the length L1 of the first filling portion along the long side direction of the sheet to the thickness T2 of the first filling portion at the position where it contacts the end face is greater than 90, and in the presence of the fourth clamping portion, the ratio of the sum of the length L1 of the first filling portion along the long side direction of the sheet and the length L2 of the fourth clamping portion along the long side direction of the sheet to the thickness T2 of the first filling portion at the position where it contacts the end face is greater than 90.

[0036]

[20] The roll according to the above-mentioned

[19] , wherein, in the absence of the fourth clamping portion, the ratio of the area S1 of the region sandwiched by the outer peripheral surface of the core and the front face of the first filling portion in a plane including the long side direction of the sheet and the radial direction of the core to the thickness T2 of the first filling portion is greater than 3.0, and in the presence of the fourth clamping portion, the ratio of the total area S1 of the region sandwiched by the outer peripheral surface of the core and the front face of the first filling portion in a plane including the long side direction of the sheet and the radial direction of the core and the area S2 of the region sandwiched by the outer peripheral surface of the core and the front face of the fourth clamping portion to the thickness T2 of the first filling portion is greater than 3.0.

[0037]

[21] A roll according to the above-mentioned

[17] , wherein, when the thickness of the second clamping portion is measured along the long side direction of the sheet, the ratio of the length L4 from the second end of the second clamping portion on the opposite side of the first end on the fixing part side to the position of the maximum thickness T6 of the second clamping portion in the long side direction to the maximum thickness T6 of the second clamping portion is greater than 12.

[0038]

[22] A roll according to the above-mentioned

[21] , wherein the ratio of the cross-sectional area S3 of the second clamping portion from the second end of the second clamping portion to the position of the maximum thickness T6 in a plane including the long side direction of the sheet and the radial direction of the winding core to the maximum thickness T6 of the second clamping portion is greater than 2.5.

[0039]

[23] The roll according to

[15] or

[17] above, wherein the sheet has protrusions projecting in the radial direction of the winding core at both ends extending along the long side direction of the sheet.

[0040]

[24] The roll according to any one of

[13] to

[23] above, wherein the sheet has a resin film.

[0041]

[25] The roll according to any one of

[13] to

[23] above, wherein the sheet material comprises an acrylic resin, a polyester resin, or a cycloolefin polymer resin.

[0042]

[26] The roll according to

[24] or

[25] above, wherein the thickness of the sheet is greater than or equal to 15 μm and less than or equal to 300 μm.

[0043]

[27] The roll according to

[13] above, wherein the first filling portion contains a coloring material or a luminescent material.

[0044]

[28] The roll according to

[14] or

[16] above, wherein the second filling part and the third filling part respectively contain a coloring material or a luminescent material.

[0045]

[29] The roll according to

[15] above, wherein the first intervening portion contains a coloring material or a luminescent material.

[0046]

[30] The roll according to the above

[17] , wherein the second intervening portion and the third intervening portion respectively contain a coloring material or a luminescent material.

[0047]

[31] The roll according to

[13] above, wherein the first filling portion contains a cured product of a curable polymer composition.

[0048]

[32] The roll according to

[14] or

[17] above, wherein the second filling portion and the third filling portion each contain a cured product of a curable polymer composition.

[0049]

[33] The roll according to

[15] above, wherein the first intervening portion includes a cured product of a curable polymer composition.

[0050]

[34] The roll according to

[17] above, wherein the second intervening portion and the third intervening portion each contain a cured product of a curable polymer composition.

[0051]

[35] The production method according to any one of

[13] to

[34] above, wherein the sheet is a laminate having a substrate and one or more functional layers laminated on the substrate.

[0052]

[36] The production method according to any one of

[13] to

[35] above, wherein the sheet is used for an optical film, a polarizing plate, or a display device.

[0053] Effects of the Invention

[0054] According to one embodiment of the present invention, a method for manufacturing a roll that can effectively alleviate the step difference caused by the starting end of the sheet can be provided, and such a roll. In addition, according to another embodiment of the present invention, a method for manufacturing a roll that can effectively alleviate the step difference caused by a fixing member can be provided, and such a roll. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 This is a perspective view of the roll according to the first embodiment.

[0056] Figure 2 This is a top view of a sample used to determine the position for measuring the in-plane phase difference.

[0057] Figure 3 Yes Figure 1 An enlarged view of a portion of the volume.

[0058] Figure 4 It is used to illustrate Figure 1 A diagram showing the dimensions of each component of the roll.

[0059] Figure 5 Yes Figure 1 An enlarged view of the vicinity of the end portion of the first filling portion of the roll.

[0060] Figure 6 It is shown Figure 1 FIG. 1 is a diagram of region R1 and region R2 in a roll.

[0061] Figure 7This is an enlarged view of a portion of another roll according to the first embodiment.

[0062] Figure 8 This is an enlarged view of a portion of another roll according to the first embodiment.

[0063] Fig. 9 This is a top view of the roll used to determine the measurement position of the laser displacement meter.

[0064] Fig.10 This is a diagram showing the displacement relative to position based on the measurement of a laser displacement meter.

[0065] Fig.11 In order to find the areas S1 and S2, Fig.10 An enlarged view of a portion of the image graph.

[0066] Fig.12 This is an enlarged view of a portion of another roll according to the first embodiment.

[0067] Fig.13 This is an enlarged view of a portion of another roll according to the first embodiment.

[0068] Fig.14 This is an enlarged view of a portion of another roll according to the first embodiment.

[0069] Fig.15 This is an enlarged view of a portion of another roll according to the first embodiment.

[0070] Fig.16 This is an enlarged view of a portion of another roll according to the first embodiment.

[0071] Fig.17 (A) and Fig.17 (B) is a diagram schematically showing the production process of the roll according to the first embodiment.

[0072] Fig.18 (A) and Fig.18 (B) is a diagram schematically showing the production process of the roll according to the first embodiment.

[0073] Fig.19 (A)~ Fig.19 (C) is a diagram schematically showing another roll production process according to the first embodiment.

[0074] Fig. 20 (A) and Fig. 20 (B) is a diagram schematically showing another manufacturing process of the roll according to the first embodiment.

[0075] Fig.21 (A) and Fig.21(B) is a diagram schematically showing another manufacturing process of the roll according to the first embodiment.

[0076] Fig. 22 (A)~ Fig. 22 (D) is a diagram schematically showing another manufacturing process of the roll according to the first embodiment.

[0077] Fig.23 (A)~ Fig.23 (C) is a diagram schematically showing another manufacturing process of the roll according to the first embodiment.

[0078] Fig.24 (A) and Fig.24 (B) is a diagram schematically showing another manufacturing process of the roll according to the first embodiment.

[0079] Fig.25 It is a perspective view of the roll body of the second embodiment.

[0080] Fig.26 Yes Fig.25 An enlarged view of a portion of the volume.

[0081] Fig. 27 It is used to illustrate Fig.25 A diagram showing the dimensions of each component of the roll.

[0082] Fig.28 It is measured Fig.25 The diagram shows the maximum thickness and length of the second intervening portion.

[0083] Fig.29 It is a diagram showing the cross-sectional area S3.

[0084] Fig.30 This is an enlarged view of a part of another roll according to the second embodiment.

[0085] Fig.31 This is an enlarged view of a part of another roll according to the second embodiment.

[0086] Fig.32 This is an enlarged view of a part of another roll according to the second embodiment.

[0087] Fig.33 This is an enlarged view of a part of another roll according to the second embodiment.

[0088] Fig.34 This is an enlarged view of a part of another roll according to the second embodiment.

[0089] Fig.35 This is an enlarged view of a part of another roll according to the second embodiment.

[0090] Fig.36 This is an enlarged view of a part of another roll according to the second embodiment.

[0091] Fig.37 This is an enlarged view of a part of another roll according to the second embodiment.

[0092] Fig.38 (A)~ Fig.38 (C) is a diagram schematically showing the production process of the roll according to the second embodiment.

[0093] Fig.39 (A) and Fig.39 (B) is a diagram schematically showing the production process of the roll according to the second embodiment.

[0094] Fig.40 (A) is a graph showing the displacement of the roll body of Example 7 relative to the position of the first filling part. Fig.40 (B) is a graph showing the displacement of the roll body of Example 8 relative to the position around the first filling part. Fig.40 (C) is a graph showing the displacement amount of the roll body of Example 9 relative to the periphery of the first filling part. DETAILED DESCRIPTION

[0095] [First embodiment]

[0096] Hereinafter, a roll body according to a first embodiment of the present invention will be described with reference to the drawings. Figure 1 is a three-dimensional diagram of the roll body of this embodiment, Figure 2 is a top view of the sample used to determine the position for measuring the in-plane phase difference, Figure 3 Yes Figure 1 An enlarged view of a portion of the scroll. Figure 4 It is used to illustrate Figure 1 A diagram showing the dimensions of each component of the scroll body, Figure 5 Yes Figure 1 An enlarged view of the vicinity of the end portion of the first filling portion of the roll. Figure 6 It is shown Figure 1 A diagram of regions R1 and R2 in a volume of Fig. 9 This is a top view of the roll used to determine the measurement position of the laser displacement meter. Fig.10 This is an image curve diagram of displacement relative to position based on the measurement of the laser displacement meter. Fig.11 In order to find the areas S1 and S2, Fig.10 An enlarged view of a portion of the image graph. Figure 7 , Figure 8 , Figure 12 to Figure 16 This is an enlarged view of a portion of another roll according to the present embodiment. Figures 17 to 19It is a figure which shows typically the manufacturing process of the roll body which concerns on this embodiment. Figure 20 to Figure 24 It is a figure which shows typically another manufacturing process of the roll body of this embodiment.

[0097] <<<Roll>>>

[0098] Figure 1 The roll body 10 shown in the figure includes a core 11 and a long strip of sheet material 12 wound around an outer peripheral surface 11A of the core 11. Figure 3 As shown, the roll body 10 further includes: a first filling portion 14, which is filled in the first gap 13 between the core 11 and the sheet 12; a second filling portion 16, which is filled in the second gap 15 between the core 11 and the sheet 12; and a fixing member 17, which is used to fix a part of the sheet 12 to the core 11. In addition, the roll body 10 further includes a fourth intervening portion 18 provided continuously with the first filling portion 14 and between the first cycle of the sheet 12 and the second cycle of the sheet 12. Figure 3 The roll body 10 shown in the figure has a fourth sandwiching portion 18, but it may also be Figure 7 The fourth intervening portion is not provided like the illustrated roll 10. The sheet 12 is wound around the core 11 a plurality of times, for example, two times or more.

[0099] <<Core>>

[0100] The shape of the winding core 11 is not particularly limited, but is preferably a columnar or cylindrical shape from the viewpoint of being able to easily wind up the sheet 12 . Figure 1 The winding core 11 shown is cylindrical. When the winding core is cylindrical, the roll 10 can be held by inserting a chuck member of the winding device into the hole 11B in the width direction DR1 of the winding core 11. When the winding core is cylindrical, the winding core has an axis member that passes through the winding core, and the roll can be held in the winding device by attaching the axis member to the winding device.

[0101] The width W1 of the winding core 11 (see Figure 1 ) is not particularly limited, for example, it can be greater than 0.1m and less than 50m. The lower limit of the width W1 of the core 11 can be greater than 0.2m, greater than 0.3m, greater than 0.7m, greater than 1.0m, greater than 1.5m or greater than 2m, and the upper limit can be less than 30m, less than 20m, less than 10m, less than 7m, less than 5m, less than 3.5m, less than 3m or less than 2.5m. The width of the core can be calculated as follows: measure the width of the core at 10 locations, and calculate the arithmetic mean of the widths of 8 locations after excluding the maximum and minimum values ​​of the 10 measured widths.

[0102] The outer diameter of the core 11 is not particularly limited, and may be, for example, 30 mm or more and 8000 mm or less. The lower limit of the outer diameter of the core 11 may be 90 mm or more or 100 mm or more, and the upper limit may be 5000 mm or less, 3500 mm or less, 2000 mm or less, 1000 mm or less, 700 mm or less, 500 mm or less, 350 mm or less, or 300 mm or less. The outer diameter of the core can be obtained by measuring the outer diameter of the core at 10 locations, and obtaining the arithmetic mean of the outer diameters of 8 locations excluding the maximum and minimum values ​​of the 10 measured outer diameters.

[0103] When the core 11 is cylindrical, the inner diameter of the core 11 is not particularly limited, and may be greater than 20 mm and less than 7500 mm. The lower limit of the inner diameter of the core 11 may be greater than 50 mm, greater than 80 mm, greater than 120 mm, or greater than 150 mm, and the upper limit may be less than 4500 mm, less than 3000 mm, less than 1500 mm, less than 900 mm, less than 600 mm, less than 400 mm, less than 250 mm, or less than 200 mm. The inner diameter of the core can be obtained by measuring the inner diameter of the core at 10 locations, and obtaining the arithmetic mean of the inner diameters of 8 locations excluding the maximum and minimum values ​​among the 10 measured inner diameters.

[0104] In order to alleviate the step difference caused by the starting end of the sheet material, there is also a case where a step is formed at the portion of the outer circumferential surface of the core that contacts the sheet material so that the position of the starting end of the sheet material is reduced by the thickness of the sheet material, but such a step is not formed at the portion of the outer circumferential surface 11A of the core 11 that contacts the sheet material 12. By using a core 11 that does not have a step at the above-mentioned portion of the outer circumferential surface 11A, it is also possible to cope with sheets 12 of various thicknesses. In this specification, "no step is formed at the portion of the outer circumferential surface of the core that contacts the sheet material" means that there is no portion with a height difference of more than 3μm on the outer circumferential surface of the central portion of the core and the portion that is more than 100mm away from the central portion in the width direction of the core. In addition, the above-mentioned step with a height difference of less than 3μm may be formed at the portion of the outer circumferential surface 11A of the core 11 that contacts the sheet material 12.

[0105] The material constituting the core 11 is not particularly limited. Examples of the material constituting the core 11 include paper, plastic, or metal. Paper also includes paper impregnated with resin. Examples of plastics include fiber reinforced plastics (FRP / FiberReinforced Plastics), polyolefins such as polyethylene (PE) or polypropylene (PP), polyvinyl chloride (PVC), polystyrene (PS), acrylonitrile-butadiene-styrene copolymer (ABS), phenolic resin, nylon, and the like. Among them, for example, in the case of optical coating processing, fiber reinforced plastics (FRP) are preferred from the viewpoints of weight, processability, and strength. Examples of fiber reinforced plastics include fiber reinforced plastics in which fibers such as glass, epoxy resin, polyester, carbon, and aramid are mixed in a main body composed of epoxy resin or phenolic resin. Examples of metals include iron, stainless steel (SUS), and aluminum.

[0106] <<Sheet>>

[0107] The sheet material 12 is in the shape of a long strip. Specifically, the sheet material 12 is thin enough relative to its width and long enough.

[0108] The width W2 of the sheet 12 (see Figure 1 ) is not particularly limited, for example, it can be greater than 0.1m and less than 50m. The "width of the sheet" in this specification refers to the length of the short side direction of the sheet (the width direction of the core). The lower limit of the width W2 of the sheet 12 can be greater than 0.2m, greater than 0.3m, greater than 0.5m, greater than 1.0m or greater than 2.0m, and the upper limit can be less than 30m, less than 20m, less than 10m, less than 7m, less than 5m, less than 3.5m or less than 3m. The width of the sheet can be calculated as follows: measure the width of the sheet at 10 locations, and calculate the arithmetic mean of the widths of 8 locations after excluding the maximum and minimum values ​​of the 10 measured widths.

[0109] The width W2 of the sheet 12 is preferably smaller than the width W1 of the core 11 . Thus, the sheet 12 can be reliably held by the core 11 .

[0110] The length of the sheet 12 can be, for example, 20 m or more and 10,000 m or less. The "length of the sheet" in this specification refers to the length of the long side of the sheet. The lower limit of the length of the sheet 12 can be 30 m or more, 40 m or more, or 50 m or more, and the upper limit can be 9,000 m or less or 8,000 m or less.

[0111] The thickness of the sheet 12 is not particularly limited, for example, it can be 3 μm or more and 600 μm or less. The lower limit of the thickness of the sheet 12 can be 10 μm or more, 15 μm or more, 20 μm or more or 30 μm or more, and the upper limit can be 500 μm or less, 400 μm or less, 300 μm or less, 200 μm or less, 110 μm or less or 80 μm or less. In the case where a film is preferred according to the use, it is not limited thereto, preferably 3 μm or more and less than 50 μm, more preferably 40 μm or less. The thickness of the sheet can be obtained by measuring the thickness of the sheet at 10 locations, and obtaining the arithmetic mean of the thickness of 8 locations after removing the maximum and minimum values ​​from the 10 measured thicknesses. It should be noted that the above-mentioned step difference is difficult to produce when the thickness of the sheet is thicker, but the thinner the thickness, the more significant it is. The present invention is particularly effective when the thickness of the sheet is thin (80 μm or less, less than 50 μm, and further less than 40 μm).

[0112] In the case where the sheet 12 contains, for example, an acrylic resin, a polyester resin (particularly polyethylene terephthalate) or a cycloolefin polymer resin, the thickness of the sheet 12 is preferably 15 μm or more and 300 μm or less. In the case where the sheet 12 contains any of these resins, the thinner the thickness of the sheet, the more significant the above-mentioned step difference is, but if the thickness of the sheet is made extremely thin, the above-mentioned step difference tends to become smaller. For example, in the case where there is a heating process of 50°C or more in the subsequent process, if it is a thin sheet, the deformation caused by the above-mentioned step difference can sometimes be eliminated. However, if the thickness of the sheet is a certain degree of thickness (for example, 15 μm or more), even if the heating process is performed, it is possible that the above-mentioned deformation cannot be eliminated. Therefore, it is particularly effective when the thickness of the sheet 12 is 15 μm or more. In addition, in the case where the sheet 12 contains any of these resins, if the thickness of the sheet is too thick, a large amount of coating material is required. Therefore, from the perspective of reducing costs, the thickness of the sheet 12 is preferably 300 μm or less. In addition, when any of these resins is contained, if the thickness exceeds 300 μm, it is sometimes difficult to produce a step difference. When the sheet 12 contains any of these resins, the lower limit of the thickness of the sheet 12 is more preferably 20 μm or more, 35 μm or more, or 50 μm or more, and the upper limit of the thickness of the sheet 12 is more preferably 250 μm or less, 200 μm or less, 150 μm or less, or 100 μm or less. When any of these resins is contained, it is particularly effective for a thickness that is neither too thin nor too thick.

[0113] In addition, when the fixing member 17 is provided, since the sheet 12 is arranged on the fixing member 17, the combined thickness of the sheet 12 and the fixing member 17 will affect the step difference caused by the winding start end of the sheet. Therefore, for example, if it is assumed that the thickness of the fixing member 17 is greater than 3 μm and less than 10 μm, the thickness of the sheet 12 is preferably thinner, so its upper limit is preferably less than 130 μm, and more preferably less than 90 μm. In addition, in the case where the fixing member is an adhesive tape, if the thickness of the fixing member exceeds 15% of the thickness of the sheet, it is more likely to affect the above-mentioned step difference. Therefore, the thickness of the sheet 12 is preferably not too thin, and the lower limit of the thickness of the sheet 12 is preferably greater than 20 μm or greater than 35 μm, for example.

[0114] As the sheet material, for example, a film, a metal foil, paper, etc. can be cited. The film can be, for example, a resin film. When the resin film is used in an application requiring light transmittance (for example, an optical film application), the resin film preferably has light transmittance. As the resin constituting such a resin film, there is no particular limitation as long as it has light transmittance, and for example, acrylic resins, polyolefin resins (polyethylene resins, polypropylene resins, cycloolefin polymer resins), polycarbonate resins, polyacrylate resins, polyester resins (polyethylene terephthalate, polyethylene naphthalate, etc.), aromatic polyether ketone resins, polyether sulfone resins, acetyl cellulose resins (for example, triacetyl cellulose resins), polyimide resins, polyamide-imide resins, polyamide resins, or a mixture of two or more of these resins, etc. can be cited. Among them, the resin film with higher softness, such as the resin film containing acrylic resin, polyolefin resin, polyester resin, acetyl cellulose resin, polyimide resin, polyamide-imide resin, or polyamide resin, is easily deformed due to the step difference caused by the winding start end of the sheet, or the step difference caused by the fixing component, so the technology of the present invention is effective. Furthermore, in recent years, in large displays, it is preferred to use low moisture permeability resins with less deformation and low water permeability. In the case of large displays, since the width of the sheet as a whole becomes a product, even if a part of it remains with the deformation caused by the step difference, the whole must be discarded. For example, acrylic resin, polyester resin, cycloolefin polymer resin is preferably used for large displays. According to the technology of the present invention, the deformation caused by the step difference can be well prevented, and mass production can be improved, so the technology of the present invention is particularly effective for sheets composed of these resins. In addition, in the case where the final product requires thinness, for example, in the case of using a film with a thickness of less than 50μm, the technology of the present invention is suitable for films of any material.

[0115] When the sheet 12 is used for an optical film, especially when it contains an acrylic resin or a cycloolefin polymer resin, the in-plane phase difference (retardation: Re) of the sheet 12 is preferably less than 10 nm. The in-plane phase difference Re of the sheet 12 being less than 10 nm means that the optical strain is small, and it can be said that there is almost no residual stress when the sheet 12 is manufactured. That is, when the in-plane phase difference Re of the sheet 12 is less than 10 nm, the polymer in the sheet 12 is uniform, so when the sheet 12 is made into a long roll, it is not easy to form a new step difference caused by the polymer state inside the sheet 12 due to certain step differences, so it is preferred. Regarding the upper limit of the in-plane phase difference Re of the sheet 12, in display applications, it is more preferably less than 8 nm, or less than 4 nm from the viewpoint that it is not easy to produce color unevenness and blackening that become issues when used in combination with a polarizing sheet. In the case of acrylic resin, if it is used for optical purposes, the film does not turn white when bent like conventional acrylic resin films, and the haze value (total haze value) is preferably as small as 1% or less or 0.5% or less.

[0116] In addition, when the sheet 12 is used for optical film and contains a polyester resin, as described above, when the polymer in the sheet 12 is uniform, it is not easy to produce a new step difference due to the internal polymer state, which is preferred. In the case where the sheet 12 contains a polyester resin, stretching is indispensable in order to obtain physical strength. Therefore, in order to make the polymer state as uniform as possible, it can be manufactured by biaxial stretching successively or simultaneously in the longitudinal and transverse directions at approximately the same magnification. As a result, a sheet containing a polyester resin with a smaller in-plane phase difference than before can be obtained. The small in-plane phase difference means that the thickness of the sheet is 10μm to 90μm and the in-plane phase difference is less than 1500nm, preferably less than 1200nm, more preferably less than 1000nm, and further preferably less than 800nm. It should be noted that in order to make the physical properties such as the elastic modulus or tear strength of the biaxially stretched polyester plastic film good, the in-plane phase difference is preferably not too small, preferably more than 200nm, and more preferably more than 400nm.

[0117] In addition, in order to further improve the physical properties, it is preferred to consider the balance between the birefringence in the in-plane direction and the birefringence in the film thickness direction. As an indicator, there is the Nz coefficient. The Nz coefficient is affected by the crystallinity and orientation inside the film, and is therefore related to the overall properties of the sheet. In the case of polyethylene terephthalate, for example, the Nz coefficient is usually 2 to 4, and particularly in the case of long rolls, in which it is not easy to produce new step differences due to the polymer state in the sheet due to certain step differences, the Nz coefficient is preferably 5 or more, more preferably 8 or more, and most preferably 10 or more. The upper limit of the Nz coefficient is about 80, preferably below 70, and most preferably below 50.

[0118] The in-plane phase difference (Re) is represented by the following formula (1) using the following parameters: the refractive index nx in the slow axis direction which is the direction in which the refractive index in the plane of the sheet is the largest; the refractive index ny in the fast axis direction which is the direction in the plane orthogonal to the slow axis direction; and the thickness t (nm) of the sheet. As can be seen from the following formula (1), when the in-plane phase difference is small, the degree of orientation is low, so there is a tendency to improve the bending resistance. The in-plane phase difference (Re) can be measured, for example, by equipment with the trade name "RETS-100" manufactured by Otsuka Electronics Co., Ltd., and the trade name "KOBRA-WR" and "PAM-UHR100" manufactured by Oji Instruments Co., Ltd.

[0119] In-plane phase difference (Re) = (nx-ny) × t… (1)

[0120] The Nz coefficient is expressed by the following formula (2) from the refractive index nz in the thickness direction of the sheet, the above nx and the above ny.

[0121] Nz coefficient = (nx-nz) / (nx-ny) (2)

[0122] When using RETS-100 to measure the above Re, the following steps can be used for measurement. First, in order to stabilize the light source of RETS-100, leave the light source for more than 60 minutes after lighting. Then, select the rotating analyzer method and select the θ mode (angular phase difference measurement mode). By selecting this θ mode, the worktable becomes a tilted rotating worktable.

[0123] Next, enter the following measurement conditions into RETS-100.

[0124] (Measurement conditions)

[0125] Delay measurement range: rotating analyzer method

[0126] Measuring point diameter: φ5mm

[0127] Tilt angle range: -40°~40°

[0128] ·Measurement wavelength range: 400nm~800nm

[0129] The average refractive index of the sample (for example, N=1.617 in the case of PET, and 1.5 in the case of an acrylic resin film).

[0130] Thickness: Thickness measured separately using SEM or optical microscope

[0131] Next, background data is obtained without placing a sample in the device. The device is set as a closed system, and the closed system is implemented every time the light source is turned on.

[0132] Then, the sample is set on the workbench in the device. The shape of the sample can be any shape, for example, it can be a rectangular shape. The size of the sample can also be 50mm×50mm. In the case of multiple samples, all need to be set in the same direction. For example, in order to set all samples in the same direction, it is preferred to mark all samples in advance.

[0133] After setting up the sample, rotate the workbench 360° on the XY plane in an environment with a temperature of 23±5℃ and a relative humidity of 50±20%, and measure the fast axis and slow axis. After the measurement, select the slow axis. Then, measure while tilting the workbench to the angle range set with the slow axis as the center, and obtain data (Re) for the set tilt angle range and the set wavelength range in units of 10°. The in-plane phase difference Re is set to the value when measuring with an incident angle of 0° and light of a wavelength of 589nm. The in-plane phase difference Re is measured at 5 points in different positions. Specifically, first, as Figure 2 As shown, draw two orthogonal imaginary lines IL1 and IL2 through the center A1 of the sample SA. If the imaginary lines IL1 and IL2 are drawn, the sample is divided into four partitions. Then, set one point at an equal distance from the center A1 in each partition, and a total of four points A2 to A4, and measure at a total of five points, namely the center A1 and points A2 to A4. Then, the arithmetic mean of the three points after removing the maximum and minimum values ​​from the measured values ​​of the five points is taken as the in-plane phase difference Re.

[0134] The sheet 12 can be a single-layer structure or a laminated structure formed by stacking more than two layers. Specifically, the sheet 12 can be a substrate monomer or a functional layer monomer, for example, it can be a laminate (for example, an optical laminate) with more than one functional layer formed on a substrate. The "functional layer" in this specification refers to a layer that intentionally exerts a certain function in the laminate. Specifically, as a functional layer, for example, a base layer, a hard coat layer, an impact absorbing layer, an anti-glare layer, an antistatic layer, a conductive layer, a heat dissipation layer, an ultraviolet absorbing layer, a special wavelength absorbing layer, a special wavelength transmission layer, a color reproducibility improvement layer, a liquid crystal layer, a phase difference adjustment layer, a viewing angle adjustment layer, a reflecting layer, a coloring layer, an anti-reflection layer (a high refractive index layer, a low refractive index layer), an antifouling layer, a water-repellent layer, an oil-repellent layer, etc., or a combination thereof, etc. The "functional layer" in this specification can be a single-layer structure or a laminated structure. However, in this specification, a "functional layer" is a layer that also exists when the sheet 12 is used, and does not include a release liner that is peeled off during use. If a release liner is present on the sheet, defects are likely to occur, and a new step difference different from the above step difference is likely to occur. Assume that a release liner is provided on the sheet 12 and the sheet is wound around the core 11 with the release liner peeled off.

[0135] The use of the sheet 12 is not particularly limited, and examples thereof include optical uses (optical film uses, polarizing plate uses, display device uses), window and door uses, automobile interior decoration uses, battery component uses, food packaging material uses, etc. Among them, if the optical film has a step difference caused by the winding start end of the sheet or a step difference caused by a fixing component, it not only affects the appearance but also may affect the light transmittance, so the technology of the present invention is particularly effective in optical uses.

[0136] The sheet 12 has a winding start end portion 12A (see Figure 3 ) and the winding end portion 12B (refer to Figure 1 ). In the roll body 10, the winding start end 12A is located on the inner side (toward the winding core 11) than the winding end 12B. Figure 3 As shown, the end face 12A1 of the winding start end 12A in the longitudinal direction DR2 is roughly aligned with the second end face 17B of the fixing member 17 described later in the cross section along the longitudinal direction DR2 of the sheet 12 and the radial direction DR3 of the winding core 11. The term "roughly aligned" in this specification means that the distance between the end face 12A1 of the winding start end 12A in the longitudinal direction DR2 and the second end face 17B is within the width W3 of the fixing member 17 (see FIG. Figure 4 ). In addition, the above “+” means that the end face 12A1 protrudes more than the second end face 17B, and the above “-” means that the end face 12A1 is retracted from the second end face 17B (that is, the second end face 17B protrudes more than the end face 12A1).

[0137] <<Fixed parts>>

[0138] The fixing member 17 is used to fix a part of the sheet 12 to the outer peripheral surface 11A of the core 11. The fixing member 17 extends in the width direction DR1 of the core 11. Thus, a part of the sheet 12 can be fixed to the outer peripheral surface 11A of the core 11 along the width direction DR1 of the core 11.

[0139] The fixing member 17 has a second end surface 17B on the opposite side to the first end surface 17A. Both the first end surface 17A and the second end surface 17B extend in the width direction DR1 of the core 11.

[0140] exist Figure 3 In the embodiment, the fixing member 17 is in close contact with the outer peripheral surface 11A of the winding core 11 and the winding start end 12A of the sheet 12, and the winding start end 12A of the sheet 12 is fixed relative to the outer peripheral surface 11A of the winding core 11. In addition, if it is the first turn of the sheet 12, the sheet 12 can also be fixed at a portion other than the winding start end 12A. Figure 3 In the embodiment, the front side of the fixing member 17 is completely in close contact with the winding start end 12A, but if Figure 8 As shown, as long as the winding start end 12A is fixed relative to the fixing component 17 to a degree that does not cause a problem during winding, for example, the winding start end 12A is fixed to a degree that does not peel off from the fixing component 17 during winding, the first filling portion 14 can also enter between the winding start end 12A and the fixing component 17.

[0141] The fixing member 17 is not particularly limited, and examples thereof include adhesive members such as adhesive members and double-sided tapes. The fixing member 17 may have elasticity (cushioning properties). The adhesive member has adhesive properties on both surfaces.

[0142] The width W3 of the fixing member 17 (see Figure 4 ) is preferably 5 mm or more and 100 mm or less. If the width W3 of the fixing member 17 is 5 mm or more, a portion of the sheet 12 can be reliably fixed to the outer peripheral surface 11A of the winding core 11. In addition, if it is 100 mm or less, the sheet 12 can be wound without causing wrinkles in the sheet 12. The "width of the fixing member" in this specification refers to the distance from the first end face to the second end face. The lower limit of the width W3 of the fixing member 17 is preferably 10 mm or more, 20 mm or more, or 30 mm or more, and the upper limit is preferably 50 mm or less, or 40 mm or less.

[0143] The thickness of the fixing member 17 is preferably 3 μm or more and 600 μm or less. If the thickness of the fixing member 17 is 3 μm or more, a portion of the outer peripheral surface 11A of the core 11 can be reliably fixed. If it is 600 μm or less, deformation of the sheet 12 can be further suppressed. The lower limit of the thickness of the fixing member 17 is preferably 5 μm or more, 10 μm or more, or 20 μm or more, and the upper limit is preferably 200 μm or less, 100 μm or less, or 50 μm or less. The thickness of the fixing member can be obtained by measuring the thickness of the fixing member at 10 locations and finding the arithmetic mean of the thicknesses at the 10 locations.

[0144] <1st gap>

[0145] The first gap 13 is located in the longitudinal direction DR2 (see Figure 3 ) is connected to the end surface 12A1 of the gap. Specifically, Figure 3 The first gap 13 shown is a gap surrounded by the outer peripheral surface 11A of the core 11, the back surface 12C of the first cycle of the sheet 12, the end surface 12A1 of the winding start end 12A, and the second end surface 17B of the fixing member 17. When the fixing member 17 is not provided, the first gap is a gap surrounded by the outer peripheral surface of the core, the back surface of the first cycle of the sheet, and the end surface of the winding start end.

[0146] The first gap 13 is a gap in contact with the end surface 12A1 and is also a gap between the winding core 11 and the sheet 12 of the first cycle and in contact with the second end surface 17B, and is therefore also a third gap described later.

[0147] <Second gap>

[0148] The second gap 15 is a gap that is in contact with the first end surface 17A of the fixing member 17. Specifically, Figure 3 The second gap 15 shown is a gap surrounded by the outer peripheral surface 11A of the core 11 , the back surface 12C of the sheet 12 of the first cycle, and the first end surface 17A of the fixing member 17 .

[0149] <First Filling Section>

[0150] The first filling portion 14 is filled in the first gap 13. That is, the first filling portion 14 is in contact with the outer peripheral surface 11A of the core 11, the back side 12C of the sheet 12 of the first week, the end face 12A1 of the winding start end 12A, and the second end face 17B of the fixing component 17. In addition, when the fixing component 17 is not provided, the first filling portion is in contact with the outer peripheral surface of the core, the back side of the sheet 12 of the first week, and the end face of the winding start end. "Filling" in this specification refers to a state in which the gap is roughly filled with the material constituting the filling portion. However, there may be voids (for example, bubbles) inside the filling portion.

[0151] The sheet 12 has: an effective area used as a product; and an ineffective area located on both sides of the effective area in the short side direction of the sheet 12 and not used as a product, and the first filling part 14 exists at least in the effective area. Since the effective area is an area used as a product, it is preferred that the first filling part 14 exists in the entire width of the effective area in the width direction DR1 of the core 11. As long as the first filling part 14 exists in the effective area, it may also exist in the ineffective area, but if the first filling part 14 exists in the ineffective area, the first filling part 14 may also overflow from the sheet 12. In addition, the ineffective area is an area that is not originally used as a product, and there is no need to ease the above-mentioned step difference, so the first filling part 14 may not exist in the ineffective area. The ineffective area varies depending on the purpose of the sheet and the width of the sheet, but is generally an area within 10 mm to 30 mm from both ends of the short side direction of the sheet to the inside. When the first filling portion 14 exists in the non-effective area, the first filling portion 14 can exist at both ends of the short side direction of the sheet, but from the viewpoint of suppressing overflow, it is preferably present at a position more than 1 mm (preferably more than 5 mm, more preferably more than 10 mm) away from the two ends toward the center of the sheet.

[0152] The edge thickness T1 of the terminal portion 14A at the separation position P1 side where the sheet 12 of the first round is separated from the core 11 in the first filling portion 14 (see Figure 4 , Figure 5), if the thickness is thicker, a new step difference may be formed due to the thickness, so the thickness is preferably thinner. It should be noted that, as described later, depending on the purpose, it is sometimes better for the edge thickness T1 to exist to a certain extent rather than not exist. The edge thickness T1 is preferably 50 μm or less, for example. From the viewpoint of being able to shorten the distance from the winding start end 12A to the point where the deformation caused by the step difference at the winding start end 12A becomes visually unrecognizable, that is, the deformation relaxation length, the edge thickness T1 is more preferably 30 μm or less, 20 μm or less, 10 μm or less, 5 μm or less, and further preferably 2 μm or less. The more the step difference caused by the winding start end is relaxed, the more the deformation of the sheet caused by the step difference is relaxed, and therefore the deformation relaxation length becomes shorter. In this specification, the "deformation relaxation length" is sometimes used to mean the length until the deformation of the sheet caused by the step difference caused by the starting end of the winding is relaxed, in addition to the length until the deformation of the sheet caused by the step difference caused by the fixing component becomes visually unrecognizable. When the deformation relaxation length is used to mean the length until the deformation of the sheet caused by the step difference caused by the fixing component becomes visually unrecognizable, the deformation relaxation length is the distance from the starting end 12A of the winding to the point where the deformation caused by the step difference of the fixing component 17 becomes visually unrecognizable. The deformation relaxation length is preferably shorter, specifically, preferably less than 100m, less than 75m, less than 60m, less than 50m, or less than 35m, less than 20m, or less than 15m. It should be noted that if the deformation relaxation length is less than 75m, the portion where the deformation of the sheet cannot be visually recognized becomes larger, which is good. As described above, the deformation relaxation length is the length until the sheet deformation caused by the step difference cannot be visually recognized, but whether there is a step difference is judged in the following way. First, in an indoor environment of more than 800Lux and less than 2000Lux, a white light source tube (white LED lamp, white fluorescent lamp, etc.) is projected into a long strip of sheet material, and the contour line of the white light source tube projected into the sheet material is judged to have a deformed part compared with the other parts of the sheet material as the presence of a step difference, and the contour line of the white light source tube projected around the step difference can be judged to be the same as the other parts of the sheet material as the absence of a step difference. The white light source tube is configured in a manner that the length direction of the white light source tube is along the long side direction of the sheet material. According to the width and length of the sheet material, the length of the white light source tube can also be changed. Specifically, the length of the white light source tube is preferably the length of the part with the step difference and the part without the step difference in the sheet material. Thus, it is easy to know the part with the step difference. In addition, if the observation environment is as bright as described above, the white light source tube itself can be lit or not. When observing, what is important is the state of the line where the white light source tube is reflected into the sheet and its outline can be seen.Therefore, as an observation condition, a side that can clearly see the outline of the white light source tube is appropriately selected. For example, in the case where the outline of the white light source tube is easier to see on the back side of the sheet than on the front side of the sheet, the white light source tube can also be reflected on the back side of the sheet to confirm whether there is a step difference. Specifically, in the case of a laminated body with a functional layer such as an anti-glare layer stacked on the front side of the substrate that is not easy to be reflected by the white light source tube, it is sometimes difficult to confirm whether there is a step difference when observed from the anti-glare layer side. Therefore, in this case, the white light source tube can be reflected on the back side of the substrate where the anti-glare layer is not stacked, and confirm whether there is a step difference. It should be noted that this judgment can also be used for rolls of various purposes such as laminated bodies with more than one functional layer stacked on the substrate, laminated bodies attached to polarizing sheets, etc. For example, in the case where an anti-glare layer is stacked on the substrate as a functional layer, it can also be judged in the following way: for the part with a step difference, the concave-convex shape that exerts an anti-glare function under pressure appears to be crushed and produces coloring such as shadows. In addition, when various functional layers are stacked and the white light source tube is difficult to be reflected on the visual side surface or the opposite side of the roll, as described above, it can be judged by the following method: the color different from other parts is seen by shadows due to shape changes.

[0153] In addition, when the sheet 12 is a film having a thickness of more than 3 μm and less than 50 μm, it is more susceptible to the step difference caused by the winding start end 12A than in the case of a thicker thickness. Therefore, when using such a film, the edge thickness T1 is preferably less than 10 μm. In addition, from the viewpoint of minimizing the above-mentioned deformation relaxation length, it is more preferably less than 7 μm, less than 5 μm, and even more preferably less than 1 μm.

[0154] From the viewpoint of minimizing the above-mentioned deformation relaxation length, the edge thickness T1 is preferably the above-mentioned thickness, but there is a case where the surface of the core is subjected to surface finishing, so that there are projections and depressions. At the end of the first filling portion, the material constituting the first filling portion is buried along the projections and depressions, resulting in a portion where the edge thickness T1 exists and a portion where the edge thickness T1 does not exist, which may become uneven. However, if the edge thickness T1 is thin, even if such an unevenness occurs, no actual damage will be caused. Therefore, in the case where there are projections and depressions and the edge thickness T1 becomes uneven, it is preferably thinner. Specifically, for example, the edge thickness T1 is preferably less than 15 μm, less than 10 μm, less than 5 μm, and more preferably less than 1 μm.

[0155] On the other hand, there is also an effect caused by the presence of the edge thickness T1. For example, the core is often reused after the use of the roll body. Therefore, the core is required to have the following reprocessability: the filling part such as the first filling part that is in contact with the core is peeled off from the core, or it is removed by washing or wiping, so that the core is reused. Therefore, for example, it is preferred that the first filling part 14 is not bonded to the core 11 as described later. In addition, in the portion where the first filling part 14 is in contact with the core 11 and the sheet 12, respectively, it is preferred that the sheet 12 is cleanly peeled off from the first filling part 14. Assuming that when the sheet 12 is peeled off from the first filling part 14, if the first filling part 14 undergoes cohesive failure, it is difficult to cleanly peel off the entire first filling part 14 from the core 11. In contrast, if the edge thickness T1 exists, it becomes the beginning of peeling off the sheet 12, so from the viewpoint of reprocessability, it is preferred that the edge thickness T1 is intentionally present. For example, from the perspective of reprocessability, the edge thickness T1 is preferably 5 μm or more. The preferred thickness of the edge thickness T1 varies depending on the material of the core and the sheet, and the edge thickness T1 can be set to 1.5 μm or more, and further to 5 μm or more. As for the upper limit of the edge thickness, since a new step difference may be formed due to the thickness, it is preferably 30 μm or less.

[0156] The edge thickness T1 can be measured using a scanning optical interference type surface profile measuring instrument. Examples of such surface profile measuring instruments include the "New View" series manufactured by Zygo Corporation.

[0157] Specifically, a scanning optical interference surface shape measuring instrument (product name "NewView7300", manufactured by Zygo Corporation) can be used to calculate the edge thickness T1 as follows. First, if all the sheets are fed out, the first filling portion 14 may adhere to the side of the sheet 12 and peel off from the core. In the case where the first filling portion 14 is attached to the side of the fed sheet 12, one or more samples having a size of 0.5 mm square or more, including the end portion 14A of the first filling portion 14, are obtained from the sheet. In addition, as long as the sample is 0.5 mm square or more in size, it is not limited to a square, but may also be a rectangle (for example, 2 mm×5 mm). The sample is cut from any part that includes the first filling portion 14 and is not attached with dirt, fingerprints, etc. Then, under the following measurement conditions, measure the edge thickness T1 of the first filling portion 14. The edge thickness T1 can be calculated as follows: measure the edge thickness at 10 locations, and calculate the arithmetic mean of the thicknesses at 8 locations after removing the maximum and minimum values ​​from the 10 measured thicknesses.

[0158] (Measurement conditions)

[0159] Objective lens: 10 times

[0160] Zoom: 1x

[0161] Measuring area: 2.17mm×2.17mm

[0162] Scan Length: 5μm

[0163] Min mod: 0.015

[0164] The thickness T2 of the first filling portion 14 at the position in contact with the distal end surface 12A1 (see Figure 4 ), when there is a fixing component 17, it is preferably thicker than the sum of the thicknesses of the fixing component 17 and the sheet 12, and when there is no fixing component 17, it is preferably thicker than the thickness of the sheet 12. By setting the thickness T2 to such a thickness, the step difference caused by the winding start end 12A can be more effectively alleviated. However, if the thickness T2 is too thick, although the step difference caused by the winding start end 12A can be alleviated, it sometimes has an adverse effect on the winding of the sheet 12. Therefore, for example, when the thickness of the sheet 12 is greater than 50μm and less than 200μm, the thickness T2 is preferably greater than 52μm and less than 220μm, and more preferably greater than 52μm and less than 150μm. In addition, when the thickness of the sheet 12 is greater than 3μm and less than 50μm, the thickness T2 is preferably greater than 50.5μm and less than 100μm.

[0165] The thickness T2 of the first filling portion 14 at the position where it contacts the terminal surface 12A1 can be measured as follows. Regarding the thickness T2, the measurement method may be different when the fourth clamping portion 18 is present and when the fourth clamping portion 18 is not present. When the fourth clamping portion 18 is not present, it can be measured using a laser displacement meter or a stereo microscope, and when the fourth clamping portion 18 is present, it can be measured using a stereo microscope. The measurement of the thickness T2 based on the laser displacement meter or the stereo microscope is performed in an environment with a temperature of 23±5°C and a relative humidity of 50±20%.

[0166] The measurement of the thickness T2 based on the laser displacement meter can be performed as follows. Regarding the following measurement method, since it utilizes the reflection of laser, it is particularly effective when the sheet 12 is transparent and the first filling part is opaque (for example, when it is colored). First, prepare a clamp and a laser displacement meter (for example, the product name is "LK-G30", manufactured by KEYENCE Co., Ltd.) for rotating the roll 10, and arrange them at specified positions respectively. The clamp is configured to be inserted into the hole 11B in the width direction DR1 of the core 11 to hold the roll 10 so that it can rotate. In addition, LK-G30 is listed as the laser displacement meter, but even if it is not LK-G30, a laser displacement meter equivalent to a successor model can also be used.

[0167] The laser displacement meter includes a laser source and a light receiving element, and is a device capable of measuring displacement based on a light receiving position in the light receiving element by receiving laser light emitted from the laser source and reflected on the surface of the first filling part 14 .

[0168] The laser displacement meters are located above the roll 10, and three are arranged so as to irradiate the laser toward the front of the roll 10. The laser displacement meters are arranged as follows. Fig. 9 As shown, the first position B1 and the second position B2 that divide the width of the sheet 12 into three equal parts are determined. The first position B1 is located on the first end 12G1 side in the short side direction of the sheet 12 (the width direction DR1 of the core 11), and the second position B2 is located on the second end 12G2 side opposite to the first end 12G1. In addition, the first laser displacement meter is configured to irradiate the laser to the midpoint C1 between the first position B1 and the first end 12G1, the second laser displacement meter is configured to irradiate the laser to the midpoint C2 between the first position B1 and the second position B2, and the third laser displacement meter is configured to irradiate the laser to the midpoint C3 between the second position B2 and the second end 12G2.

[0169] Then, the roll body 10 is mounted on the fixture, and the sheet 12 is fed out until the first filling portion 14 overflows from the roll body 10. Then, while the first filling portion 14 overflows, the core 11 is rotated at a speed of 30 mm / s and the displacement is continuously measured with a laser displacement meter at a sampling period of 200 μs, and a graph is obtained with the horizontal axis being the position (mm) and the vertical axis being the displacement (mm) (see Fig.10 ). The measurement is performed from the end portion 14A of the first filling portion 14 toward the position in contact with the end surface 12A1. In the measurement, the reference height (the line where the displacement is 0 mm) is used as the height of the core 11, and the difference between the reference height and the displacement of the first filling portion 14 is used as the thickness of the first filling portion 14. In addition, in the graph, one scale mark of the horizontal axis is set to 5 mm, and one scale mark of the vertical axis is set to 0.02 mm.

[0170] In this graph, the displacement amount starts to increase from the terminal portion 14A in the portion where the first filling portion 14 is present, but the displacement amount decreases sharply after the position in contact with the terminal surface 12A1 in the first filling portion 14. Therefore, the position E1 on the displacement curve where the displacement amount starts to decrease sharply is found in the graph. Then, by finding the difference between the line with a displacement amount of 0 mm and the displacement amount at position E1, the thickness T2 of the first filling portion 14 at the position in contact with the terminal surface 12A1 is found.

[0171] The measurement of the thickness T2 based on the stereoscopic microscope can be carried out as follows. First, the portion including the winding start end portion 12A, the first filling portion 14 and the second week of the sheet 12 is selected and fixed in such a way that the portion is not crushed. Then, the cross section of the fixed portion is ground, and the thickness T2 of the first filling portion 14 is measured using a stereoscopic microscope (for example, the product name is "digital microscope VHX-7000", manufactured by KEYENCE Co., Ltd.). In addition, as a stereoscopic microscope, a digital microscope VHX-7000 is listed, but even if it is not VHX-7000, a stereoscopic microscope equivalent to a successor model can also be used.

[0172] Since the two end portions 12G (see Figure 1 ) is a portion that is not used as a product, so as long as the length of the first filling portion 14 in the width direction DR1 of the core 11 is greater than the effective area of ​​the roll body 10 for realizing productization, it can also be smaller than the width W2 of the sheet 12.

[0173] The first filling part 14 preferably contains a coloring material or a luminescent material. By making the first filling part 14 contain a coloring material or a luminescent material, it is easy to visually check when the first filling part 14 overflows from the roll body 10. In addition, the thickness and length of the first filling part 14 are easy to check.

[0174] When the first filling portion 14 is colored, the color of the first filling portion 14 is not particularly limited, but white, gray, etc. are preferred from the viewpoint of being able to reliably grasp the presence of the first filling portion 14 and not being easily conspicuous even if the components of the first filling portion 14 adhere to the winding device.

[0175] When the first filling portion 14 is colored, the first filling portion 14 includes a coloring material. When the first filling portion 14 is a cured product of a coating material, the coloring material is preferably a material that does not hinder curing. The coloring material may be any one of a pigment and a dye, and may also be any one of an organic coloring material and an inorganic coloring material. Examples of specific coloring materials include titanium oxide, carbon black, or mixtures thereof.

[0176] When the first filling portion 14 is colored, the content of the coloring material in the first filling portion 14 is preferably 0.1 mass % or more and 50 mass % or less. If the content of the coloring material is 0.1 mass % or more, the first filling portion 14 can be visually confirmed, and if it is 50 mass % or less, even if the coloring material is an inorganic material or an organic material, reprocessability can be well maintained.

[0177] When the first filling portion 14 includes a light-emitting material, the light-emitting material is not particularly limited, and examples thereof include fluorescent materials and light-storage materials. When the first filling portion 14 includes a fluorescent material or a light-storage material, the fluorescent material or light-storage material in the first filling portion 14 can be made to emit light by irradiating the first filling portion 14 with light such as ultraviolet light or visible light.

[0178] The shape of the front side 14B of the first filling portion 14 is preferably a convex shape that bulges upward. If the shape of the front side 14B is a convex shape that bulges upward, the sheet 12 can be lifted compared to a concave shape that is sunken downward, so the above-mentioned step difference can be alleviated. Whether the shape of the front side 14B is a convex shape that bulges upward can be judged based on the curve graph of the position displacement curve in the same way as the thickness T2. Specifically, first, in the above-mentioned curve graph, the position at the location where the first filling portion 14 exists is higher than the height of the core 11, so the displacement amount increases. The intersection of the line with a displacement amount of 0 mm at the location where the displacement amount starts to increase and the position displacement curve is position E2 (refer to Fig.10 Then, draw an imaginary line IL3 passing through position E1 and position E2 (refer to Fig.10 ). If the ratio of the number of peaks above the imaginary line IL3 among the number of peaks in the position displacement curve between the position E1 and the position E2 is 50% or more, it can be judged that the shape of the front surface 14B of the first filling portion 14 is a convex shape that bulges upward. In addition, if the ratio of the number of peaks below the imaginary line IL3 among the number of peaks of more than 50% of the number of peaks in the position displacement curve between the position E1 and the position E2 is less than 50%, it can be judged that the shape of the first filling portion 14 is a concave shape that is sunken downward. In addition, when the imaginary line IL3 overlaps with the position displacement curve, it is judged to be a concave shape that is sunken downward. In the curve graph for judging the shape of the first filling portion 14, one scale of the horizontal axis is set to 5 mm, and one scale of the vertical axis is set to 0.02 mm.

[0179] When the shape of the front side 14B of the first filling part 14 is a convex shape that bulges upward, the average distance D1 from the imaginary line IL3 to the position displacement curve in the longitudinal direction is preferably greater than 0.003 mm. If the average distance D1 is greater than 0.003 mm, the sheet 12 can be effectively lifted, so the above-mentioned step difference can be further alleviated. The lower limit of the average distance D1 is more preferably greater than 0.01 mm. If the upper limit of the average distance D1 is excessively convex, it may become the cause of a new step difference, so it is preferably less than 0.1 mm, and more preferably less than 0.07 mm. The above-mentioned average distance D1 refers to the value obtained by averaging the values ​​of the five points after removing the maximum and minimum values, reading 7 peaks that are convex upwards than the imaginary line IL3 with the imaginary line IL3 as the reference line. In addition, the peak value read is the mountain part, and the larger part is selected.

[0180] The slope of the horizontal axis of the graph of the imaginary line IL3 relative to the position displacement curve is preferably 0.0020 or more and 0.0130 or less, more preferably 0.0030 or more and 0.0070 or less, and further preferably 0.0050 or more and 0.0060 or less. If the slope is 0.0050 or more, the filler can be filled without being recessed, and if it is 0.0060 or less, the filler can be filled without being greatly protruded. The lower limit of the slope is preferably 0.0020 or more, 0.0030 or more, or 0.040 or more, and the upper limit is preferably 0.0130 or less, 0.0120 or less, or 0.0100 or less.

[0181] The thickness of the first filling portion 14 preferably gradually increases from the vicinity of the separation position P1 toward the end face 12A1. By changing the thickness of the first filling portion 14 in this way, it is possible to suppress a sharp height change of the sheet 12 in the radial direction DR3 (normal direction of the outer peripheral surface 11A) of the core 11, thereby alleviating the step difference caused by the winding start end 12A.

[0182] If the thickness of the first filling portion changes drastically, there is a concern that deformation may remain due to the change in thickness, and thus the step difference caused by the beginning of winding may not be fully alleviated. Therefore, it is preferable to ensure a sufficient length of the first filling portion relative to the thickness of the sheet. However, in the case where other effects such as winding occur by lengthening the length of the first filling portion, the length of the first filling portion may be intentionally made shorter than the optimal state. Thus, although the deformation alleviation length becomes longer than when the first filling portion has the optimal length, the deformation alleviation length can be shortened compared to when the first filling portion is not provided. Therefore, in the case of Figure 4 When the fourth intervening portion 18 is present, it is preferable that the length L1 of the first filling portion 14 along the longitudinal direction DR2 of the sheet 12 (see Figure 4) and the length L2 of the fourth intervening portion 18 along the long side direction DR2 of the sheet 12 (refer to Figure 4 ) and the ratio ((length L1+length L2) / thickness T2) of the thickness T2 of the first filling portion 14 at the position in contact with the end surface 12A1 is 90 or more. Figure 7 In the case where the fourth intervening portion 18 does not exist, the length L1 of the first filling portion 14 along the longitudinal direction DR2 of the sheet 12 (see Figure 7 ) to the thickness T2 of the first filling portion 14 at a position where it contacts the terminal surface 12A1 (length L1 / thickness T2) is preferably 90 or more. From the viewpoint of shortening the above-mentioned deformation relaxation length, the lower limits of these ratios are preferably 100 or more, 110 or more, 120 or more, or 140 or more. In addition, the upper limits of these ratios are not particularly limited, and for example, they may be 1200 or less, 1000 or less, 800 or less, 500 or less, or 300 or less.

[0183] The length L1 is the length of the first filling portion 14 along the long side direction DR2 of the sheet 12 from the position in contact with the end face 12A1 to the end on the separation position P1 side. The length L2 is the length from the position directly above the end face 12A1 of the sheet 12 along the long side direction DR2 to the end on the side where the first week of sheets 12 and the second week of sheets 12 are in contact. The length L1 and the length L2 can be determined from the graph of the position displacement curve in the same way as the thickness T2. Specifically, first, the existence of the fourth clamping portion is confirmed by the method described below. In the case where the fourth clamping portion exists, the above-mentioned position E1 and position E2 are found from the graph of the position displacement curve. Next, an imaginary line IL4 (refer to Fig.10 ). Next, if the intersection of the imaginary line IL4 and the line with a displacement of 0 mm is set as position E3, the total length of the length L1 and the length L2 can be obtained by calculating the distance between the position E2 and the position E3. In addition, in the absence of the fourth clamping portion, the length L1 can be obtained by calculating the distance between the position E2 and the position E3 using the above method.

[0184] From the viewpoint of easing the above-mentioned step difference, the longer the length L1, the better. For example, when the thickness of the sheet 12 is 50 μm or more and 200 μm or less, the length L1 is preferably 110 μm or more. In order to further shorten the above-mentioned deformation relaxation length, it is preferably 1 mm or more, and more preferably 10 mm or more. However, if the length L1 is too long, it is difficult to form a convex first filling portion that bulges upward during processing, and it is possible that a wavy thickness unevenness will occur in the first filling portion. Therefore, from the viewpoint of easily obtaining a convex first filling portion 14 that bulges upward and suppressing a wavy thickness unevenness, the upper limit of the length L1 is preferably 100 mm or less.

[0185] The above (length L1+length L2) / thickness T2 and length L1 / thickness T2 can roughly represent the shape of the first filling portion 14, but in order to more appropriately represent the upward convex shape of the first filling portion 14, it is preferred to further use the area of ​​the first filling portion 14 on a plane including the long side direction DR2 of the sheet 12 and the radial direction DR3 of the core 11. Specifically, in the case of Figure 4 When the fourth intervening portion 18 is present, the plane ( Figure 4 The area S1 of the region R1 sandwiched between the outer peripheral surface 11A of the winding core 11 and the front surface 14B of the first filling portion 14 in the plane shown in FIG. Figure 6 ), and an area S2 of a region R2 sandwiched between the outer peripheral surface 11A of the winding core 11 and the front surface 18A of the fourth sandwiching portion 18 (see Figure 6 ) to the thickness T2 of the first filling portion 14 at a position in contact with the distal end surface 12A1 ((area S1+area S2) / thickness T2) is preferably 3.0 or more. Figure 6 The area S1 of the region R1 in φ represents the cross-sectional area of ​​the first filling portion 14. Figure 6 The area S2 of the region R2 in FIG. 1 represents the sum of the cross-sectional area of ​​the fourth intervening portion 18, the cross-sectional area of ​​the sheet 12 in the region R2, and the cross-sectional area of ​​the fixing member 17 in the region R2. Figure 6 , the sheet 12 on the first filling part 14 and the fourth sandwiching part 18 is peeled off to make the first filling part 14 and the fourth sandwiching part 18 overflow. In the absence of the fourth sandwiching part 18, the plane ( Figure 7 The ratio of the area S1 of the region R1 sandwiched by the outer peripheral surface 11A of the core 11 and the front surface 14B of the first filling portion 14 in the plane shown in the figure to the thickness T2 of the first filling portion 14 (area S1 / thickness T2) is preferably 3.0 or more. If these ratios are greater than 3.0, the total of the area S1 and the area S2, or the area S1, is larger relative to the thickness T2, so the sheet 12 can be effectively lifted by the first filling portion 14, thereby further alleviating the above-mentioned step difference. From the viewpoint of further alleviating the above-mentioned step difference, the lower limits of these ratios are preferably greater than 4.0, greater than 5.0, greater than 6.0, greater than 7.0, or greater than 8.0. In addition, the upper limits of these ratios are not particularly limited, for example, they can be less than 50.0, and further can be less than 17.0.

[0186] The sum of area S1 and area S2, or area S1, can be obtained as follows: In the region from position E2 to position E3, as Fig.11As shown in the figure, the product of the thickness t at each measuring point MP and the width d between each measuring point MP is calculated and summed. In addition, the width between the measuring points can be calculated based on the sampling period, the rotation speed of the core, and the outer diameter of the core. Specifically, the width between the measuring points can be calculated by the following formula (3). In formula (3), d (μm) is the width between the measuring points, ΔT (s) is the sampling period, r (rpm) is the rotation speed of the core, φ (mm) is the outer diameter of the core, and π is the circumference.

[0187] d=ΔT×(r / 60)×φ×π×1000…(3)

[0188] As described above, the core is often reused after the use of the roll body, so reprocessability is required. Therefore, the first filling part 14 is preferably not bonded to the core 11. If the reprocessability is good, the core becomes a state that can be reused after the roll body is used. The "state in which the core can be reused" in this specification refers to a state in which there is no attachment that causes the step difference by visually observing the entire outer peripheral surface of the core. The removal method varies depending on the filling material used for the first filling part. In the case of a hard coating with a high crosslinking density and a hard coating such as a display device, sometimes the thinner the thickness of the edge thickness T1, the easier it is to remove. On the other hand, in the case of a crosslinking density that is not too high and has rubber elasticity, sometimes the thicker the edge thickness T1, the easier it is to remove. In either case, it is sufficient to confirm by visual observation that there is no attachment that causes the step difference. In addition, "bonding" in this specification is a concept that includes adhesion. By making the first filling part 14 not bonded to the core 11, the first filling part 14 can be easily peeled off, so it has good reprocessability. The first filling portion 14 is preferably formed by washing or wiping the core 11, or by making a start with a blade-like member at the end of the first filling portion 14 so as not to damage the core 11, and then slowly peeling it from the core 11 with fingers or the like. In addition, the first filling portion 14 is more preferably not substantially containing an adhesive component.

[0189] When a 90° peeling test is performed in which the constituent material of the first filling portion 14 is peeled off perpendicularly to the outer peripheral surface 11A of the core 11, it is preferably peeled off from the outer peripheral surface 11A of the core 11 with a tensile force of less than 2.0 N. When the constituent material is peeled off with a tensile force of less than 2.0 N, the first filling portion 14 can be easily peeled off, thereby having good reworkability. In addition, when the constituent material is peeled off with a tensile force of 0.3 N or less, the first filling portion 14 can be more easily peeled off, thereby having excellent reworkability.

[0190] The 90° peel test can be performed using a sample and a spring tensiometer (manufactured by Ohba Measuring Instruments Co., Ltd.). Specifically, first, a mold larger than the size of the sample is prepared, and the mold is arranged on the outer peripheral surface 11A of the core 11. Then, the coating material for forming the first filling portion 14 is flowed into the mold, and it is solidified as needed to obtain a material layer. Then, the material layer is taken out from the mold, and the material layer is cut into a size of 20 mm×100 mm using a cutting machine, etc., to obtain 10 samples set on the outer peripheral surface 11A of the core 11. Then, one end of the sample is held by a spring tensiometer, and the tensile force is measured while the end is lifted vertically relative to the outer peripheral surface 11A of the core 11 in an environment where the temperature is 25°C and the relative humidity is 30% or more and 70% or less, and the sample is peeled at a peeling speed of 10 mm / second. Then, the arithmetic average of the tensile forces of the 8 samples other than the sample with the largest tensile force and the sample with the smallest tensile force among the 10 samples subjected to the 90° peel test is taken as the tensile force of the above-mentioned constituent material.

[0191] The tensile strength of the constituent material of the first filling portion 14 is preferably 3.0 MPa or more. If the tensile strength of the above-mentioned constituent material is 3.0 MPa or more, the first filling portion 14 is difficult to tear when the first filling portion 14 is peeled off, and good reprocessability can be obtained. From the viewpoint of obtaining excellent reprocessability, the lower limit of the tensile strength of the above-mentioned constituent material is more preferably 3.2 MPa or more or 3.4 MPa or more. In addition, if the tensile strength of the above-mentioned constituent material is too large, the cushioning of the first filling portion is poor, and therefore, in order to obtain good cushioning, the upper limit of the tensile strength of the above-mentioned constituent material is preferably 16.0 MPa or less, 8.0 MPa or less, or 5.5 MPa or less.

[0192] The tensile strength of the above-mentioned constituent materials can be measured in accordance with JIS K6251: 2017 using a sample and a Tensilon universal testing machine (product name "RTC-1310A", manufactured by A&D Co., Ltd.). Specifically, first, a mold larger than the size of the sample is prepared, and the mold is arranged on the outer peripheral surface 11A of the core 11. Then, a coating material for forming the first filling portion 14 is poured into the mold, and the material layer is cured as needed to obtain a material layer. Then, the material layer is taken out of the mold, and a punching knife (for example, a tensile No. 2 dumbbell punching knife manufactured by Polymer Measuring Instruments Co., Ltd.) is used to punch the material layer into the size of the dumbbell No. 2 shape described in JIS K6251: 2017 to obtain 10 samples. Then, the sample is kept at 25°C for 24 hours. Then, a pair of grippers of the Tensilon universal testing machine grip both ends of the sample in the long side direction, and a tensile test is performed under the conditions of a temperature of 25°C and a relative humidity of 30% to 70%, with an initial gripper distance of 20 mm and a tensile speed of 100 mm / min to measure the tensile strength of the sample. The arithmetic mean of the tensile strengths of 8 samples excluding the maximum and minimum values ​​among the 10 samples is taken as the tensile strength of the constituent material.

[0193] The elongation at cutting of the constituent material of the first filling part 14 is preferably 200% or more. If the elongation at cutting of the above-mentioned constituent material is 200% or more, the first filling part 14 is easy to stretch, so the first filling part 14 is not easy to tear when peeling off the first filling part 14, and good reprocessability can be obtained. From the viewpoint of obtaining excellent reprocessability, the lower limit of the elongation at cutting of the above-mentioned constituent material is more preferably 250% or more, 300% or more, or 350% or more. In addition, the upper limit of the elongation at cutting of the above-mentioned constituent material can be 850% or less, 600% or less, or 500% or less. The elongation at cutting of the above-mentioned constituent material can be measured in accordance with JIS K6251:2017 and using a sample and a Tensilon universal testing machine (product name "RTC-1310A", manufactured by A&D Co., Ltd.) in the same manner as the measurement method of tensile strength.

[0194] The tear strength of the constituent material of the first filling part 14 is preferably 1.0N / mm or more. If the tear strength of the above-mentioned constituent material is 1.0N / mm or more, the first filling part 14 is not easily torn when the first filling part 14 is peeled off, and good reprocessability can be obtained. From the viewpoint of obtaining excellent reprocessability, the lower limit of the tear strength of the above-mentioned constituent material is more preferably 2.0N / mm or more, 4.0N / mm or more, 6.0N / mm or more, 8.0N / mm or more, or 10N / mm or more. In addition, the upper limit of the tear strength of the above-mentioned constituent material can be 35N / mm or less, 30N / mm or less, or 25N / mm or less. The tear strength of the above-mentioned constituent material can be measured according to JIS K6252:2007 using a sample and a Tensilon universal testing machine (product name "RTC-1310A", A&D Co., Ltd.). The sample is made by the method described in the tensile strength column.

[0195] The hardness of the constituent material of the first filling portion 14 measured by the A-type durometer is preferably 95° or less. Pressure is always applied to the terminal portion of the first filling portion during winding, and sometimes pressure is applied due to time changes and environmental changes (temperature, humidity and / or pressure). In order to suppress the step difference caused by the terminal portion of the first filling portion, it is also effective to make the terminal portion of the first filling portion thinner, but by using a soft resin such as the hardness of the above-mentioned constituent material measured by the A-type durometer is 95° or less, the first filling portion is deformed due to the pressure when the sheet is wound, thereby suppressing the step difference caused by the terminal portion of the first filling portion. The upper limit of the above-mentioned hardness is more preferably 95° or less, 80° or less, 70° or less or 50° or less. On the other hand, in the case where the sheet is harder and the first filling portion is soft, and the difference in hardness between the sheet and the first filling portion is large, in the absence of the fourth sandwiching portion, only the first filling portion is compressed due to the pressure when the sheet is wound, and the step difference caused by the winding start end is not fully alleviated, and it is possible to produce some deformation in the sheet. Therefore, the lower limit of the hardness is preferably 10° or more, 15° or more, 20° or more, or 25° or more.

[0196] The hardness measurement by a type A durometer is performed in accordance with JIS K6253:1997. Specifically, first, a mold larger than the size of the sample is prepared, and the mold is arranged on the outer peripheral surface 11A of the core 11. Then, a coating material for forming the first filling portion 14 is poured into the mold, and it is cured as needed to obtain a material layer. Then, the material layer is taken out of the mold, and the material layer is cut out using a cutting machine, etc., to obtain 10 samples with a size of 100 mm×100 mm and a thickness of 10 mm. Then, using a type A durometer (product name "GS-719N (TYPEA)", manufactured by Teclock Co., Ltd.), the hardness is measured in an environment with a temperature of 25°C and a relative humidity of 30% to 70%. The arithmetic mean of the hardness of 8 samples excluding the maximum and minimum values ​​among the 10 samples is taken as the hardness of the above-mentioned constituent material.

[0197] When winding the sheet, the coating material flows to alleviate the step difference caused by the starting end of the winding, but in the case where the coating material is a curable polymer composition, if it shrinks during the subsequent curing, the step difference cannot be fully alleviated by the first filling part, especially in the absence of the fourth clamping part, and the sheet may be slightly deformed. Therefore, the linear shrinkage rate of the constituent material of the first filling part 14 is preferably 1.5% or less. If the linear shrinkage rate of the above-mentioned constituent material is 1.5% or less, a first filling part with excellent dimensional stability can be formed, so the first filling part can be used to fully alleviate the step difference. From the viewpoint of more fully alleviating the step difference, the upper limit of the linear shrinkage rate of the first filling part 14 is more preferably less than 1.3%, less than 1.0%, or less than 0.7%. In addition, the lower limit of the above-mentioned thermal shrinkage rate can be more than 0%.

[0198] The linear shrinkage of the above-mentioned constituent material can be measured as follows. First, a mold with a size of 130 mm square or more and a thickness of 2 mm is prepared, and a coating material for forming the first filling portion 14 is poured into the mold and solidified to obtain a sample (molded product). After complete solidification, the size of the sample is measured and compared with the size on the inside of the mold, and the linear shrinkage is calculated based on JIS K6249: 2003. The arithmetic mean of the linear shrinkage of 8 samples excluding the maximum and minimum values ​​among the 10 samples is taken as the linear shrinkage of the above-mentioned constituent material.

[0199] The first filling portion 14 can be formed by flowing or deforming the filling material. When the filling material exhibits fluidity, it is not always necessary to exhibit fluidity as long as it exhibits fluidity before or during sheet winding. Examples of the filling material include a coating material and a filling tape.

[0200] The coating material is a material that can be coated, for example, having fluidity when coated or wound. As the coating material having fluidity, not only liquids but also materials that change from liquid to solid, solids that have fluidity by heating, etc., or curable materials can be cited. In the case where the coating material is a curable material, the first filling portion 14 is formed of a cured product of the curable material.

[0201] Examples of the coating material include curable polymer compositions, thermoplastic resins, oils, starches, adhesives, tackifiers, and sols.

[0202] Examples of the curable polymer composition include curable resin compositions and curable rubber compositions. When a thermoplastic resin is used as a coating material, it is necessary to heat the resin to obtain a fluid state during coating and winding.

[0203] The filling tape is a tape that is filled in the first gap 13 to form the first filling portion 14 and is a tape or gel tape that has the property of expanding by capillary action under pressure when winding the sheet 12. The filling tape is attached or closely attached to the outer peripheral surface 11A of the core 11 for use.

[0204] As described above, the first filling portion is required to have reprocessability. Here, if the filling material (e.g., coating material, etc.) is a sealing material, the sealing material will be firmly attached to the winding core, so the reprocessability is poor. In contrast, the demolding material is based on the premise of being removed from the mold, so it is excellent in reprocessability. Therefore, from the viewpoint of reprocessability, the demolding material is preferred as the filling material (e.g., coating material, etc.).

[0205] The shear viscosity of the filling material (e.g., coating material, etc.) at a shear rate of 1 / s at 25°C is preferably 500 Pa·s or less. For example, it is also possible to consider extending the filling material (e.g., coating material, etc.) applied to the core using a scraper or the like while adjusting the shape of the filling material before the sheet is wound, but in the case of extending the filling material by such a process, a lot of work is required. In contrast, if the shear viscosity of the filling material is 500 Pa·s or less, the filling material can be extended into a desired shape by utilizing the pressure during sheet winding, thereby omitting a special process for extending the filling material. The above-mentioned shear viscosity is more preferably 200 Pa·s or less. From the viewpoint of making the filling material easy to extend, the above-mentioned shear viscosity is preferably 300 Pa·s or less, 100 Pa·s or less, or 50 Pa·s or less.

[0206] On the other hand, from the viewpoint of shortening the deformation relaxation length, the shear viscosity is preferably 10 Pa·s or more and 75 Pa·s or less, and more preferably 20 Pa·s or more and 50 Pa·s or less. If the shear viscosity is 10 Pa·s or more, the fluidity will not become too high, so the deformation of the sheet 12 can be relaxed. In addition, if it is 75 Pa·s or less, the deformation caused by the terminal end of the first filling part can be suppressed.

[0207] Furthermore, from the viewpoint of further suppressing the overflow of the filling material, when the shear viscosity is 15 Pa·s or more, and further 20 Pa·s or more, it is preferable because the filling material can be suppressed from overflowing from between the core 11 and the sheet 12 during coating. In addition, the shear viscosity is preferably 60 Pa·s or more. If the shear viscosity is 60 Pa·s or more, the fluidity of the filling material is low, and the filling material can be suppressed from overflowing from between the core and the sheet due to the pressure during coating and / or winding.

[0208] The above-mentioned shear viscosity of the filler can be measured using a dynamic viscoelasticity measuring device (for example, manufactured by Anton-Paar Japan Co., Ltd.). Specifically, the shear viscosity of the filler at a shear rate of 1 [1 / s] is measured 10 times using a parallel plate having a diameter of 25 mm under an environment of a temperature of 25° C. and a relative humidity of 30% to 70%, and the arithmetic mean of 8 shear viscosities excluding the maximum and minimum values ​​among the 10 measured shear viscosities is obtained to obtain the shear viscosity.

[0209] The filling material (eg, coating material) preferably does not contain volatile components such as solvents. When the filling material does not contain volatile components, the first filling portion 14 is less likely to experience shape changes such as cracks, and sheet marks are less likely to occur.

[0210] (Coating material)

[0211] The coating material can be applied when the first filling portion is formed, but is preferably a material with low fluidity in the state of the roll 10. "Low fluidity in the state of the roll" in this specification means that the coating material will not overflow from the roll when the roll is transported or manufactured. When the first filling portion 14 is formed in the first gap 13, it is necessary to be able to apply the coating material. However, if the coating material has high fluidity in the state of the roll 10, the first filling portion may overflow and cause contamination during transportation, manufacturing, etc. On the other hand, if the coating material is a material that can be applied when the first filling portion 14 is formed and has low fluidity in the state of the roll 10, the first filling portion 14 can be formed in the first gap 13, and overflow or contamination of the first filling portion 14 can be suppressed. As such a material that can be applied when the first filling portion is formed but has low fluidity in the state of the roll 10, a curable polymer composition can be cited.

[0212] When the coating material is a curable polymer composition, as the coating material, for example, an ionizing radiation curable polymer composition (ionizing radiation curable resin composition, ionizing radiation curable rubber composition), a thermosetting polymer composition (thermosetting resin composition, thermosetting rubber composition), a room temperature curable polymer composition (a polymer composition that cures at room temperature of about 20° to 30° Celsius) (room temperature curable resin composition, room temperature curable rubber composition), etc. can be used.

[0213] Among room temperature curable polymer compositions, there are, for example, two-component curable polymer compositions consisting of a main agent and a curing agent, and one-component curable polymer compositions that are cured using moisture in the air. The portion in the first filling portion that is present in the center of the sheet is roughly in a sealed state when the sheet is wound, so it is difficult for air to come into contact with the portion, and it may not be fully cured. In contrast, for a two-component curable polymer composition, if a main agent and a curing agent are mixed, the reaction begins, so curing can be performed only by time management. In addition, a two-component curable polymer composition is preferred in that it is excellent in storage stability compared to a one-component curable polymer composition.

[0214] As the ionizing radiation curable polymer composition, for example, there can be cited compositions containing compounds having ethylenically unsaturated groups such as (meth)acryloyl, vinyl, and allyl groups. As ionizing radiation irradiated when curing the ionizing radiation curable polymer composition, there can be cited visible light, ultraviolet rays, X-rays, electron beams, α rays, β rays, and γ rays.

[0215] Regarding the ionizing radiation curable polymer composition, for example, an acrylic gel composition that forms an acrylic gel by irradiating ionizing radiation can be cited. The acrylic gel composition includes, for example, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-hexyl (meth)acrylate, n-pentyl (meth)acrylate, isopentyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, isomyristyl (meth)acrylate, lauryl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, tridecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, etc. In this specification, "(meth)acrylate" means both "acrylate" and "methacrylate".

[0216] As the heat-curable polymer composition and the room temperature curable polymer composition, for example, polyurethane resin composition, epoxy resin composition and silicone composition can be cited. Among them, silicone composition can be preferably used. As the silicone composition, silicone gel composition and silicone rubber composition can be cited, which are both easy to alleviate the above-mentioned step difference and deformation and are preferred.

[0217] The "cured silicone gel (silicone gel)" formed by curing a silicone gel composition in this specification refers to a cured product having an extremely low crosslinking density and containing an organopolysiloxane as a main component, and refers to a cured product having a needle penetration of 10 to 150 based on JIS K2220:2013 (1 / 4 cone). This corresponds to a case where the measured value (rubber hardness value) in the rubber hardness measurement based on JIS K6249:2003 is 0 and the hardness is so low (that is, soft) that an effective rubber hardness value is not shown, and in this respect, it is different from the so-called silicone rubber composition and the cured silicone rubber (rubber-like elastic body).

[0218] Silicone rubber compositions include single-component curable silicone rubber compositions and two-component curable silicone rubber compositions. Among the single-component curable silicone rubber compositions, there are condensation-curable rubber compositions that cure at room temperature and addition-reactive rubber compositions that cure by heating. In addition, among the two-component curable silicone rubber compositions, there are condensation-curable rubber compositions that cure at room temperature and addition-reactive rubber compositions, as well as addition-reactive rubber compositions that cure by heating. In addition, ionizing radiation-curable rubber compositions can also be formed by modifying other resins in the silicone rubber composition. In the present invention, any curing method can be used, among which, from the viewpoint of being able to cure uniformly and having excellent storage stability, a two-component curable silicone rubber composition is preferred.

[0219] As a silicone rubber composition, for example, an RTV (Room Temperature Vulcanizing) silicone rubber composition can be cited. Compared with an ionizing radiation curable polymer composition, the RTV silicone rubber composition has a smaller shrinkage rate and good dimensional stability. In addition, it has excellent fluidity before curing, so it is easy to penetrate into the gap between the core 11 and the sheet 12 or between the sheets 12. In addition, it has low fluidity after curing. Furthermore, the RTV silicone rubber composition has deep curing properties, so it is easy to uniformly perform a curing reaction regardless of the thickness at the time of coating. In addition, the composition also has excellent demolding properties, so it is easy to peel off the cured product to form a state that can be used as a roll again.

[0220] Among the above-mentioned RTV silicone rubber compositions, there are condensation reaction curing RTV silicone rubber compositions, addition reaction curing RTV silicone rubber compositions, and the like according to the curing reaction mechanism. In the present invention, all of them can be preferably used. If it is a condensation reaction curing RTV silicone rubber composition, it will not hinder curing, so it is preferred. If it is an addition reaction curing RTV silicone rubber composition, the curing shrinkage is smaller, so it is preferred. In the present invention, there is a tendency that the larger the curing shrinkage of the material, the greater the thickness of the coating material required to alleviate the above-mentioned step difference. Therefore, especially in thin sheets (for example, the thickness of the sheet 12 is 3μm to 45μm), it is preferred to use an addition reaction curing RTV silicone rubber composition.

[0221] The RTV silicone rubber composition is preferably liquid silicone rubber LSR (Liquid Silicone Rubber) because no special processing equipment is required.

[0222] It should be noted that in order to exert the desired functions, functional components may be included in the above-mentioned various compositions. For example, silicone rubber compositions are generally electrical insulators, and therefore sometimes become charged due to contact with the winding core 11, the sheet 12, or other substances. In this case, the silicone rubber composition may contain a conductive filler. This can prevent foreign matter such as dust from mixing in, thereby preventing it from becoming the cause of the above-mentioned step difference.

[0223] As conductive fillers mixed into the silicone rubber composition, carbon black (acetylene black, Ketjen black), silver powder, gold-plated silica, graphite, conductive zinc oxide, etc. are listed. In addition, in recent years, ion conductive silicone rubber has also been developed, and this ion conductive silicone rubber can also be used.

[0224] The silicone gel composition may be mixed with any component within the range that does not impair the purpose of the present invention. Examples of such components include reaction inhibitors, inorganic fillers, organopolysiloxanes containing no silicon-bonded hydrogen atoms and no silicon-bonded alkenyl groups, heat resistance imparting agents, flame retardancy imparting agents, thixotropy imparting agents, pigments, dyes, and the like.

[0225] The reaction inhibitor is a component for inhibiting the reaction of the above-mentioned composition, and specific examples thereof include acetylene-based, amine-based, carboxylate-based, and phosphite-based reaction inhibitors.

[0226] As inorganic fillers, for example, fumed silica, crystalline silica, precipitated silica, hollow fillers, silsesquioxane, fumed titanium dioxide, magnesium oxide, zinc oxide, iron oxide, aluminum hydroxide, magnesium carbonate, calcium carbonate, zinc carbonate, layered mica, carbon black, diatomaceous earth, glass fiber and other inorganic fillers; and fillers obtained by surface hydrophobizing these fillers with organic silicon compounds, such as organic alkoxysilane compounds, organic chlorosilane compounds, organic silazane compounds and low molecular weight siloxane compounds. In addition, silicone rubber powder, silicone resin powder, etc. can also be combined.

[0227] When the coating material is an adhesive, the adhesive may be a denture stabilizer. Denture stabilizers can be roughly divided into denture adhesives and denture liners, and denture adhesives may also be used as adhesives in denture stabilizers. When adhesives are classified into, for example, powder type, cream type, or tape type, like denture adhesives, the adhesive used as the coating material is a powder type or cream type adhesive.

[0228] Regarding adhesives, in addition to the adhesive itself showing adhesiveness, it can also show adhesiveness through water. For example, a powder-type adhesive absorbs water when in contact with water and shows adhesiveness. For example, a cream-type adhesive is formed by creaming an adhesive powder component with an ointment base, and it shows adhesiveness.

[0229] The binder preferably comprises a water-soluble polymer. As the water-soluble polymer, it is not particularly limited, for example, alginic acid, alginates (such as sodium alginate, potassium alginate, ammonium alginate, alginate esters etc.), natural polymer compounds (such as gum arabic, tragacanth, locust bean gum, xanthan gum, guar gum, agar, gelatin, locust bean gum, carrageenan etc.), cellulose-based polymers (such as methylcellulose, sodium carboxymethylcellulose, hydroxyethylcellulose, hydroxypropyl methylcellulose, hydroxypropyl cellulose etc.), polyethylene glycol, polyvinyl pyrrolidone, polyvinyl alcohol, methyl vinyl ether, carboxyvinyl polymer, acrylamide and acrylic acid copolymer, sodium polyacrylate, polyethylene oxide etc. can be enumerated. These water-soluble polymers can be used alone or in any combination of two or more.

[0230] Among the above-mentioned cellulose-based polymers, sodium carboxymethylcellulose is preferred. Sodium carboxymethylcellulose is the sodium salt of polycarboxymethyl ether of cellulose, also known as sodium carboxymethylcellulose. Sodium carboxymethylcellulose is a powder that hydrates when wetted and exhibits adhesiveness or elasticity, thereby imparting further adhesiveness to the adhesive.

[0231] As for the adhesive as a coating material, as long as it can be coated, it can be further mixed with an oily base, an aqueous base, a powder base, a gum base, an excipient, an emulsifier, a wetting agent, a pH adjuster, a viscosity adjuster, a plasticizer, a pigment, etc. As these bases and additives, bases and additives that have been widely used in denture stabilizers can be cited.

[0232] For example, when the adhesive is modulated into a paste-like form such as a cream type, the oily base is used as the base. As the oily base, mineral oil components (e.g., liquid paraffin, vaseline, gelled hydrocarbons, etc.) commonly used in non-aqueous adhesives (e.g., cream types) can be cited.

[0233] As cream-type adhesives, for example, New Polygrip (registered trademark) S, New Polygrip (registered trademark) V, New Polygrip (registered trademark) additive-free, Polydent (registered trademark) NEO tooth stabilizer (all manufactured by Glaxo Smith Kline Consumer Healthcare Japan), Tough Grip (registered trademark) cream-free (manufactured by Kobayashi Pharmaceutical Co., Ltd.), and Collect (registered trademark) cream (manufactured by Shionogi Pharmaceutical Co., Ltd.) can be used.

[0234] When the coating material is an adhesive, the adhesive may be a denture liner (buffer type) of a denture stabilizer. The adhesive enhances adhesion by improving the edge sealing effect. Such an adhesive may include, for example, a water-insoluble polymer. The water-insoluble polymer is not particularly limited, and may be, for example, a polyethylene resin such as a vinyl acetate resin.

[0235] As the adhesive, for example, Polydent (registered trademark) Cushion (manufactured by Glaxo Smith Kline Consumer Healthcare Japan), Tough Grip (registered trademark) Cushion Transparent, Tough Grip (registered trademark) Cushion Pink, Soft Tough Grip (registered trademark) (all manufactured by Kobayashi Pharmaceutical Co., Ltd.), Cushion Collect (registered trademark) EZ (manufactured by Shionogi Pharmaceutical Co., Ltd.), New Riodent White, New Riodent Pink (both manufactured by Lion Co., Ltd.), etc. can be used.

[0236] When the coating material is a sol, examples of the sol include silica sol, alumina sol, and metal oxide sols such as zirconium oxide sol, titanium oxide sol, cerium oxide sol, tin oxide sol, and niobium oxide sol.

[0237] In order to prevent the coating material from excessively flowing and to allow the coating material to flow to the vicinity of the position (separation position) P1 where the first-round sheet 12 separates from the outer peripheral surface 11A of the core 11 , it is preferable to appropriately adjust the viscosity of the coating material during coating.

[0238] The coating material is applied in a linear shape, but the coating amount per unit width of the coating material is preferably an amount that can obtain the thickness T1 to T3 in the above range in the first filling portion 14. Specifically, for example, the lower limit of the coating amount per unit width of the coating material is preferably 0.2 cm 3 If the coating amount of the coating material is too small, for example, air may be mixed in when applying with a syringe, and insufficient coating may occur when it is difficult to eject the coating material from the syringe or when applying by moving the sheet. However, if the coating amount is 0.2 cm 3 / m or more, such a situation can be suppressed. In addition, the upper limit of the coating amount per unit width of the coating material is preferably 3.5cm 3 If the coating amount of the coating material is too much, the coating material may drip due to its own weight or a new step difference may be generated. However, if the coating amount is 3.5 cm 3 / m or less, this can be suppressed. The lower limit of the above-mentioned coating amount is more preferably 0.3cm 3 / m or more, and the upper limit of the coating amount is more preferably 2.0cm 3 / m or less or 1.5cm 3 / m or less.

[0239] (Filling tape)

[0240] As the constituent material of the filling tape, the adhesive, adhesion agent, or gel described in the above-mentioned coating material column can be listed. As the gel, for example, silicone gel formed by the above-mentioned silicone gel composition, acrylic gel formed by the above-mentioned acrylic gel composition, polyolefin gel, polyurethane gel, butadiene gel, isoprene gel, butyl gel, styrene butadiene gel, ethylene vinyl acetate copolymer gel, ethylene-propylene-diene terpolymer gel, or fluorine gel can be listed. As the filling tape, for example, Touch Collect (registered trademark) II (manufactured by Shionogi Pharmaceutical Co., Ltd.) or αGEL (registered trademark) (manufactured by Taica Corporation) can be used.

[0241] The length of the filling tape is preferably greater than the width of the effective area in the width direction DR1 of the core 11. By setting the length of the filling tape to such a length, the first filling portion can be formed over the entire width of the effective area, thereby alleviating the step difference caused by the winding start end 12A of the sheet 12 over the entire width of the effective area. From the viewpoint of suppressing overflow of the filling tape when winding the sheet 12, the filling tape is preferably arranged so as to be spaced inward from both ends of the short side direction of the sheet 12 in the width direction DR1 of the core 11 by more than 1 mm, more than 10 mm, or more than 30 mm. In addition, the length of the filling tape refers to the length of the filling tape in the width direction DR1.

[0242] The width of the filling band is preferably greater than 5 mm. By setting the width of the filling band to such a width, the step difference caused by the winding start end 12A of the sheet 12 can be more effectively alleviated. The lower limit of the width of the filling band is more preferably greater than 6 mm, greater than 7 mm, or greater than 8 mm. From the viewpoint of suppressing the overlapping of the filling band, the upper limit of the width of the filling band is preferably less than the outer circumference of the core 11. It should be noted that the width of the filling band refers to the length of the filling band in the long side direction DR2 of the sheet 12.

[0243] The thickness of the filling tape is preferably greater than the height of the upper surface 12A2 of the winding start end 12A. By setting the thickness of the filling tape to such a thickness, the filling tape can be expanded over a wide range when the sheet 12 is wound, so that the step difference caused by the winding start end 12A of the sheet 12 can be more effectively alleviated. Regarding the specific thickness of the filling tape, for example, when the thickness of the sheet 12 is greater than 50 μm and less than 200 μm, it is preferably greater than 52 μm and less than 220 μm. In addition, when the thickness of the sheet 12 is greater than 3 μm and less than 50 μm, it is preferably greater than 50.5 μm and less than 100 μm.

[0244] <Second filling section>

[0245] The second filling portion 16 is filled in the second gap 15 . That is, the second filling portion 16 is in contact with the outer peripheral surface 11A of the core 11 , the back surface 12C of the sheet 12 , and the first end surface 17A of the fixing member 17 .

[0246] The physical properties such as tensile strength of the constituent material of the second filled portion 16 are the same as those of the constituent material of the first filled portion 14 , and thus description thereof is omitted here.

[0247] The second filling portion 16 can be formed by applying a filling material or deforming the filling material. As the filling material, a coating material or a filling tape can be cited. The filling material, coating material and filling tape are the same as the filling material, coating material and filling tape described by the first filling portion 14, so the description is omitted. The constituent material of the second filling portion can be the same as the constituent material of the first filling portion 14, or it can be different.

[0248] The thickness of the second filling portion 16 preferably gradually decreases from the first end surface 17A toward the vicinity of the arrival position P2 where the first-circle sheet 12 reaches the outer peripheral surface 11A of the winding core 11. By changing the thickness of the second filling portion 16 in this way, it is possible to suppress a sharp change in the height direction of the sheet 12, thereby alleviating the step difference caused by the fixing member 17.

[0249] Since the two end portions 12G of the sheet 12 extending along the long side direction DR2 are not used as products, the second filling portion 16 can be smaller than the width W2 of the sheet 12 as long as the length in the width direction DR1 of the core 11 is greater than the effective area in the roll body 10 for productization.

[0250] <Fourth Interposition Section>

[0251] Since the first filling portion has a tendency to be softer than the sheet, if the height of the first filling portion at the position in contact with the end face of the winding start end is the same height as the upper surface of the winding start end, when the sheet is wound, a step difference may be generated at the corner between the end face of the winding start end and the upper surface. In contrast, when the fourth clamping portion 18 is formed, the fourth clamping portion 18 can absorb the difference in hardness between the first filling portion 14 and the sheet 12, thereby reducing the step difference at the corner between the end face 12A1 of the winding start end 12A and the upper surface 12A2. In addition, by the presence of the fourth clamping portion 18, it is possible to suppress the stress concentration on the portion of the step difference caused by the winding start end 12A, and the deformation of the sheet 12 after the third week can be smoothed, thereby alleviating the step difference.

[0252] The fourth intervening portion 18 preferably contains a coloring material and a luminescent material similarly to the first filling portion 14. By making the fourth intervening portion 18 contain a coloring material and a luminescent material, it is easy to visually identify the fourth intervening portion 18 when it overflows from the roll body 10. In addition, the existence of the fourth intervening portion 18 is easy to confirm. The coloring material and the luminescent material contained in the fourth intervening portion 18 are the same as the coloring material and the luminescent material described in the column of the first filling portion 14, and therefore the description thereof is omitted.

[0253] When the sheet 12 is transparent and the fourth intervening portion 18 is colored, it is possible to easily confirm the presence of the fourth intervening portion 18 by visual inspection. Specifically, first, the sheet 12 is fed out from the roll 10 until the surface becomes the second-week sheet 12. Then, in the roll 10 where the second-week sheet 12 becomes the surface, the vicinity of the winding start end 12A is visually observed to observe whether there is a colored portion on the winding start end 12A. When there is a colored portion on the winding start end 12A, it can be determined that the fourth intervening portion 18 exists, and when there is no colored portion, it can be determined that the fourth intervening portion 18 does not exist.

[0254] Even when the sheet 12 is transparent and the fourth intervening portion 18 includes a luminescent material, the presence of the fourth intervening portion 18 can be easily confirmed by visual inspection as described above. When the luminescent material is a material that emits light by irradiation with light such as ultraviolet light or visible light, the presence of the fourth intervening portion 18 can be confirmed by irradiating the light.

[0255] When the thickness of the sheet 12 is 50 μm or more and 200 μm or less, the thickness T3 of the fourth intervening portion 18 (see Figure 4 ) is preferably greater than 2 μm and less than 110 μm. If the thickness T3 of the fourth clamping portion 18 is within this range, the adverse effect on the winding of the sheet 12 can be avoided, and the above-mentioned deformation relaxation length can be shortened. It should be noted that even if the thickness T3 of the fourth clamping portion 18 exceeds 110 μm, the above-mentioned deformation relaxation length can be shortened, but it may have an adverse effect on the winding of the sheet 12.

[0256] When the thickness of the sheet 12 is 3 μm or more and less than 50 μm, and further less than 40 μm, the sheet 12 is more likely to be deformed due to the step difference caused by the winding start end 12A than when the thickness of the sheet 12 is thick. Therefore, the thickness T3 of the fourth sandwiching portion 18 is preferably 0.5 μm or more and 50 μm or less. If the thickness T3 of the fourth sandwiching portion 18 is within this range, it is possible to avoid adverse effects on the winding of the sheet 12 and shorten the above-mentioned deformation relaxation length.

[0257] The thickness T3 of the 4th clamping portion 18 is set to the maximum thickness of the 4th clamping portion 18. The thickness T3 of the 4th clamping portion 18 is measured as follows. First, the portion including the winding start end portion 12A, the 4th clamping portion 18 and the 2nd week of the sheet 12 is selected and fixed in a manner that the portion is not crushed. Then, the cross section of the fixed portion is ground, and the thickness T3 of the 4th clamping portion 18 is measured using a solid microscope (for example, the product name is "digital microscope VHX-7000", manufactured by KEYENCE Co., Ltd.).

[0258] The fourth interposed portion 18 can be formed by applying a filling material or deforming the filling material. As the filling material, a coating material or a filling tape can be cited. The filling material, the coating material, and the filling tape are the same as the filling material, the coating material, and the filling tape described by the first filling portion 14, so the description thereof is omitted. The constituent material of the fourth interposed portion 18 may be the same as or different from the constituent material of the first filling portion 14.

[0259] <<Other volumes>>

[0260] The end face 12A1 of the winding start end 12A of the sheet 12 of the roll body 10 and the second end face 17B of the fixing member 17 are roughly aligned in the cross section along the long side direction DR2 of the sheet 12 and the radial direction DR3 of the winding core 11, but may also be as follows: Fig.12 As shown in the roll body 20, the end face 12A1 of the winding start end 12A of the sheet 12 protrudes from the second end face 17B of the fixing member 17. In this case, the second gap 15 may be filled with the second filling portion 16, and the third filling portion 22 may be located between the outer peripheral surface 11A of the winding core 11 and the back surface 12C of the first cycle of the sheet 12 and fill the third gap 21 on the second end face 17B side.

[0261] <Third Gap>

[0262] The third gap 21 is a gap in contact with the second end surface 17B of the fixing member 17. Specifically, Fig.12 The third gap 21 shown is a gap surrounded by the outer peripheral surface 11A of the core 11 , the back surface 12C of the sheet 12 of the first cycle, and the second end surface 17B of the fixing member 17 .

[0263] <Third filling section>

[0264] The third filling portion 22 is the same as the second filling portion 16 except that it fills the third gap 21 , and thus the description thereof is omitted here.

[0265] The roll body 10 is filled with the second filling portion 16 in the second gap 15, but from the viewpoint of alleviating the step difference caused by the winding start end 12A of the sheet 12, it is sufficient to fill the first gap 13 with the first filling portion 14, so it is also possible to Fig.13 As in the illustrated roll 30, the second gap 15 is not filled with the second filling portion 16. The second gap 15 of the roll 30 is hollow.

[0266] The roll body 10 is filled with the first filling portion 14 in the first gap 13, but from the viewpoint of alleviating the step difference caused by the fixing member 17, it is sufficient to fill the second gap 15 with the second filling portion 16, so it is also possible to Fig.14As in the illustrated roll 40, the first gap 13 is not filled with the first filling portion 14. The first gap 13 of the roll 40 is hollow.

[0267] The roll body 10 has a fixing member 17, but Fig.15 As shown, more than two fixing parts may be provided. Fig.15 In the roll body 50 shown in the figure, in addition to the fixing member 17, a fixing member 51 is provided on the first end surface 17A side of the fixing member 17. Fig.15 In the roll body 50 shown, the end face 12A1 of the winding start end 12A of the sheet 12 protrudes from the second end face 17B of the fixing member 17. Therefore, in order to suppress the step difference caused by the fixing member 17, it is preferred that the second gap 15 is filled with the second filling part 16, and the third gap 21 is filled with the third filling part 22. Fig.15 In the shown roll body 50, in order to suppress the step difference caused by the fixing component 51, it is preferred that the second gap 52 on the side of the first end face 51A described later of the fixing component 51 is filled with a second filling portion 53, and the third gap 54 on the side of the second end face 51B described later of the fixing component 51 is filled with a third filling portion 55.

[0268] <Fixed parts>

[0269] The fixing member 51 has a second end face 51B opposite to the first end face 51A. The first end face 51A and the second end face 51B both extend in the width direction DR1 of the core 11. The fixing member 51 is the same as the fixing member 17, and thus description thereof is omitted here.

[0270] <Second gap>

[0271] The second gap 52 is a gap that is in contact with the first end surface 51A of the fixing member 51. Specifically, Fig.15 The second gap 52 shown is a gap surrounded by the outer peripheral surface 11A of the core 11 , the back surface 12C of the sheet 12 of the first cycle, and the first end surface 51A of the fixing member 51 .

[0272] <Third Gap>

[0273] The third gap 54 is a gap that is in contact with the second end surface 51B of the fixing member 51. Specifically, Fig.15 The third gap 54 shown is a gap surrounded by the outer peripheral surface 11A of the core 11 , the back surface 12C of the sheet 12 of the first cycle, and the second end surface 51B of the fixing member 51 .

[0274] <Second Filling Section and Third Filling Section>

[0275] The second filling part 53 is the same as the second filling part 16 except that it fills the second gap 52, and thus its description is omitted. The third filling part 55 is the same as the second filling part 16 except that it fills the third gap 54, and thus its description is omitted.

[0276] The roll body 10 is provided with a fixing member 17, but it may also be Fig.15 The roll body 60 shown does not include the fixing member 17 .

[0277] exist Fig.12 , Fig.13 , Fig.15 , Fig.16 Length L1, length L2, thickness T2, thickness T3, area S1, and area S2 are not shown, but in rolls 20, 30, 50, and 60, length L1, length L2, thickness T2, thickness T3, (length L1+L2) / thickness T2, and (area S1+S2) / thickness T2 are the same as those of roll 10.

[0278] The rolls 20, 30, 50, and 60 all include the fourth intervening portion 18, but may not include the fourth intervening portion. In this case, the length L1 / thickness T2, the area S1 / thickness T2 and Figure 7 The same is true for the roll 10 shown.

[0279] exist Fig.13 In the embodiment, the front surface of the fixing member 17 is in close contact with the winding start end 12A, but it can also be in close contact with Figure 8 In the illustrated roll 10 , the first filling portion 14 is similarly inserted between the winding start end portion 12A and the fixing member 17 .

[0280] <<Method for manufacturing roll>>

[0281] The roll 10 can be manufactured, for example, by the following method. Fig.17 As shown in FIG. 2 (A), the fixing member 17 is arranged on the outer peripheral surface 11A of the core 11 along the width direction DR1 of the core 11 .

[0282] After the fixing member 17 is arranged, a coating device such as a dispenser or a syringe is used, such as Fig.17 As shown in (B), the coating materials 201 and 202 are applied to the outer peripheral surface 11A of the core 11 along the width direction DR1 of the core 11. The coating material 201 is applied in a manner of contacting the second end surface 17B of the fixing member 17, and the coating material 202 is applied in a manner of contacting the first end surface 17A of the fixing member 17. In this case, for example, two coating devices may be used to apply the coating materials 201 and 202 at the same time.

[0283] In the above, the coating material 201 is applied in contact with the second end face 17B, and the coating material 202 is applied in contact with the first end face 17A. However, if the coating material has high wettability and low viscosity, the coating material 202 may be applied in contact with the second end face and the first end face, and may be wetted and spread between the winding start end and the fixing member and between the winding start end and the back of the sheet. The coating material can be controlled to achieve a preferred state, but if there is excessive impregnation or wet spread, solidification may occur at an uncontrollable position, and as a result, a new step difference may be generated. In addition, in the case where the viscosity of the filling material is high (for example, a strip-shaped material) or the wettability of the coating material is low, if the filling material or the coating material is configured, there is a high possibility that the solidification will occur in a state where the filling material or the coating material is only wetted and extended to the vicinity of the configuration. Therefore, in the case where the subsequent process is wound without sufficient wetting and extension, more material will solidify in a thicker state near the beginning of the winding, which may lead to a larger step difference. Therefore, the coating material 201 is preferably applied in a manner close to the second end face 17B of the fixing component 17, and the coating material 202 is preferably applied in a manner close to the first end face 17A of the fixing component 17. "Close" in this specification refers to a position that is significantly separated from the beginning of the winding or the fixing component. For example, even if the coating material is a low-viscosity material, the separation distance from the beginning of the winding or the fixing component is preferably 0.3 mm or more. The separation distance is preferably 0.5 mm or more, and from the most stable point of view, it is preferably 1 mm or more. It should be noted that if the separation distance is too large, it is difficult to obtain the effect of alleviating the step difference, so it is preferred to form a separation distance that is close to the first end face 17A of the fixing component 17. Figure 3 The distance is adjusted within the range of the first filling part 14. For example, the upper limit of the separation distance is preferably less than 10 mm, less than 7 mm, and more preferably less than 5 mm. In addition, if the separation distance exceeds 10 mm, in addition to the possibility that the first gap is not filled, although it also depends on the diameter of the core, the coating material may flow off before the sheet is wound. It should be noted that when the viscosity of the coating material is low, the coating amount can be increased. The separation distance is calculated as follows: measure 10 places, and calculate the arithmetic mean of the 8 separation distances other than the maximum and minimum values ​​of the 10 measured separation distances.

[0284] When the viscosity of the coating material is high, the coating material is difficult to spread, and therefore, it is preferred that the above separation distance is shorter. When the viscosity of the coating material is low, if the above separation distance is too small, there is a concern that a large amount of the coating material will exist on the fixed component. In addition, if the above separation distance is too large, there is a concern that the target gap cannot be fully filled due to expansion in other directions. Therefore, it is preferred that the above separation distance is neither too small nor too large.

[0285] In the above, after the fixing member 17 is arranged on the outer peripheral surface 11A of the winding core 11, the coating materials 201 and 202 are applied to both sides of the fixing member 17 at the same time. However, the coating materials 201 and 202 may be applied and the fixing member 17 may be arranged in the order of the following manufacturing methods (1) to (3). Among them, the following manufacturing method (2) is preferred. The same applies to the coating materials 204 and 205 described later.

[0286] Manufacturing method (1) is a method in which, after configuring a fixing component 17 on the outer peripheral surface 11A of the winding core 11, a coating material 201 is applied to the second end surface 17B side of the fixing component 17 in a manner to achieve the above-mentioned separation distance, and then, a coating material 202 is applied to the first end surface 17A side of the fixing component 17 in a manner to achieve the above-mentioned separation distance.

[0287] The manufacturing method (2) is a method in which, after applying the coating material 201 to the outer peripheral surface 11A of the winding core 11, the fixing member 17 is arranged so that the distance from the coating material 201 becomes the above-mentioned separation distance, and then the coating material 202 is applied to the fixing member 17 on the side opposite to the coating material 201 so that the distance from the fixing member 17 becomes the above-mentioned separation distance. By applying the coating materials 201 and 202 and arranging the fixing member 17 in this order, the fixing member 17 can be arranged stably with the separation distance, and the coating of excess coating material 201 and 202 on the fixing member 17 can be suppressed, so that the generation of a new step difference on the fixing member 17 can be suppressed.

[0288] The manufacturing method (3) is a method in which the coating materials 201 and 202 are applied to the outer peripheral surface 11A of the core 11 at a predetermined interval, and then the fixing member 17 is disposed between the coating materials 201 and 202 .

[0289] In addition, when the first filling portion 14 is formed but the second filling portion 16 is not formed, it is preferred that the coating material 201 is applied first, and then the fixing component 17 is arranged in such a manner that the distance from the coating material 201 becomes the above-mentioned separation distance. In addition, when the second filling portion 16 is formed but the first filling portion 14 is not formed, it is preferred that the coating material 202 is applied first, and then the fixing component 17 is arranged in such a manner that the distance from the coating material 202 becomes the above-mentioned separation distance.

[0290] The coating materials 201 and 202 are preferably applied to a width greater than the effective area in the width direction DR1 of the core 11. By applying the coating materials 201 and 202 in this way, the coating materials 201 to 205 can be present in the first filling part and the second filling part over the entire width of the effective area, thereby alleviating the step difference caused by the winding start end of the sheet 12 and the step difference caused by the fixing member 17 over the entire width of the effective area. From the viewpoint of suppressing the overflow of the coating materials 201 and 202 when the sheet 12 is wound, the coating materials 201 and 202 are preferably applied in a manner that they are separated from the two ends of the short side direction of the sheet 12 inwardly by 1 mm or more, 10 mm or more, or 30 mm or more, respectively.

[0291] The coating material 201 is preferably applied so that the width of the coating material 201 is 5 mm or more, 10 mm or more, or 30 mm or more. By applying the coating material 201 in this way, the step difference caused by the winding start end 12A of the sheet 12 can be more effectively alleviated. From the viewpoint of suppressing the overlap of the coating material, the upper limit of the width of the coating material 201 is preferably smaller than the outer circumference of the core 11.

[0292] The coating material 202 is preferably applied so that the width of the coating material 202 is 0.5 mm or more, 1 mm or more, or 5 mm or more. By applying the coating material 202 in this way, the step difference caused by the fixing member 17 can be more effectively alleviated. From the viewpoint of suppressing the overlap of the coating material, the upper limit of the width of the coating material 202 is preferably smaller than the outer circumference of the core 11.

[0293] The coating material 201 is preferably applied in such a manner that the thickness of the coating material 201 becomes greater than the height of the upper surface 12A2 of the winding start end 12A. By applying the coating material 201 in this way, a sufficient amount of the coating material 201 can be applied, so that the step difference caused by the winding start end 12A of the sheet 12 can be more effectively alleviated. Regarding the specific thickness of the coating material 201, for example, when the thickness of the sheet 12 is greater than 50 μm and less than 200 μm, it is preferably greater than 52 μm and less than 2000 μm. In addition, when the thickness of the sheet 12 is greater than 3 μm and less than 50 μm, it is preferably greater than 50.5 μm and less than 2000 μm. In addition, the thickness of the above-mentioned coating material 201 is the thickness before the sheet 12 is wound.

[0294] The coating material 202 is preferably applied in such a manner that the thickness of the coating material 202 becomes greater than the height of the front surface of the fixing member 17. By applying the coating material 202 in this way, a sufficient amount of the coating material 202 can be applied, so the step difference caused by the fixing member 17 can be more effectively alleviated. Regarding the specific lower limit of the thickness of the coating material 202, when the thickness of the fixing member 17 is greater than 3 μm and less than 10 μm, it is preferably greater than 3 μm and less than 12 μm. In addition, the thickness of the coating material 202 is the thickness before the sheet 12 is wound.

[0295] After applying the coating materials 201, 202, as Fig.18 As shown in (A), the winding start end 12A of the sheet 12 is arranged in such a manner that the end face 12A1 of the winding start end 12A contacts the coating material 201 and the sheet 12 covers the coating material 202. Specifically, the winding start end 12A of the sheet 12 is adhered to the fixing member 17, and the winding start end 12A is fixed to the outer peripheral surface 11A of the winding core 11 via the fixing member 17.

[0296] After the winding start end 12A of the sheet 12 is fixed to the winding core 11, as shown in FIG. Fig.18 As shown in (B), the sheet 12 is wound along the outer peripheral surface 11A of the winding core 11. When the sheet 12 is wound, the coating materials 201 and 202 flow and expand, so that the coating material 201 is filled in the first gap 13 and the coating material 202 is filled in the second gap 15, forming the first filling part 14 filled in the first gap 13 and the second filling part 16 filled in the second gap 15. Thus, the roll body 10 is obtained. It should be noted that in order to reliably expand and fill the coating material 201, etc. in the first gap 13, etc., it is preferred that when the sheet 12 exceeds 1000m, the sheet 12 is wound for more than 1000m, and when the sheet 12 is less than 1000m, the entire length of the sheet 12 is wound.

[0297] In addition, when the coating materials 201 and 202 are curable polymer compositions, after winding at least the second week of the sheet 12, the curable polymer composition is cured. In the case where the curable polymer composition is a one-component curable polymer composition (moisture curable polymer composition), the composition is cured by reacting with the humidity in the air and being placed at room temperature, so it can be cured without using special devices such as a heating device and an ionizing radiation irradiation device. In addition, when the curable polymer composition is a two-component curable polymer composition, it can be cured by mixing a main agent and a curing agent.

[0298] The roll body 20 can be manufactured, for example, by the following method. First, the fixing member 17 is disposed on the outer peripheral surface 11A of the core 11 along the width direction DR1 of the core 11 .

[0299] After the fixing member 17 is arranged, a coating device such as a dispenser or a syringe is used, such as Fig.19 As shown in (A), coating materials 203 to 205 are applied to the outer peripheral surface 11A of the core 11 along the width direction DR1 of the core 11. The coating material 204 is applied in a manner in contact with the first end face 17A of the fixing member 17, and the coating material 205 is applied in a manner in contact with the second end face 17B of the fixing member 17. The coating material 203 is applied to a portion separated from the second end face 17B of the fixing member 17 and the coating material 205. In addition, the coating material 203 may be applied in a manner close to the end face 12A1 of the winding start end 12A of the sheet 12, the coating material 204 may be applied in a manner close to the first end face 17A of the fixing member 17, and the coating material 205 may be applied in a manner close to the second end face 17B of the fixing member 17. In addition, after the fixing component 17 is arranged on the outer peripheral surface 11A of the winding core 11, the coating material 203~205 is applied, but after applying the coating material 203~205, the fixing component 17 can be arranged in a manner such that the coating material 204 contacts or is close to the first end face 17A of the fixing component 17, and the coating material 205 contacts or is close to the second end face 17B of the fixing component 17.

[0300] After applying the coating materials 203 to 205, Fig.19 As shown in (B), the winding start end 12A of the sheet 12 is arranged in such a manner that the end face 12A1 of the winding start end 12A contacts the coating material 203 and the sheet 12 covers the coating materials 204 and 205, respectively. Specifically, the winding start end 12A of the sheet 12 is adhered to the fixing member 17, and the winding start end 12A is fixed to the outer peripheral surface 11A of the winding core 11 via the fixing member 17.

[0301] After the winding start end 12A of the sheet 12 is fixed to the winding core 11, as shown in FIG. Fig.19As shown in (C), the sheet 12 is wound along the outer peripheral surface 11A of the winding core 11. When the sheet 12 is wound, the coating materials 203 to 205 flow and expand, so that the coating material 203 is filled in the first gap 13, the coating material 204 is filled in the second gap 15, and the coating material 205 is filled in the third gap 21, thereby forming the first filling part 14 filled in the first gap 13, the second filling part 16 filled in the second gap 15, and the third filling part 22 filled in the third gap 21. Thus, the roll body 20 is obtained. It should be noted that in order to reliably expand and fill the coating material 203 and the like in the first gap 13 and the like, it is preferred that when the sheet 12 exceeds 1000m, the sheet 12 is wound for more than 1000m, and when the sheet 12 is less than 1000m, the entire length of the sheet 12 is wound.

[0302] In the above manufacturing method, the coating materials 201 to 205 are made to flow by winding the sheet 12, but the coating material 201 and the like may be made to flow before the sheet 12 is wound. However, if the coating material 201 and the like are made to flow before the sheet 12 is wound, the number of steps increases, so it is preferred to make the coating materials 201 to 205 flow by winding the sheet 12.

[0303] In the above manufacturing method, the coating materials 201 to 205 are applied using a coating device such as a dispenser or a syringe, but a mold having a slit may be used together with the coating device to apply the coating materials 201 to 205. By applying the coating materials 201 to 205 using a mold having a slit, local variations in thickness, width, etc. of the coating materials 201 to 205 can be reduced. The constituent material of the mold is not particularly limited, and examples thereof include resins and metals.

[0304] Specifically, first, Fig. 20 As shown in (A), a mold 210 having a slit 210A is prepared. The mold 210 is used to apply the coating material 201. The length, width, and depth of the slit 210A are respectively the same as the length, width, and thickness of the coating material 201, and thus description thereof is omitted here.

[0305] After preparing the mold 210, as Fig. 20 As shown in (B), the mold is arranged on the outer peripheral surface 11A of the core 11 along the width direction DR1 of the core 11. The mold 210 is arranged so that the inner surface of the fixing member 17 side in the width direction of the gap overlaps or is close to the second end surface 17B of the fixing member 17 when the mold 210 is viewed from directly above.

[0306] After the mold 210 is placed on the outer peripheral surface 11A of the core 11, a coating device such as a dispenser or a syringe is used. Fig. 20The coating material 201 is supplied into the gap 210A as shown in (B). The coating device may be a dispenser or a syringe, or may be a sprayer or a die coater. Then, as needed, the excess coating material 201 existing on the surface of the mold 210 is scraped off using a scraper or the like. Then, the mold 210 is removed, so that the coating material 201 can be arranged on the outer peripheral surface 11A of the core 11. The subsequent steps are the same as the above-mentioned steps of the rolls 10 and 20. The coating materials 202 to 205 can also be arranged in the same order using the mold 210 having the gap 210A.

[0307] Instead of applying the coating materials 201 to 205, a filling tape may be arranged on the outer peripheral surface 11A of the winding core 11. Specifically, first, as Fig.21 As shown in (A), a coating material 201 is applied in a strip shape to the front surface of a substrate 221 using a coating device such as a dispenser or a syringe, thereby forming a laminate 220 having a substrate 221 and a filling strip 222 composed of the coating material 201. In addition, here, the filling strip 222 is formed by the coating material 201, but the coating material 201 may not be used as long as the filling strip is formed by a material that is expanded by pressure when the sheet is wound.

[0308] The constituent material of the substrate 221 is not particularly limited, and examples thereof include polyester resins such as polyethylene terephthalate, cellulose resins such as triacetyl cellulose, acrylic resins, and the like. In addition, a known release film may also be used as the substrate 221. When the coating material 201 is applied to the front of the substrate 221, it is preferred that an alignment line 221A is drawn in advance on the substrate 221, and the coating material 201 is applied along the alignment line 221A. By drawing such an alignment line 221A in advance on the substrate 221, positional deviation of the coating material 201 can be suppressed. In addition, when the coating material 201 is applied to the front of the substrate 221, it is preferred that the substrate 221 be unrolled at a constant speed using a roll-out device while the coating device is fixed. By unrolling the substrate 221 at a constant speed, uneven coating can be suppressed.

[0309] After forming the stacked body 220, as Fig.21 As shown in (B), the stacked body 220 is adhered or closely attached to the outer peripheral surface 11A of the core 11 in such a manner that the filling tape 222 contacts the outer peripheral surface 11A of the core 11. The filling tape 222 is adhered or closely attached in such a manner that it contacts or is close to the second end surface 17B of the fixing member 17. Then, the base material 221 is peeled off. In this way, the filling tape 222 can be arranged on the outer peripheral surface 11A of the core 11. The subsequent steps are the same as the above-mentioned steps of the rolls 10 and 20.

[0310] In the above, a laminate having one substrate and a filling tape is formed, but a laminate having two substrates, a filling tape and a thickness adjustment member may be formed. Fig. 22 As shown in (A), the coating material 201 is applied to the front surface of the first substrate 231 using a coating device such as a dispenser or a syringe.

[0311] Then, if Fig. 22 As shown in (B), a second substrate 233 is overlapped from above the coating material 201 in a manner that sandwiches the coating material 201 and a thickness adjusting member 232 having a desired thickness in order to make the coating material 201 the desired thickness, thereby forming a laminate 230. As the thickness adjusting member 232, for example, spacers, particles, etc. can be cited. The peel strength of the second substrate 233 relative to the coating material 201 is preferably smaller than the peel strength of the first substrate 231 relative to the coating material 201. By satisfying such a relationship, the second substrate 233 can be easily peeled off. The peel strength of the second substrate 233 is a value measured using a tensile tester (product name "single column material testing machine STA-1150", manufactured by A&D Co., Ltd.) and the following measurement method. When measuring the peel strength, first, a double-sided tape (No. 751B, manufactured by Teraoka Seisakusho Co., Ltd.) is attached to a glass plate of 30 cm in length and 2.5 cm in width. On the other hand, the laminate 230 is cut into a size of 200 mm in length and 25 mm in width, and the first substrate 231 side is pasted with double-sided tape on the glass plate, so that it is held in a pair of clamps of the tensile tester. Then, the laminate 230 pasted on the glass plate is held in a pair of clamps of the tensile tester. When the laminate 230 is held in the clamp, the second substrate 233 is slightly peeled off from the laminate 230 by hand in advance, and the beginning is made, so that one clamp holds the second substrate 233 and the other clamp holds the glass plate and the laminate 230. Then, in this state, the second substrate 233 is peeled off under the conditions of a peeling speed of 300 mm / min, a peeling distance of 50 mm, and a peeling angle of 180°, and the peeling strength of the coating material 201 and the second substrate 233 at this time is measured. It should be noted that the peeling strength is the arithmetic mean of the values ​​measured 3 times. The peeling strength of the first substrate 231 is also measured in the same way as the peeling strength of the second substrate 233. As the first substrate 231 and the second substrate 233 , the same substrate as the substrate 221 can be used.

[0312] After forming the laminate 230, a predetermined pressure is applied to the laminate 230. Thus, the thickness of the coating material 201 becomes a desired thickness. Then, the laminate 230 is cut into strips. Thus, the laminate 230 having the filling strip 234 composed of the coating material 201 is formed.

[0313] Afterwards, if Fig. 22 As shown in (C), the second substrate 233 is peeled off. Then, in this state, Fig. 22As shown in (D), the stacked body 230 is adhered or closely attached to the outer peripheral surface 11A of the core 11 in such a manner that the filling tape 234 contacts the outer peripheral surface 11A of the core 11. The filling tape 234 is adhered or closely attached in such a manner that it is in contact with or close to the second end surface 17B of the fixing member 17. Then, the first substrate 231 is peeled off. In this way, the filling tape 234 can be arranged on the outer peripheral surface 11A of the core 11. The subsequent steps are the same as the above-mentioned steps of the rolls 10 and 20. The filling tape can be arranged on the outer peripheral surface 11A of the core 11 in the same order as the filling tape 234 instead of the coating materials 202 to 205.

[0314] Alternatively, the filling tape may be transferred while forming the filling tape using a mold. By transferring the filling tape using a mold, the filling tape can be easily set simultaneously with the fixing member 17. Specifically, first, as Fig.23 As shown in (A), prepare a mold 241. The mold 241 has an opening 241A. Regarding the mold 241, it is preferred that the side surface of the mold 241 in the long side direction is open in a manner that a filling tape described later can be easily removed from the mold 241. The mold 241 is, for example, U-shaped. The mold 241 is not particularly limited, and for example, it can be formed of resin, metal, etc. The length, width, and depth of the opening 241A of the mold 241 are the same as the length, width, and thickness of the filling tape, so the description is omitted here.

[0315] After the mold 241 is prepared, Fig.23 As shown in (B), the coating material 201 is flowed into the mold 241 to form a filling zone 242. Then, as shown in Fig.23 As shown in (C), the mold 241 is pressed so that the filling tape 242 is in contact with the outer peripheral surface 11A of the core 11. When pressing the mold 241, if the coating material 201 is a material that shows stickiness due to moisture, it is preferred to wet the surface of the filling tape 242 with water in advance to make it sticky. By making the surface of the filling tape 242 sticky, it can be attached or closely attached to the outer peripheral surface 11A of the core 11.

[0316] Then, the mold 241 is removed from the filling tape 242. Thus, the filling tape 242 can be arranged on the outer peripheral surface 11A of the core 11. The subsequent steps are the same as the above steps of the rolls 10 and 20. The filling tape can be arranged on the outer peripheral surface 11A of the core 11 in the same order as the filling tape 242 instead of the coating materials 202 to 205.

[0317] Alternatively, the filling tape may be transferred to the outer peripheral surface 11A of the winding core 11 by using offset printing. By forming the filling tape by using offset printing and transferring it, time management becomes easy, and the filling tape can be set at a set time position with good accuracy. Specifically, first, as Fig.24As shown in (A), the coating material 201 is applied to the outer peripheral surface of the intermediate transfer body 251 (for example, the intermediate transfer roller) by a coating device such as a dispenser or a syringe to form a filling belt 252. Then, as shown in FIG. Fig.24 As shown in (B), the filling tape 252 formed on the outer peripheral surface of the intermediate transfer body 251 is transferred to the outer peripheral surface 11A of the core 11 by offset printing. In this way, the filling tape 252 can be arranged on the outer peripheral surface 11A of the core 11. The subsequent steps are the same as the above steps of the rolls 10 and 20. The filling tape can be arranged on the outer peripheral surface 11A of the core 11 in the same order as the filling tape 252 instead of the coating materials 202 to 205.

[0318] According to this embodiment, since the first gap 13 is filled with the first filling portion 14, the first circumference of the sheet 12 on the first filling portion 14 can be smoothly lifted from the separation position P1 toward the end face 12A1. Thus, the step difference caused by the winding start end 12A of the sheet 12 can be alleviated.

[0319] According to this embodiment, since the second gap 15 is filled with the second filling portion 16, the first circumference of the sheet 12 on the second filling portion 16 can be gently lowered from the first end surface 17A toward the reaching position P2. Thus, the step difference caused by the fixing member 17 can be effectively alleviated.

[0320] In the roll body 20, since the third gap 21 is filled with the third filling portion 22, the portion of the first turn of the sheet 12 on the third filling portion 22 can be gently lifted. Thus, the step caused by the fixing member 17 can be more effectively alleviated.

[0321] If the sheet material is deformed, there is a portion of the sheet material that cannot be used as a product, so in order to ensure the effective length, the effective length of the sheet material is compensated. That is, if the portion of the sheet material that does not become a product becomes longer due to deformation, the sheet material loss increases. In contrast, according to this embodiment, since the step difference caused by the winding start end 12A of the sheet material 12 and the step difference caused by the fixing components 17 and 51 can be alleviated, the deformation of the sheet material 12 can be suppressed. As a result, the sheet material loss can be reduced.

[0322] Hereinafter, a roll body according to a second embodiment of the present invention will be described with reference to the drawings. Fig.25 is a three-dimensional diagram of the roll body of this embodiment, Fig.26 Yes Fig.25 An enlarged view of a portion of the scroll. Fig. 27 It is used to illustrate Fig.25 A diagram showing the dimensions of each component of the scroll body, Fig.28 It is measured Fig.25The maximum thickness and length of the second intervening portion are shown in the figure. Fig.29 It is a diagram showing the cross-sectional area S3. Figures 30 to 37 This is an enlarged view of a portion of another roll according to the present embodiment. Fig.38 as well as Fig.39 It is a figure which shows typically the manufacturing process of the roll body which concerns on this embodiment.

[0323] <<<Roll>>>

[0324] Fig.25 The roll body 70 shown in the figure includes a core 11 and a long strip of sheet material 12 wound around an outer peripheral surface 11A of the core 11. Fig.25 As shown, the roll body 70 further includes: a first sandwiching portion 71 and a second sandwiching portion 72 provided between the sheets 12 after the first turn; and a fixing member 17 for fixing a portion of the sheet 12 to the winding core 11. The sheet 12 is wound around the winding core 11 for multiple turns, for example, more than 2 turns. With respect to the roll body 70, since the first gap 13 and the second gap 15 are hollow, the first filling portion 14 is not filled in the first gap 13, and the second filling portion 16 is not filled in the second gap 15.

[0325] <<1st interposition part>>

[0326] The first clamping portion 71 is disposed between the sheets 12 after the first week. Specifically, the first clamping portion 71 is clamped by the lower sheet 12 located below the first clamping portion 71 (on the winding core 11 side) and in contact with the first clamping portion 71, and the upper sheet 12 located above the first clamping portion 71 and in contact with the first clamping portion 71. Therefore, there must be a sheet 12 on the first clamping portion 71. In addition, the first clamping portion 71 is disposed between the sheets 12 after the first week, and specifically, the first clamping portion 71 is disposed at least in the first region 12D corresponding to the first gap 13 between the sheets 12 after the first week. In addition, the first clamping portion 71 extends along the width direction DR1 of the winding core 11.

[0327] Regarding the separation position P3 (see FIG. 1 ) at which the upper sheet 12 of the first interposing portion 71 is separated from the lower sheet 12 Fig.26 ) side edge thickness T4 of end portion 71A (refer to Fig. 27 ), if the thickness is thick, a new step difference may be formed due to the thickness, so the thickness is preferably thinner. Specifically, for example, the edge thickness T4 is preferably 50 μm or less. From the viewpoint of being able to shorten the deformation relaxation length, the edge thickness T4 is more preferably 10 μm or less, and further preferably 2 μm or less.

[0328] In addition, when the sheet 12 is a film having a thickness of more than 3 μm and less than 50 μm, it is more susceptible to the step difference caused by the winding start end 12A than in the case of a thicker thickness. Therefore, when using such a film, the edge thickness T4 is preferably less than 10 μm. In addition, from the viewpoint of minimizing the above-mentioned deformation relaxation length, it is more preferably less than 5 μm, and further preferably less than 1 μm.

[0329] Regarding the measurement of edge thickness T4, a scanning optical interference surface shape measuring instrument (product name "New View7300", manufactured by Zygo Corporation) can be used to measure it in the same way as edge thickness T1. In addition, it can also be measured as follows. First, cut out a portion including end 71A, the lower sheet 12 connected to the end 71A, and the upper sheet 12, and obtain a cross section of the portion by cutting or grinding with a tool, and measure it by observation based on a solid microscope (for example, the product name is "digital microscope VHX-7000", manufactured by KEYENCE Co., Ltd.).

[0330] like Fig.26 and Fig. 27 As shown, the first clamping portion 71 includes: a first portion 71B, which is clamped in the first area 12D corresponding to the first gap 13; and a second portion 71C, which is located at the arrival position P4 (refer to Fig.26 The first clamping portion 71 includes not only the first portion 71B but also the second portion 71C, thereby suppressing the stress concentration on the step difference portion caused by the winding start end portion 12A, thereby making it possible to make the deformation of the sheet 12 after the upper sheet 12 become gentle, thereby alleviating the step difference.

[0331] The thickness T5 of the second portion 71C (see Fig. 27 ) is preferably 2 μm or more and 300 μm or less. If the thickness T5 of the second portion 71C is within this range, the adverse effect on the winding of the sheet 12 can be avoided, and the deformation relaxation length can be shortened. In addition, when the thickness T3 of the second portion 71C exceeds 300 μm, the deformation relaxation length can be shortened, but sometimes the winding of the sheet 12 is adversely affected.

[0332] The thickness T5 of the second part 71C is the maximum thickness of the second part 71C. The thickness T5 of the second part 71C can be measured using a scanning optical interference surface shape measuring instrument (product name "New View7300", manufactured by Zygo Corporation) and by the same method as the edge thickness T1. Alternatively, the measurement can be performed as follows. First, the portion including the lower sheet 12, the second part 71C and the upper sheet 12 is selected and fixed in a manner that the portion is not crushed. Then, the cross section of the fixed portion is ground, and the thickness T5 of the second part 71C is measured using a solid microscope (for example, the product name is "digital microscope VHX-7000", manufactured by KEYENCE Co., Ltd.).

[0333] If the thickness of the first clamping portion changes suddenly, deformation will remain due to the change in thickness, and the step difference caused by the winding start end may not be fully alleviated. Therefore, it is preferable to ensure a sufficient length of the first clamping portion relative to the thickness of the sheet. However, in the case where winding and other effects are generated by lengthening the length of the first clamping portion, the length of the first clamping portion is intentionally made shorter than the optimal state. As a result, the above-mentioned deformation relaxation length becomes longer compared to the state with the optimal length of the first clamping portion, but the above-mentioned deformation relaxation length can be shortened compared to the state where the first clamping portion is not provided. Therefore, it is preferable that the length L3 of the first clamping portion 71 from the position corresponding to the end face 12A1 to the end on the separation position P3 side is equal to the distance D2 (refer to Fig. 27 ) ratio (length L3 / distance D2) is greater than 1. From the viewpoint of shortening the deformation relaxation length, the ratio is preferably greater than 5, more preferably greater than 50.

[0334] The length L3 can be measured as follows. First, keep the lower sheet 12 and the upper sheet 12, and roll out the other sheets 12. Here, if the sheet 12 is transparent or translucent, the area where the first clamping portion 71 exists can be visually confirmed. Therefore, the sheet 12 is observed through transmission, and the distance from the end surface 12A1 of the winding start end 12A to the end of the separation position P3 side of the first clamping portion 71 is measured at 10 points in the width direction of the sheet 12 using a ruler or a tape measure, and the average value is calculated to obtain the length L3. On the other hand, in the case where the sheet 12 cannot be observed through transmission, first, the portion including the lower sheet 12, the first clamping portion 71 and the upper sheet 12 is selected in a manner that the portion is not crushed. Then, after the portion is fixed, it is polished to form a cross section, and the distance from the position corresponding to the end face 12A1 of the first clamping portion to the end on the separation position side is measured using a solid microscope (for example, product name "digital microscope VHX-7000", manufactured by KEYENCE Co., Ltd.).

[0335] The longer the length L3 is, the better. For example, when the thickness of the sheet 12 is 50 μm to 200 μm, the length L3 is preferably 110 μm or more. To further shorten the deformation relaxation length, the length L3 is preferably 1 mm or more, and more preferably 10 mm or more.

[0336] The material constituting the first intervening portion 71 has the same physical properties such as tensile strength as those constituting the first filling portion 14 . Also, the material constituting the first intervening portion 71 is the same as that of the first filling portion 14 , and thus description thereof is omitted here.

[0337] <<Second interposition part>>

[0338] The second sandwiching portion 72 is provided between the sheets 12 after the first turn. Therefore, the sheet 12 is always present on the second sandwiching portion 72. In addition, the second sandwiching portion 72 is provided between the sheets 12 after the first turn. Specifically, the second sandwiching portion 72 is provided in the second region 12E corresponding to at least the second gap 15 between the sheets 12 after the first turn. In addition, the second sandwiching portion 72 extends along the width direction DR1 of the winding core 11.

[0339] The second interposing portion 72 is provided between the same sheets 12 as the first interposing portion 71 (for example, between the second and third sheets 12 ), but may be provided between sheets 12 different from the first interposing portion 71 .

[0340] The maximum thickness T6 of the second intervening portion 72 (see Fig. 27 , Fig.28) is preferably greater than 0.01 mm. If the maximum thickness T6 of the second clamping portion 72 is greater than 0.01 mm, the step difference caused by the fixing member 17 can be effectively alleviated. From the viewpoint of more effectively alleviating the above-mentioned step difference, the maximum thickness T6 is more preferably greater than 0.02 mm, greater than 0.03 mm or greater than 0.04 mm. On the other hand, if the maximum thickness T6 is too thick, although the step difference caused by the winding start end portion 12A can be alleviated, it sometimes has an adverse effect on the winding of the sheet 12. Therefore, the upper limit of the maximum thickness T6 is preferably less than 0.2 mm or less than 0.1 mm.

[0341] The maximum thickness T6 can be measured by the same method as the thickness T2 using a laser displacement meter or a stereo microscope. When the maximum thickness T6 is measured using a laser displacement meter, first, after the roll body 70 is mounted on a fixture and three laser displacement meters are arranged at specified positions, the sheet 12 is fed out until the second clamping portion 72 is exposed from the roll body 70. Then, while the second clamping portion 72 is exposed, the core 11 is rotated at a speed of 30 mm / s, while the displacement is continuously measured with a laser displacement meter at a sampling period of 200 μs, to obtain a graph with the horizontal axis being the position (mm) and the vertical axis being the displacement (mm). This measurement is performed from the second end 72B of the second clamping portion 72 on the opposite side of the first end 72A on the fixing part 17 side toward the first end 72A. In this measurement, the reference height (the line with a displacement of 0 mm) is set as the height of the core 11, and the difference between the reference height and the height of the second clamping portion 72 is set as the thickness of the second clamping portion 72. Then, the maximum thickness T6 of the second clamping portion 72 is calculated by calculating the difference in displacement between the line with a displacement of 0 mm and the position with the highest displacement. The obtained curve graph essentially represents a plane including the long side direction of the sheet and the radial direction of the core. In addition, in this curve graph, one scale mark on the horizontal axis is set to 5 mm, and one scale mark on the vertical axis is set to 0.02 mm. Fig. 27 In the embodiment, the first terminal 72A is located directly above the fixing member 17 .

[0342] The maximum thickness T6 can be measured using a stereo microscope as follows. First, a portion including the lower sheet 12, the second interposed portion 72, and the upper sheet 12 is selected and fixed in a manner that the portion is not crushed. Then, the cross section of the fixed portion is ground, and the maximum thickness T6 of the second interposed portion 72 is measured using a stereo microscope (e.g., product name "digital microscope VHX-7000", manufactured by KEYENCE Co., Ltd.).

[0343] When the thickness of the second intervening portion 72 is measured along the longitudinal direction DR2 of the sheet 12, a length L4 (see Fig. 27 ) and the maximum thickness T6 of the second intervening portion 72 (refer to Fig. 27 , Fig.28 ) (length L4 / maximum thickness T6) is preferably greater than 12. If the ratio is greater than 12, residual deformation near the second end 72B of the second clamping portion 72 can be suppressed. In addition, if the thickness of the second clamping portion is too thick, the windability may sometimes deteriorate due to separation from the perfect circle during winding, but if the ratio is greater than 12, the second clamping portion 72 will not be too thick, so the windability can be suppressed. In addition, if the thickness of the second clamping portion is too thick, new deformation caused by the second clamping portion may occur, but if the ratio is greater than 12, such new deformation can be suppressed. From the viewpoint of shortening the above-mentioned deformation relaxation length, the lower limit of the ratio is preferably greater than 25, greater than 50, greater than 75, greater than 100, greater than 125, greater than 150, greater than 175 or greater than 200. From the viewpoint of effectively alleviating the step difference caused by the fixing member, the maximum thickness T6 of the second intervening portion 72 is preferably thicker, and thus the upper limit of the ratio is preferably, for example, 2000 or less, 1000 or less, 500 or less, or 375 or less.

[0344] From the viewpoint of relieving the above-mentioned step difference, the longer the length L4 is, the better. For example, when the thickness of the sheet 12 is 50 μm or more and 200 μm or less, the length L4 is preferably 5.0 mm or more. In order to further shorten the above-mentioned deformation relief length, it is more preferably 7.0 mm or more, and further preferably 9.0 mm or more. However, if the length L4 is too long, from the processing point of view, the area R3 (refer to Fig.28 ), it is difficult to form a second clamping portion with a convex front side. In addition, wavy thickness unevenness may occur in the second clamping portion. Therefore, from the viewpoint that the front side 72C of the second clamping portion 72 in region R3 is easy to become convex and suppress the wavy thickness unevenness, the upper limit of the length L4 is preferably less than 20 mm.

[0345] The length L4 can be obtained from the graph of the position displacement curve in the same manner as the maximum thickness T6. Specifically, first, if the second end 72B of the second clamping portion 72 exists, the displacement increases. Therefore, the first position is found to be the intersection of the line with a displacement of 0 mm and the position displacement curve at the location where the displacement begins to increase. Next, an imaginary line is drawn that passes through the position where the displacement becomes the highest and is perpendicular to the line with a displacement of 0 mm. Then, the intersection of the imaginary line and the line with a displacement of 0 mm is taken as the second position, and the distance between the first position and the second position is obtained, thereby the length L4 can be obtained.

[0346] The length L4 / maximum thickness T6 can roughly represent the shape of the second sandwiching portion 72, but in order to more appropriately represent the convex shape of the front surface 72C, it is preferred to further use the cross-sectional area of ​​the second sandwiching portion 72. Specifically, it is preferred that the plane ( Fig.28 The cross-sectional area S3 of the second intervening portion 72 from the second end 72B to the position where the maximum thickness T6 is obtained in the plane shown in FIG. Fig.28 ) relative to the maximum thickness T6 of the second clamping portion 72 (cross-sectional area S3 / maximum thickness T6) is greater than 2.5. If the ratio is greater than 2.5, the cross-sectional area S3 of the second clamping portion 72 is larger relative to the maximum thickness T6, so the second clamping portion 72 can be used to effectively lift the sheet 12, thereby further alleviating the above-mentioned step difference. From the viewpoint of further alleviating the above-mentioned step difference, the lower limit of the cross-sectional area S3 / maximum thickness T6 is preferably greater than 3.0, greater than 3.5, greater than 4.0, greater than 5.0, greater than 5.5, greater than 6.0, greater than 6.5 or greater than 7.0. In addition, the upper limit of the cross-sectional area S3 / maximum thickness T6 is not particularly limited, for example, it can be less than 20.0, less than 17.5, less than 15.0, or less than 12.5, less than 10.0. The cross-sectional area S3 is the cross-sectional area of ​​the region R3 of the second clamping portion 72 (in Fig.29 , is the cross-sectional area of ​​the area surrounded by the solid line in the second clamping portion 72), which can be calculated as follows: calculate the product of the thickness at each measuring point in the area from the first position to the second position of the curve graph of the position displacement curve and the width between each measuring point, and sum them up.

[0347] The physical properties such as tensile strength of the material constituting the second intervening portion 72 are the same as those of the material constituting the second filling portion 16 . Also, the material constituting the second intervening portion 72 is the same as that of the second filling portion 16 , and thus description thereof is omitted here.

[0348] As described later, in the sheet 12 (the upper sheet 12) on the outside of the first clamping portion 71 and the second clamping portion 72 in the radial direction DR3, the step difference caused by the winding start end 12A of the sheet 12 and the step difference caused by the fixing member 17 can be suppressed, but in the sheet 12 (the lower sheet 12) on the inside of the first clamping portion 71 and the second clamping portion 72 in the radial direction DR3 (on the winding core 11 side), the step difference caused by the winding start end 12A of the sheet 12 and the step difference caused by the fixing member 17 cannot be suppressed. Therefore, it is preferable that the first clamping portion 71 and the second clamping portion 72 are provided as far as possible on the inside of the radial direction DR3 (for example, between the sheet 12 of the first cycle and the sheet 12 of the second cycle, or between the sheet 12 of the second cycle and the sheet 12 of the third cycle).

[0349] <<Other volumes>>

[0350] In the roll body 70, the end face 12A1 of the winding start end 12A of the sheet 12 and the second end face 17B of the fixing member 17 are roughly aligned in the cross section along the long side direction DR2 of the sheet 12 and the radial direction DR3 of the winding core 11, but it can also be as follows Fig.30 As shown in the roll body 80, the end face 12A1 of the winding start end 12A of the sheet 12 protrudes from the second end face 17B of the fixing member 17. In this case, not only the second sandwiching portion 72 is sandwiched in the second region 12E between the sheets 12, but also the third sandwiching portion 81 is sandwiched in the third region 12F between the sheets 12 corresponding to the third gap 21 on the second end face 17B side.

[0351] <Third Interposition Section>

[0352] The third intervening portion 81 is the same as the second intervening portion 72 except that it is interposed in the third region 12F corresponding to the third gap 21 , and thus description thereof is omitted here.

[0353] Regarding the roll body 70, the second sandwiching portion 72 is provided in the second region 12E between the sheets 12. However, from the viewpoint of alleviating the step difference caused by the winding start end 12A of the sheet 12, it is sufficient to provide the first sandwiching portion 71 in the first region 12D between the sheets 12. Fig.31 As in the roll body 90 shown in the figure, the second intervening portion 72 is not provided in the second region 12E between the sheets 12. Fig.31 In the illustrated roll 90 , the sheets 12 are in close contact with each other in the second region 12E.

[0354] Regarding the roll body 70, the first sandwiching portion 71 is provided in the first region 12D between the sheets 12, but from the viewpoint of alleviating the step difference caused by the fixing member 17, it is sufficient to provide the second sandwiching portion 72 in the second region 12E between the sheets 12, so it is also possible to Fig.32As in the roll body 100 shown in the figure, the first intervening portion 71 is not provided in the first region 12D between the sheets 12. Fig.32 In the illustrated roll 100 , the sheets 12 are in close contact with each other in the first region 12D.

[0355] The roll body 70 includes a first sandwiching portion 71, but may also be Fig.33 The first filling part 14 may be provided in place of the first intervening part 71 as in the roll body 110 shown in the figure. That is, the first gap 13 may be filled with the first filling part 14, and the second intervening part 72 may be provided in the second region 12E between the sheets 12.

[0356] The second sandwiching portion 72 of the roll body 110 is disposed between the second and third sheets 12, but may also be disposed between the second and third sheets 12. Fig.34 As in the roll body 120 shown in the figure, the second intervening portion 72 is provided between the sheet material 12 of the first turn and the sheet material 12 of the second turn.

[0357] The roll body 70 includes a second intervening portion 72, but may also be Fig.35 The second filling part 16 may be provided in place of the second intervening part 72 as in the roll body 130 shown in the figure. That is, the first intervening part 71 may be provided in the first region 12D between the sheets 12, and the second filling part 16 may be filled in the second gap 15.

[0358] The roll body 70 includes a fixing member 17 for fixing the sheet 12 to the outer peripheral surface 11A of the core 11, but may also be Fig.36 The roll body 140 shown does not include the fixing member 17 .

[0359] The thickness of the sheet 12 of the roll 70 is uniform, but it can also be as follows Fig.37As shown in the roll body 150, convex portions 12H protruding outward in the radial direction DR3 of the winding core 11 are formed at the two ends 12G extending along the long side direction of the sheet 12. When the viscosity of the filling material (e.g., coating material), the first intervening portion 71, the second intervening portion 72, or the third intervening portion 81 is low, or when the thickness of the sheet is uniform, there is a concern that the filling material (e.g., coating material, etc.) overflows from between the sheets, and the filling material exists in an undesirable position. In contrast, by forming the convex portions 12H at the two ends 12G of the sheet 12, it is possible to suppress the overflow of the filling material (e.g., coating material, etc.) at the two ends 12G after the filling material is arranged, for example, after the coating material is applied. In addition, the two ends 12G of the sheet 12 are parts that are cut off and not used as products, so even if such convex portions 12H are provided at the two ends 12G of the sheet, there is no problem for the product. The convex portion 12H may be formed by knurling or coating, or may be formed by attaching a tape (eg, a side tape). In the case of coating, the same material as that of the first filling portion 14 may be used.

[0360] exist Fig.37 In the roll body 150 shown, the convex portion 12H is provided on the entire part of the two end portions 12G of the sheet 12, but the convex portion 12H may be provided partially. For example, the convex portion 12H may be provided partially at the position of the two end portions 12G extending along the long side direction of the sheet 12 sandwiching the first sandwiching portion 71, the position of the two end portions 12G extending along the long side direction of the sheet 12 sandwiching the second sandwiching portion 72, and / or the position of the two end portions 12G extending along the long side direction of the sheet 12 sandwiching the third sandwiching portion 81. When the protrusion 12H is located at a position clamping the first clamping portion 71, overflow of the filling material (e.g., coating material) and the first clamping portion 71 can be suppressed. When the protrusion 12H is located at a position clamping the second clamping portion 72, overflow of the filling material (e.g., coating material) and the second clamping portion 72 can be suppressed. When the protrusion 12H is located at a position clamping the third clamping portion 81, overflow of the filling material (e.g., coating material) and the third clamping portion 81 can be suppressed.

[0361] exist Figure 31 to Figure 36 Although the distance D2, length L3, length L4, maximum thickness T6, and cross-sectional area S3 are not shown, when the first clamping portion 71 is present, the distance D2, length L3, and length L3 / distance D2 are the same as those of the roll 70. In addition, when the second clamping portion 72 is present, the length L4, length L4 / maximum thickness T6, and cross-sectional area S3 / maximum thickness T6 are the same as those of the roll 70.

[0362] In addition, Fig.33 , Fig.34 In the embodiment, the front surface of the fixing member 17 is in close contact with the winding start end 12A, but it can also be in close contact with Figure 8 Similarly, in the illustrated roll 10 , the first filling portion 14 enters between the winding start end portion 12A and the fixing member 17 .

[0363] <<Method for manufacturing roll>>

[0364] The roll 70 can be manufactured, for example, by the following method. Fig.38 As shown in FIG. 2 (A), the fixing member 17 is arranged on the outer peripheral surface 11A of the core 11 along the width direction DR1 of the core 11 .

[0365] After the fixing member 17 is configured, Fig.38 As shown in (B), the winding start end 12A of the sheet 12 is fixed to the outer peripheral surface 11A of the core 11 by the fixing member 17 in a manner such that the end face 12A1 of the winding start end 12A of the sheet 12 is roughly aligned with the second end face 17B of the fixing member 17.

[0366] After the winding start end 12A of the sheet 12 is fixed to the outer peripheral surface 11A of the winding core 11, as shown in FIG. Fig.38 As shown in (C), the sheet 12 is wound at least once along the outer peripheral surface 11A of the winding core 11. Thus, the intermediate roll 73 having the first gap 13 and the second gap 15 is obtained.

[0367] After obtaining the intermediate roll 73, Fig.39 As shown in (A), coating materials 206 and 207 are applied on the front surface 12I of the sheet 12 constituting the outer peripheral surface 73A of the intermediate roll body 73 along the width direction DR1 of the winding core 11. The coating material 206 is applied to at least the first area 12D corresponding to the first gap 13, and the coating material 207 is applied to at least the second area 12E corresponding to the second gap 15. The coating materials 74 and 75 are the same as the coating materials 201 and 202, and therefore their description is omitted here.

[0368] After applying the coating materials 206, 207, as Fig.39 As shown in (B), the sheet 12 is wound again on the winding core 11. As a result, the coating materials 206 and 207 flow and expand, so that the coating material 206 is provided in the first area 12D between the sheets 12, and the coating material 207 is provided in the second area 12E between the sheets 12, forming the first sandwiching portion 71 and the second sandwiching portion 72. Thus, the roll body 70 is obtained. In addition, when at least one of the coating materials 206 and 207 is a curable material, the curable material is cured after the sheet 12 is wound again.

[0369] In the method for manufacturing the roll body 70, the coating materials 206 and 207 are not applied using the mold 210 having the slits 210A, but the coating materials 206 and 207 may be applied using the mold 210 having the slits 210A as in the first embodiment. In addition, the first intervening portion 71 and the second intervening portion 72 may be formed using a filling sheet instead of the coating materials 206 and 207 by the same method as in the first embodiment.

[0370] According to this embodiment, since the first clamping portion 71 is provided in the first region 12D between the sheets 12, the portion of the sheet 12 on the first clamping portion 71 can be smoothly lifted toward the end face 12A1. Thus, the step difference caused by the winding start end 12A of the sheet 12 can be effectively alleviated.

[0371] According to the present embodiment, since the second intervening portion 72 is provided in the second region 12E between the sheets 12, the portion of the sheet 12 on the second intervening portion 72 can be gently lifted. Thus, the step caused by the fixing member 17 can be effectively alleviated.

[0372] In addition, since the step difference caused by the winding start end portion 12A of the sheet 12 and the step difference caused by the fixing member 17 can be alleviated, deformation of the sheet 12 can be suppressed.

[0373] If the first gap is filled with the first filling part and the second gap is filled with the second filling part, the first filling part and the second filling part may flow to the portion where no pressure is applied. In contrast, in the present embodiment, since the first interposing part 71 and the second interposing part 72 are provided between the sheets 12, the materials constituting the first interposing part 71 and the second interposing part 72 are difficult to flow and thus difficult to overflow.

[0374] Example

[0375] In order to explain the present invention in detail, the following examples are given for description, but the present invention is not limited to these descriptions. Fig.40 (A) is a graph showing the displacement of the roll body of Example 7 relative to the position of the first filling part. Fig.40 (B) is a graph showing the displacement of the roll body of Example 8 relative to the position around the first filling part. Fig.40 (C) is a graph showing the displacement amount of the roll body of Example 9 relative to the periphery of the first filling part.

[0376] <Preparation of Hard Coat Composition>

[0377] First, each component was mixed so as to have the composition shown below to obtain a composition 1 for hard coating layer.

[0378] (Hard Coat Composition 1)

[0379] Pentaerythritol triacrylate (product name "KAYARAD-PET-30", manufactured by Nippon Kayaku Co., Ltd.): 60 parts by mass

[0380] Photopolymerization initiator (1-hydroxycyclohexyl phenyl ketone, product name "Omnirad 184", manufactured by IGM Resins BV): 5 parts by mass

[0381] Silicone leveling agent (product name "Seika Beam 10-28", manufactured by Dainichi Seika Industries, Ltd., solid content 10%): 0.1 parts by mass

[0382] Silica particles (product name "SIRMIBK-H84", manufactured by CIK Nanotech Co., Ltd., average particle size 30 nm, solid content 30%): 3 parts by mass

[0383] Methyl isobutyl ketone (MIBK): 80 parts by mass

[0384] Cyclohexanone: 20 parts by mass

[0385] <Example 1>

[0386] First, a rectangular double-sided tape with a length of 1380 mm, a width of 20 mm and a thickness of 10 μm is pasted along the width direction of the core as a fixing part on the outer peripheral surface of a cylindrical core made of fiber-reinforced plastic with an inner diameter of 153 mm, an outer diameter of 167 mm and a width of 1600 mm.

[0387] After the double-sided tape is applied, the core is held by the clamping part of the winding device and fixed to the winding device. Then, two single-component curable silicone resin compositions (product name "Hapio SealPro HG", manufactured by Campe Hapio Co., Ltd.) are applied as coating materials at 25°C in a manner that they are in contact with the first end face and the second end face of the double-sided tape extending along the width direction of the core. The color of the silicone resin composition is gray. In addition, the shear viscosity of the silicone resin composition during application is 180 Pa·s, and the silicone resin composition is applied along the width direction of the core and in an amount of 1 cm per unit width. 3 / m are applied in a straight line.

[0388] Then, the long side winding start end of an acrylic resin film (in-plane phase difference Re: 5 nm) with a length of 3000 m, a width of 1340 mm, and a thickness of 80 μm was attached to a double-sided tape along the width direction of the core, thereby fixing the acrylic resin film to the outer peripheral surface of the core. It should be noted that the acrylic resin film is arranged so that the end surface of the long side winding start end of the acrylic resin film is in contact with the silicone resin composition and is roughly aligned with the second end surface of the double-sided tape in the radial direction of the core.

[0389] Then, the entire acrylic resin film is wound around the core using a winding device, and the silicone resin composition is filled in the first gap between the core and the acrylic resin film of the first week and in contact with the end face of the winding start end of the acrylic resin film, and the silicone resin composition is filled in the second gap between the core and the acrylic resin film of the first week and in contact with the first end face of the double-sided tape. Thus, a roll body is obtained. In the roll body, the silicone resin composition is cured to form a first filling portion with a length of 20 mm, a width of 1340 mm, and a maximum thickness of 300 μm filled in the first gap, and a second filling portion with a length of 20 mm, a width of 1340 mm, and a maximum thickness of 300 μm filled in the second gap.

[0390] The shear viscosity of the silicone resin composition is measured using a dynamic viscoelasticity measuring device manufactured by Anton-Paar Japan Co., Ltd. Specifically, the shear viscosity of the silicone resin composition is determined as follows: using a parallel plate having a diameter of 25 mm, the shear viscosity at a shear rate of 1 [1 / s] is measured at 25°C. The viscosity of the silicone resin composition is determined as follows: the viscosity of the silicone resin composition is measured 10 times, and the arithmetic mean of 8 shear viscosities excluding the maximum and minimum values ​​of the 10 measured viscosities is determined. The shear viscosity of the coating material used in the following other examples is also measured in the same manner as in Example 1.

[0391] The in-plane phase difference Re of the acrylic resin film was measured using a phase difference film-optical material inspection device (product name "RETS-100", manufactured by Otsuka Electronics Co., Ltd.). Specifically, first, in order to stabilize the light source of RETS-100, the light source was turned on and left for more than 60 minutes. Then, the rotating analyzer method was selected, and the θ mode (angular direction phase difference measurement mode) was selected. By selecting this θ mode, the workbench becomes a tilted rotating workbench.

[0392] Next, enter the following measurement conditions into RETS-100.

[0393] (Measurement conditions)

[0394] Delay measurement range: Rotating polarizer method

[0395] Measuring point diameter: φ5mm

[0396] Tilt angle range: -40°~40°

[0397] ·Measurement wavelength range: 400nm~800nm

[0398] Average refractive index of the sample: 1.5

[0399] Thickness: 80μm

[0400] Next, no sample is placed in the device to obtain background data. The device is set as a closed system, and the closed system is implemented every time the light source is turned on.

[0401] Then, a sample was placed on a workbench in the device. The size of the sample was 50 mm×50 mm.

[0402] After setting up the sample, rotate the workbench 360° on the XY plane in an environment with a temperature of 23°C and a relative humidity of 50%, and measure the fast axis and slow axis. After the measurement, select the slow axis. Then, while tilting the workbench to the angle range set with the slow axis as the center, measure and obtain the data (Re) of the set tilt angle range and the set wavelength range in units of 10°. The in-plane phase difference Re is measured at 5 points in different positions. Specifically, Figure 2 As shown, the measurement is performed at a total of five points, namely, the center A1 and points A2 to A4 of the sample. Then, the arithmetic mean of the three points excluding the maximum value and the minimum value among the five measured values ​​is taken as the in-plane phase difference Re.

[0403] <Example 2>

[0404] In Example 2, a roll body was obtained in the same manner as in Example 1, except that a two-component curable silicone rubber composition (product name "KE-24", manufactured by Shin-Etsu Chemical Co., Ltd.) was used instead of the silicone resin composition for forming the first filling part and the second filling part. The silicone rubber composition was white when mixed, and the shear viscosity of the silicone rubber composition when applied was 75 Pa·s.

[0405] <Example 3>

[0406] In Example 3, a roll body was obtained in the same manner as in Example 1 except that a two-component curable silicone rubber composition (product name "ELASTOSIL (registered trademark) M4503", manufactured by Asahi Kasei Wacker Silicone Co., Ltd., condensation curable) was used instead of the silicone resin composition for forming the first filling part and the second filling part. The silicone rubber composition was white when mixed, and the shear viscosity of the silicone rubber composition when applied was 40 Pa·s. Furthermore, the silicone rubber composition did not contain volatile components or adhesive components.

[0407] In a 90° peeling test in which the constituent material of the first filling portion in the roll of Example 3 was peeled perpendicularly to the outer peripheral surface of the core at a peeling rate of 10 mm / min, the constituent material was peeled at a tensile force of 0.2N.

[0408] The above-mentioned 90° peel test is carried out using a sample and a spring-type tensiometer (manufactured by Ohba Measuring Instruments Co., Ltd.). Specifically, first, a mold larger than the size of the sample is prepared, and the mold is arranged on the outer peripheral surface of the core. Then, a two-component curable silicone rubber composition (product name "ELASTOSIL (registered trademark) M4503", manufactured by Asahi Kasei Wacker Silicones Co., Ltd., condensation curable) is injected into the mold and cured to obtain a material layer. Then, the material layer is taken out of the mold, and the material layer is cut into a size of 20 mm × 100 mm using a cutting machine to obtain a sample set on the outer peripheral surface of the core. Then, one end of the sample is held by a spring-type tensiometer, and the tensile force is measured while the above-mentioned end is lifted vertically relative to the outer peripheral surface of the core in an environment of a temperature of 25°C and a relative humidity of 50%. The sample is peeled off at a peeling speed of 10 mm / second. Then, among the 10 samples subjected to the 90° peel test, the arithmetic average of the tensile forces of 8 samples other than the sample with the largest tensile force and the sample with the smallest tensile force was taken as the tensile force of the constituent material.

[0409] The tensile strength of the constituent material of the first filling portion in the roll of Example 3 was 3.5 MPa, the elongation when cut was 450%, and the tear strength was 12.0 N / mm. In addition, the hardness of the constituent material of the first filling portion measured by a type A durometer was 28°, and the linear shrinkage of the constituent material of the first filling portion was 0.10%.

[0410] The tensile strength of the constituent material of the first filling portion is measured in accordance with JIS K6251: 2017 using a sample and a Tensilon universal testing machine (product name "RTC-1310A", manufactured by A&D Co., Ltd.). Specifically, first, a mold larger than the size of the sample is prepared, and the mold is arranged on the outer peripheral surface of the core. Then, a two-component curable silicone rubber composition (product name "ELASTOSIL (registered trademark) M4503", manufactured by Asahi Kasei Wacker Silicones Co., Ltd., condensation curable) for forming the first filling portion is injected into the mold and cured to obtain a material layer. Then, the material layer is removed from the mold, and the material layer is punched out into the size of the dumbbell No. 2 shape described in JIS K6251: 2017 using a tensile No. 2 dumbbell-shaped punching knife manufactured by Polymer Measuring Instruments Co., Ltd. to obtain a sample. Then, the sample is kept at 25°C for 24 hours. Then, a pair of grippers of the Tensilon universal testing machine grip both ends of the sample in the long side direction, and a tensile test is performed under the conditions of a temperature of 25°C and a relative humidity of 50%, with an initial gripper distance of 20 mm and a tensile speed of 100 mm / min, to measure the tensile strength of the sample. Then, the arithmetic mean of the tensile strengths of 8 samples excluding the maximum value and the minimum value among the 10 samples is taken as the tensile strength of the above-mentioned constituent material.

[0411] The elongation at break of the constituent material of the first filling portion was measured in accordance with JIS K6251: 2017 using a sample and a Tensilon universal testing machine (product name "RTC-1310A", manufactured by A&D Co., Ltd.) in the same manner as the tensile strength measurement method. Then, the arithmetic mean of the elongation at break of 8 samples excluding the maximum and minimum values ​​among the 10 samples was taken as the elongation at break of the constituent material.

[0412] The tear strength of the constituent material of the first filling portion was measured in accordance with JIS K6252: 2007 using a sample and a Tensilon universal testing machine (product name "RTC-1310A", manufactured by A&D Co., Ltd.) in the same manner as the tensile strength measurement method. Then, the arithmetic mean of the tear strengths of 8 samples excluding the maximum and minimum values ​​among the 10 samples was taken as the tear strength of the constituent material.

[0413] The hardness measurement of the constituent material of the first filling part based on the A-type durometer is measured in accordance with JIS K6253:1997. Specifically, first, a mold larger than the size of the sample is prepared, and the mold is arranged on the outer peripheral surface of the core. Then, a two-component curable silicone rubber composition (product name "ELASTOSIL (registered trademark) M4503", manufactured by Asahi Kasei Wacker Silicone Co., Ltd., condensation curing) for forming the first filling part is injected into the mold, and it is cured as needed to obtain a material layer. Then, the material layer is taken out from the mold, and the material layer is cut out using a cutting machine to obtain a sample with a size of 100mm×100mm and a thickness of 10mm. Then, the hardness is measured using a type A durometer (product name "GS-719N (TYPEA)", manufactured by Teclock Co., Ltd.) at a temperature of 25°C and a relative humidity of 50%. Then, the arithmetic mean of the hardness of 8 samples other than the maximum and minimum values ​​among the 10 samples is taken as the hardness of the above-mentioned constituent material.

[0414] The linear shrinkage of the first filling part can be measured as follows. First, prepare a mold of 130 mm square with a thickness of 2 mm, inject a two-component curable silicone rubber composition (product name "ELASTOSIL (registered trademark) M4503", manufactured by Asahi Kasei Wacker Silicones Co., Ltd., condensation curing) used to form the first filling part into the mold and cure it to obtain a sample (molded product). After complete curing, measure the size of the sample and compare it with the size on the inside of the mold, and calculate the linear shrinkage based on JIS K6249:2003. The arithmetic mean of the linear shrinkage of 8 samples excluding the maximum and minimum values ​​among the 10 samples is taken as the linear shrinkage of the above-mentioned constituent material.

[0415] <Example 4>

[0416] In Example 4, a roll body was obtained in the same manner as in Example 1, except that a two-component curable silicone rubber composition (product name "ELASTOSIL (registered trademark) M4601", manufactured by Asahi Kasei Wacker Silicone Co., Ltd., addition-reactive) was used instead of the silicone resin composition for forming the first filling part and the second filling part. The silicone rubber resin composition was white when mixed, and the shear viscosity of the silicone rubber composition when applied was 20 Pa·s.

[0417] <Example 5>

[0418] In Example 5, a roll was obtained in the same manner as in Example 1, except that a two-component curable polyurethane resin composition (product name "Human Skin Gel", manufactured by Excsel Corporation) was used instead of the silicone resin composition for forming the first filling part and the second filling part. The polyurethane resin composition was white when mixed, and the shear viscosity of the polyurethane resin composition when applied was 6.5 Pa·s.

[0419] <Example 6>

[0420] First, a rectangular double-sided tape with a length of 1380 mm, a width of 20 mm and a thickness of 10 μm is pasted along the width direction of a cylindrical core made of fiber-reinforced plastic with an inner diameter of 153 mm, an outer diameter of 167 mm and a width of 1600 mm as a fixing component.

[0421] After the double-sided tape was attached, the winding core was held by the clamping member of the winding device and fixed to the winding device. Then, the winding start end of the long side direction of a polyethylene terephthalate film (PET film, in-plane phase difference Re: 1000nm, Nz coefficient: 20) with a length of 3000m, a width of 1490mm and a thickness of 80μm as a sheet was attached to the double-sided tape along the width direction of the winding core, thereby fixing the PET film to the outer peripheral surface of the winding core.

[0422] Then, the PET film is wound up by a winding device for one turn to obtain an intermediate roll. In the intermediate roll, a first gap is formed between the winding core and the PET film of the first turn and in contact with the end surface of the winding start end of the PET film, and a second gap is formed between the winding core and the PET film of the first turn and in contact with the first end surface of the double-sided tape.

[0423] After the intermediate roll is obtained, a one-component curable silicone resin composition (product name "HapioSeal Pro HG", manufactured by Campe Hapio Co., Ltd.) is applied as a coating material on the front side of the PET film constituting the outer peripheral surface of the intermediate roll along the width direction of the roll core at 25°C. The viscosity of the silicone resin composition during application is 180 Pa·s, and the silicone resin composition is applied in an amount of 1 cm2 / cm3 along the width direction of the roll core and per unit width. 3 Specifically, the silicone resin composition is applied to the first region corresponding to the first gap and the second region corresponding to the second gap.

[0424] After the silicone resin composition is applied, the PET films are all wound around the winding core again using a winding device so that the silicone resin composition is respectively interposed between the first region and the second region between the PET films. Thus, a roll body is obtained. In the roll body, the silicone resin composition is cured to form a first sandwiching portion having a length of 20 mm, a width of 1340 mm, and a maximum thickness of 300 μm in the first region between the PET films, and a second sandwiching portion having a length of 20 mm, a width of 1340 mm, and a maximum thickness of 300 μm in the second region between the PET films.

[0425] The in-plane phase difference Re of the PET film used in Example 6 was measured in the same manner as the in-plane phase difference Re of the acrylic resin film used in Example 1. However, in this case, the average refractive index N of the sample was set to 1.617.

[0426] <Example 7>

[0427] In Example 7, an acrylic resin film having a length of 3000 m, a width of 1340 mm, and a thickness of 85 μm was used as a sheet. Specifically, a laminate composed of an acrylic resin film and a hard coating layer was used. In addition, a silicone rubber composition for forming a first filling portion and a second filling portion was applied along the width direction of the core at a coating amount of 0.3 cm per unit width. 3 A roll was obtained in the same manner as in Example 3 except that the roll was applied in a linear shape so as to have a thickness of 100 mm / m.

[0428] The laminated body is formed as follows. First, a continuous coating machine is used to feed the acrylic resin film of 3000 m in length, 1340 mm in width and 80 μm in thickness used in Example 1 from a roll-out roller to the coating section of the first unit, and the hard coating composition 1 is applied to form a coating film. Then, the coating film is dried at a temperature of 70° C. for 60 seconds in a drying section to evaporate the solvent in the coating film, and then the coating film is dried at a temperature of 70° C. in a curing section to evaporate the solvent in the coating film to a cumulative light intensity of 150 mJ / cm 2 The coating was cured by irradiating with ultraviolet rays in a manner to form a hard coating layer with a film thickness of 5.0 μm and a coating width of 1300 mm, thereby obtaining a laminate with a continuous film length of 3000 m and a thickness of 85 μm.

[0429] <Example 8>

[0430] In Example 8, the silicone rubber composition for forming the first filling part and the second filling part was applied along the width direction of the core at a coating amount of 0.5 cm per unit width. 3 A roll was obtained in the same manner as in Example 7 except that the coating was applied linearly in the form of 1.5 % / m.

[0431] <Example 9>

[0432] In Example 9, the silicone rubber composition for forming the first filling part and the second filling part was applied along the width direction of the core at a coating amount of 0.8 cm per unit width. 3 A roll was obtained in the same manner as in Example 7 except that the coating was applied linearly in the form of 1.5 % / m.

[0433] <Example 10>

[0434] In Example 10, the silicone rubber composition for forming the first filling part and the second filling part was applied in an amount of 1 cm per unit width. 3 A roll was obtained in the same manner as in Example 9 except that the coating was applied linearly in the form of 1 / m.

[0435] <Example 11>

[0436] In Example 11, the shear viscosity of the two-component curable silicone rubber composition used to form the first filling portion and the second intervening portion during coating was set to 2 Pa·s, and the coating amount per unit width was set to 1.5 cm 3 / m, a roll was obtained in the same manner as in Example 9 except for the above.

[0437] <Example 12>

[0438] In Example 12, the shear viscosity of the silicone rubber composition used to form the first filling portion and the second interposing portion during coating was set to 6.5 Pa·s, and the coating amount per unit width was set to 1.2 cm 3 / m, a roll was obtained in the same manner as in Example 9 except for the above.

[0439] <Example 13>

[0440] First, a cylindrical core made of fiber-reinforced plastic with an inner diameter of 153 mm, an outer diameter of 167 mm, and a width of 1600 mm is held by the clamping part of the winding device, thereby fixing it to the winding device. Then, a two-component curable silicone rubber composition (product name "ELASTOSIL (registered trademark) M4503", manufactured by Asahi Kasei Wacker Silicones Co., Ltd., condensation curable) is applied as a coating material along the width direction of the core at 25°C. The viscosity of the silicone rubber composition during application is 180 Pa·s, and the silicone rubber composition is applied in an amount of 1 cm·s per unit width along the width direction of the core. 3 / m in a straight line.

[0441] Then, a rectangular double-sided tape with a length of 1380 mm, a width of 20 mm, and a thickness of 10 μm was attached to the core as a fixing member in the width direction so that the separation distance between the double-sided tape and the two-component curable silicone rubber composition was 3 mm. The separation distance was determined by measuring 10 locations and calculating the arithmetic mean of the separation distances of 8 locations excluding the maximum and minimum values ​​of the measured separation distances. In the following examples, the separation distance was also determined in this way.

[0442] Then, the winding start end of the laminated body having the same length of 3000 m, width of 1340 mm and thickness of 85 μm as in Example 7 was attached to the double-sided tape along the width direction of the core, thereby fixing the laminated body to the outer peripheral surface of the core. It should be noted that the laminated body was arranged so that the end surface of the winding start end of the laminated body in the long side direction was in contact with the silicone rubber composition and was roughly aligned with the second end surface of the double-sided tape in the radial direction of the core.

[0443] Then, the laminate is wound around a winding core by a winding device, and the silicone rubber composition is filled in a first gap between the winding core and the first turn of the laminate and in contact with the end surface of the winding start end of the laminate.

[0444] Then, the stacked body is wound up once by a winding device to obtain an intermediate roll. In the intermediate roll, a second gap is formed between the winding core and the stacked body of the first turn and in contact with the first end face of the double-sided tape.

[0445] After the intermediate roll is obtained, a two-component curable silicone rubber composition (product name "ELASTOSIL (registered trademark) M4503", manufactured by Asahi Kasei Wacker Silicone Co., Ltd., condensation curable) is applied as a coating material on the front side of the laminate constituting the outer peripheral surface of the intermediate roll along the width direction of the roll core at 25°C. The viscosity of the silicone rubber composition during application is 180 Pa·s, and the silicone rubber composition is applied in an amount of 1 cm per unit width along the width direction of the roll core. 3 Specifically, the silicone rubber composition is applied to the second region corresponding to the second gap.

[0446] After the silicone rubber composition is applied, the entire stack is wound around the winding core again using a winding device so that the silicone rubber composition is interposed between the second regions between the stacks. Thus, a roll is obtained. In the roll, the silicone rubber composition is solidified, and a first filling portion with a width of 1340 mm is formed in the first gap, and a second intervening portion with a width of 1340 mm is formed in the second region between the stacks.

[0447] <Example 14>

[0448] In Example 12, a roll body was obtained in the same manner as in Example 11, except that a two-component curable silicone rubber composition (product name "ELASTOSIL (registered trademark) M4601", manufactured by Asahi Kasei Wacker Silicone Co., Ltd., addition-reactive) was used instead of the two-component curable silicone rubber composition (product name "ELASTOSIL (registered trademark) M4503", manufactured by Asahi Kasei Wacker Silicone Co., Ltd., condensation-curable) used to form the first filling portion and the second interposing portion. The shear viscosity of the silicone rubber composition during application was 10 Pa·s.

[0449] <Example 15>

[0450] In Example 15, the shear viscosity of the two-component curable silicone rubber composition used to form the first filling portion and the second interposing portion during coating was set to 10 Pa·s, and the coating amount per unit width was set to 0.8 cm 3 / m, and except that the separation distance between the double-sided tape and the two-component curable silicone rubber composition was set to 3 mm, a roll was obtained in the same manner as in Example 13.

[0451] <Example 16>

[0452] In Example 16, the shear viscosity of the two-component curable silicone rubber composition used to form the first filling portion and the second intervening portion during coating was set to 10 Pa·s, and the coating amount per unit width was set to 1.2 cm 3 / m, and except that the separation distance between the double-sided tape and the two-component curable silicone rubber composition was set to 3 mm, a roll was obtained in the same manner as in Example 13.

[0453] <Comparative Example 1>

[0454] In Comparative Example 1, a roll was obtained in the same manner as in Example 1 except that the coating material was not applied.

[0455] <Comparative Example 2>

[0456] In Comparative Example 2, a roll was obtained in the same manner as in Comparative Example 1, except that the laminate used in Example 7 was used instead of the acrylic resin film.

[0457] In the rolls of Examples 1 to 16, the edge thickness T1 of the first filling part was measured. The edge thickness T1 was measured using a scanning optical interference surface shape measuring instrument (product name "New View7300", manufactured by Zygo Corporation). Specifically, first, when the film such as acrylic resin film, PET film, or the laminate is completely fed out, there is a case where the first filling part adheres to the side of the laminate and peels off from the roll core. Then, one or more samples of a size of 2 mm × 5 mm including the first filling part are cut out from the laminate. The sample is cut out from any part that includes the end of the first filling part and is not attached to dirt, fingerprints, etc. Then, under the following measurement conditions, the edge thickness T1 of the first filling part is measured. The edge thickness T1 is calculated by measuring the edge thickness at 10 locations and calculating the arithmetic mean of the thicknesses at 8 locations excluding the maximum and minimum values ​​of the 10 measured thicknesses.

[0458] (Measurement conditions)

[0459] Objective lens: 10 times

[0460] Zoom: 1x

[0461] Measuring area: 2.17mm×2.17mm

[0462] Scan Length: 5μm

[0463] Min mod: 0.015

[0464] Temperature: 23℃

[0465] Relative humidity: 50%

[0466] <Measurement of deformation relaxation length>

[0467] In the rolled bodies of the examples and comparative examples, the step difference caused by a film such as an acrylic resin film or a PET film, or the winding start end portion of the laminate, and the length in which the step difference caused by the double-sided tape is alleviated were measured. Specifically, since the step difference becomes smaller from the winding start end portion toward the winding end portion, first, until the location where the step difference is visually confirmed, the film or laminate was fed out while measuring the feed length (m) of the film or laminate. Then, the film or laminate was cut at the location where the step difference was observed. In a state where a polyvinyl alcohol film was adhered to the cut portion of the film or laminate, visual observation was performed using reflected light in an indoor environment of 800 Lux or more and 2000 Lux or less with a white LED light incident on the film or laminate. Then, the distance from the location where the step difference could not be seen to the winding start end portion was measured and taken as the deformation alleviation length. Here, a portion where the contour line of the white LED light incident on the film or laminate is deformed compared to other portions of the film or laminate was judged to have a step difference, and a portion where the contour line of the white LED light incident around the step difference could be judged to be the same as other portions of the film or laminate was judged to have no step difference. The white LED lights were arranged such that the long side direction of the white LED lights was along the long side direction of the film or laminate. The length of the white LED lights was the length covering the portion with a step difference and the portion without a step difference in the film or laminate. At the time of observation, the side where the line of the white LED light could be clearly seen was appropriately selected, and the white LED light was incident on the film or laminate to be in a state where its contour line could be seen. In addition, the visual observation was performed based on the normal direction (0°) of the surface of the film or laminate from all angles (~180°~180°).

[0468] <Confirmation of the presence of the fourth intervening portion>

[0469] In Examples 3 and 7 to 16, it was confirmed whether the fourth clamping portion was present at the winding start end portion. Specifically, first, the laminate was fed out from the rolled body until the laminate on the front side became the second turn. Then, in the rolled body where the laminate on the second turn was on the front side, the vicinity of the winding start end portion was visually observed to see if there was a colored portion on the winding start end portion. Moreover, when there was a colored portion on the winding start end portion, it was confirmed that the fourth clamping portion was present, and when there was no colored portion, it was confirmed that the fourth clamping portion was absent. There were 15 observers, and when all the observers thought that there was a colored portion on the winding start end portion, it was judged that the fourth clamping portion was present.

[0470] <Measurement of the slopes of L1, L1 + L2, T2, S1, S1 + S2, and IL3>

[0471] In the rolls of Examples 3, 7 to 16, when the existence of the fourth sandwiching portion is not confirmed, the length L1, thickness T2, and area S1 are measured, and the length L1 / thickness T2 and area S1 / thickness T2 are calculated. In addition, when the existence of the fourth sandwiching portion is confirmed, the length L1+length L2, thickness T1, T2, area S1+area S2 are measured, and (length L1+length L2) / thickness T2 and (area S1+area S2) / thickness T2 are calculated. In addition, the lengths L1, L2, thickness T2, and areas S1, S2 refer to Figures 4 to 8 The portion shown.

[0472] Specifically, first, a jig and a laser displacement meter (product name "LK-G30", manufactured by KEYENCE Co., Ltd.) for rotating the roll are prepared and arranged at predetermined positions. The jig is inserted into a hole in the width direction of the core to rotatably hold the roll.

[0473] The laser displacement meter is located above the roll, and three laser displacement meters are arranged in a manner to irradiate the laser toward the front of the roll. The arrangement positions of the laser displacement meters are as follows. First, determine the first position and the second position that divide the width of the stack into three equal parts. The first position is located on the first end side of the short side direction of the stack, and the second position is located on the second end side opposite to the first position. Moreover, the first laser displacement meter is arranged in a manner to irradiate the laser to the midpoint between the first position and the first end, the second laser displacement meter is arranged in a manner to irradiate the laser to the midpoint between the first position and the second position, and the third laser displacement meter is arranged in a manner to irradiate the laser to the midpoint between the second position and the second end.

[0474] Then, the roll body was mounted on the fixture, and the acrylic resin film was fed out from the roll body until the first filling portion was exposed. Then, in the state where the first filling portion was exposed, the core was rotated at a speed of 30 mm / s in an environment of a temperature of 23°C and a relative humidity of 50%, and the displacement was continuously measured with a laser displacement meter at a sampling period of 200 μs to obtain a graph with the horizontal axis being the position (mm) and the vertical axis being the displacement (mm) (see Fig.40 (A)~ Fig.40 (C)). The measurement is performed from the end of the first filling part toward the position connected to the end surface. In the measurement, the reference height (the line with a displacement of 0 mm) is set as the height of the core, and the difference between the height of the core and the first filling part is taken as the thickness of the first filling part. The obtained curve graph essentially represents a plane including the long side direction of the sheet and the radial direction of the core. In addition, in the curve graph, one scale of the horizontal axis is set to 5 mm, and one scale of the vertical axis is set to 0.02 mm.

[0475] In this graph, the position on the displacement curve where the displacement begins to decrease sharply is defined as position E1. In addition, when the presence of the fourth interposed portion is not confirmed, the thickness T2 of the first filling portion at the position where it contacts the end surface is determined by determining the difference between the line with a displacement of 0 mm and the displacement at position E1.

[0476] When the presence of the fourth clamping portion is confirmed, the thickness T2 is measured by the following method. First, a sample of 2 cm × 2 cm in size including the portion including the winding start end 12A, the first filling portion 14 and the second week of the sheet 12 is selected and fixed in such a way that the portion is not crushed. Then, the cross section of the fixed sample is ground, and the thickness T2 of the first filling portion is measured using a stereoscopic microscope (product name "Digital Microscope VHX-7000", manufactured by KEYENCE Co., Ltd.) at a temperature of 23°C and a relative humidity of 50%. The measurement of the thickness T2 based on the stereoscopic microscope selects coaxial epi-illumination as the illumination of the digital microscope and is performed under dark field and reflected light at a magnification of 500 times.

[0477] In addition, when the existence of the fourth clamping part is not confirmed, the length L1 is obtained from the curve graph of the position displacement curve in the same way as the thickness T2. Specifically, first, according to the curve graph, the above-mentioned position E1 is determined, and the intersection of the line with a displacement of 0 mm at the location where the displacement begins to rise and the position displacement curve is set as position E2. Next, an imaginary line IL4 is drawn that passes through the above-mentioned position E1 and is perpendicular to the line with a displacement of 0 mm. Then, the intersection of the imaginary line IL4 and the line with a displacement of 0 mm is taken as position E3, and the distance between position E2 and position E3 is calculated, thereby calculating the length L1. The area S1 is calculated as follows: in the area from the above-mentioned position E2 to the position E3, the product of the thickness at each measuring point and the width between each measuring point is calculated, and the sum is calculated. It should be noted that based on the above-mentioned formula (3), the width between the measuring points is calculated from the sampling period, the rotation speed of the core and the outer diameter of the core, and the result is 6.24μm. When the presence of the fourth intervening portion is confirmed, length L1 + length L2 is calculated in the same manner as length L1 when the presence of the fourth intervening portion is not confirmed.

[0478] Then, when the existence of the fourth intervening portion is not confirmed, the length L1, thickness T2, and area S1 are used to obtain length L1 / thickness T2 and area S1 / thickness T2. In addition, when the existence of the fourth intervening portion is confirmed, (length L1+length L2) / thickness T2 and (area S1+area S2) / thickness T2 are obtained using the obtained sum of length L1 and length L2, thickness T2, and the sum of area S1 and area S2.

[0479] In addition, in the above-mentioned curve graph, a hypothetical line IL3 passing through positions E1 and E2 is drawn (refer to Fig.40 of (A) to Fig.40 of (C)), and the slope of this hypothetical line IL3 is obtained.

[0480] <Measurement of L4, T6, S3>

[0481] In the rolled bodies of Examples 13 to 16, the length L4, the maximum thickness T6, and the cross-sectional area S3 are measured, and L4 / maximum thickness T6 and cross-sectional area S3 / maximum thickness T6 are obtained. In addition, the length L4 and the maximum thickness T6 refer to the parts shown in Fig. 27 and the cross-sectional area S3 refers to the part shown in Fig.29 The length L4, the maximum thickness T6, and the cross-sectional area S3 are measured using a jig for rotating the rolled body and a laser displacement meter (product name "LK-G30", manufactured by KEYENCE CORPORATION). Specifically, first, the rolled body is mounted on the jig in the same manner as the measurement of the length L1, etc., and three laser displacement meters are arranged at specified positions. Then, the laminate is sent out from the rolled body until the second clamping portion is exposed. Then, in the state where the second clamping portion is exposed, in an environment of a temperature of 23°C and a relative humidity of 50%, while rotating the core at a rotational speed of 30 mm / s, the displacement amount is continuously measured by the laser displacement meter at a sampling period of 200 μs, and a curve graph is obtained with the horizontal axis representing the position (mm) and the vertical axis representing the displacement amount (mm). This measurement is performed from the second end of the second clamping portion on the side opposite to the first end of the double-sided tape side toward the first end. In this measurement, the reference height (the line with a displacement amount of 0 mm) is taken as the height of the core, and the difference in height between the core and the second clamping portion is taken as the thickness of the second clamping portion. The obtained curve graph substantially represents a plane including the long side direction of the sheet and the radial direction of the core. In addition, in this curve graph, one scale on the horizontal axis is set to 5 mm, and one scale on the vertical axis is set to 0.02 mm.

[0482] In this curve graph, the position with the highest displacement amount is observed, and the difference between the line with a displacement amount of 0 mm and the displacement amount at this position is obtained, thereby obtaining the maximum thickness T6 of the second clamping portion.

[0483] In addition, according to the curve graph, the intersection of the line with a displacement of 0 mm at the location where the displacement begins to rise and the position displacement curve is found, that is, the first position. Next, draw an imaginary line that passes through the position where the displacement becomes the highest and is perpendicular to the line with a displacement of 0 mm. Then, the intersection of the imaginary line and the line with a displacement of 0 mm is taken as the second position, and the distance between the first position and the second position is calculated, thereby calculating the length L4. The cross-sectional area S3 is calculated as follows: in the area from the first position to the second position, the product of the thickness at each measuring point and the width between each measuring point is calculated, and the sum is calculated. It should be noted that based on the above formula (3), the width between the measuring points is calculated from the sampling period, the rotation speed of the core and the outer diameter of the core, and the result is 6.24μm.

[0484] Furthermore, using the obtained length L4, maximum thickness T6, and cross-sectional area S3, length L4 / maximum thickness T6 and cross-sectional area S3 / maximum thickness T6 are obtained.

[0485] The results are shown in Tables 1 to 3 below.

[0486] [Table 1]

[0487]

[0488] [Table 2]

[0489]

[0490] [Table 3]

[0491]

[0492] Regarding the roll of Comparative Example 1, the deformation relaxation length at the winding start end and the deformation relaxation length of the double-sided tape are both longer. This is considered to be because: since the first gap is a hole, the step difference caused by the winding start end of the acrylic resin film is large, and since the second gap is a hole, the step difference caused by the double-sided tape is large. In contrast, in the rolls of Examples 1 to 12, the deformation relaxation length at the winding start end and the deformation relaxation length of the double-sided tape are both shorter than the roll of Comparative Example 1. This is considered to be because: in the rolls of Examples 1 to 5 and 7 to 15, since the first gap is filled with the first filling part, the step difference caused by the winding start end of the acrylic resin film is small, and since the second gap is filled with the second filling part, or the second sandwiching part is sandwiched in the area corresponding to the second gap, the step difference caused by the double-sided tape is small. In addition, in Example 6, since the first clamping portion is clamped in the first area corresponding to the first gap, the step difference caused by the starting end of the winding of the PET film is small. In addition, since the second clamping portion is clamped in the second area corresponding to the second gap, the step difference caused by the double-sided tape is small.

[0493] For the first filling part of the roll of Examples 3, 8 to 16, the length L1 / thickness T2 or (length L1+length L2) / thickness T2 is greater than 90, and / or the area S1 / thickness T2 or (area S1+area S2) / thickness T2 is greater than 3.0. Therefore, compared with the roll of Example 7 in which the length L1 / thickness T2 is less than 90, the deformation relaxation length at the starting end of winding is shorter.

[0494] In the second interposed portion of the rolls of Examples 13 to 16, the length L4 / maximum thickness T6 is 12 or more and / or the cross-sectional area S3 / maximum thickness T6 is 2.5 or more, so the deformation relaxation length of the double-sided tape is short.

[0495] In the rolls of Examples 1, 2, 6, and 13, the shear viscosity of the silicone resin composition and the silicone rubber composition during coating was 60 Pa·s or more, and therefore, the overflow of the above-mentioned composition from between the core and the acrylic resin film or the PET film was not confirmed during coating and when pressure was applied during winding. In the rolls of Examples 3, 4, and 7 to 10, the shear viscosity of the composition during coating was less than 60 Pa·s but was more than 15 Pa·s, and therefore, although there was no overflow during coating, overflow of the composition was confirmed when pressure was applied during winding. In Examples 5, 11, 12, and 14 to 16, the shear viscosity of the composition during coating was less than 15 Pa·s, and therefore, overflow of the composition from between the core and the acrylic resin film was confirmed.

[0496] In addition, a reprocessability test was performed on the roll of Example 3. Specifically, first, the acrylic resin film was unwound to expose the first filling part. Then, an opening was made at the end of the first filling part with a blade-like component in a manner not to damage the core, and an attempt was made to slowly peel the first filling part from the core with the fingers. The evaluation criteria for reprocessability are as follows: a case where the first filling part was cleanly peeled off was set as good, and a case where a part of the first filling part remained on the core due to breakage, etc. was set as poor. In such an evaluation, the first filling part of the roll of Example 3 was cleanly peeled off, so it was good. It should be noted that the reprocessability test was also performed on the rolls of embodiments other than Example 3, and the result was that the reprocessability was good, just like the first filling part of Example 3. The tensile strength of the constituent material of the first filling part in the rolls of the embodiments other than the embodiment 3 is 3.0 MPa or more and 5.5 MPa or less, the elongation when cut is 250% or more and 600% or less, the tear strength is 6 N / mm or more and 25 N / mm or less, the hardness of the constituent material of the first filling part measured by the A-type hardness meter is 10° or more and 50° or less, and the linear shrinkage of the constituent material of the first filling part is within the range of 0% or more and 1.0% or less. In addition, as shown in Table 1, the edge thickness T1 of the first filling part of the rolls of the embodiments 1 to 16 is within the range of 1.5 μm or more and 20 μm or less. When peeling off the first filling part, or when washing or wiping, the first filling part is easy to peel off or remove, although slightly, for the side with thicker edge thickness T1.

[0497] In Examples 1 to 12, the silicone resin composition or silicone rubber composition was applied in contact with the first end face and the second end face of the double-sided tape, but in Examples 1 to 12, the silicone resin composition or silicone rubber composition was applied, or the double-sided tape was arranged, so that the separation distance between the silicone resin composition or silicone rubber composition and the double-sided tape was 1 mm, and as a result, the roll body could be stably manufactured, and the obtained roll body was also substantially the same as the above-mentioned evaluation results or measurement results of the roll body of Examples 1 to 12, respectively. In addition, similarly, in Examples 1 to 12, the silicone resin composition or silicone rubber composition was applied, or the double-sided tape was arranged, so that the separation distance between the silicone resin composition or silicone rubber composition and the double-sided tape was 3 mm, and as a result, the roll body could be stably manufactured, and the obtained roll body was also substantially the same as the above-mentioned evaluation results or measurement results of the roll body of Examples 1 to 12, respectively. In these cases, the following sequence is followed: first, the silicone resin composition, etc. is applied linearly along the width direction of the core, and then the double-sided tape is arranged so that the separation distance between the second end face of the double-sided tape and the silicone resin composition, etc. is 1 mm or 3 mm, and then the silicone resin composition, etc. is applied linearly along the width direction of the core so that the separation distance between the first end face of the double-sided tape and the silicone resin composition, etc. is 1 mm or 3 mm.

[0498] Furthermore, in Example 2, the silicone rubber composition was applied or the double-sided tape was arranged in such a manner that the separation distance between the silicone rubber and the double-sided tape was 5 mm, and as a result, the roll was able to be manufactured stably, and the obtained roll was also substantially the same as the above-mentioned evaluation results or measurement results of the roll of Example 2. In addition, the edge thickness T1 was 2 μm. In this case, the following sequence was performed: first, the silicone rubber composition was applied in a linear shape along the width direction of the core, and then the double-sided tape was arranged in such a manner that the separation distance between the second end face of the double-sided tape and the silicone rubber composition was 5 mm, and then the silicone rubber composition was applied in a linear shape along the width direction of the core in such a manner that the separation distance between the first end face of the double-sided tape and the silicone rubber composition was 5 mm.

[0499] In Example 3, a silicone rubber composition having a shear viscosity of 40 Pa·s during coating was used. However, when the shear viscosity during coating was set to 7 Pa·s and the separation distance between the double-sided tape and the silicone rubber composition was set to 11 mm, for example, the silicone rubber composition located on the first end face side of the double-sided tape flowed to the side opposite to the double-sided tape side. Similarly, when the shear viscosity was set to 250 Pa·s and the silicone rubber composition was arranged in contact with the first end face and the second end face of the double-sided tape, it was difficult to make it flow sufficiently even when the acrylic resin film was wound, and therefore, after curing, although it was small, another step difference was generated at the winding start end.

[0500] Description of symbols

[0501] 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150: roll body;

[0502] 11: core;

[0503] 11A: outer peripheral surface;

[0504] 12: Sheet;

[0505] 12A: winding start end;

[0506] 12A1: terminal face;

[0507] 12D: Area 1;

[0508] 12E: Area 2;

[0509] 12F: Area 3;

[0510] 12G: end;

[0511] 12H: convex part;

[0512] 13: 1st gap;

[0513] 14: 1st filling part;

[0514] 15, 52: 2nd gap;

[0515] 16, 53: 2nd filling part;

[0516] 17, 51: fixed parts;

[0517] 17A, 51A: 1st end surface;

[0518] 17B, ​​51B: second end surface;

[0519] 21, 54: 3rd gap;

[0520] 22, 55: 3rd filling part;

[0521] 71: 1st clamping part;

[0522] 72: second interposition part;

[0523] 73: middle volume;

[0524] 81: The third clamping part;

[0525] 201~207: coating material.

Claims

1. A roll body comprising a core and a long sheet material wound around the outer peripheral surface of the core, wherein: The roll body has: A fixing member for fixing a portion of the sheet relative to the winding core, the fixing member being disposed between the winding core and the sheet of the first cycle and having a first end surface extending along the width direction of the winding core and a second end surface on a side opposite to the first end surface; a second gap located between the winding core and the sheet of the first cycle and in contact with the first end surface of the fixing member; a third gap located between the winding core and the sheet of the first cycle and in contact with the second end surface of the fixing member; and At least one of the second clamping portion and the third clamping portion, wherein the second clamping portion is arranged in a second area corresponding to the second gap between the sheets after the first week and extends along the width direction of the winding core, and the third clamping portion is arranged in a third area corresponding to the third gap between the sheets after the first week and extends along the width direction of the winding core.

2. The roll according to claim 1, wherein: The sheet has convex portions projecting in the radial direction of the winding core at both ends extending along the longitudinal direction of the sheet.

3. The roll according to claim 1, wherein: The second interposing portion and the third interposing portion each contain a coloring material or a light emitting material.

4. The roll according to claim 1, wherein: The second filling part and the third filling part each contain a cured product of a curable polymer composition.

5. The roll according to claim 1, wherein: When the thickness of the second clamping portion is measured along the long side direction of the sheet, the ratio of a length L4 from the second end of the second clamping portion on the opposite side of the first end on the fixing component side to a position at which the maximum thickness T6 of the second clamping portion is obtained to the maximum thickness T6 of the second clamping portion is greater than 12.

6. The roll according to claim 5, wherein: A ratio of a cross-sectional area S3 of the second sandwich portion from the second end of the second sandwich portion to a position of the maximum thickness T6 in a plane including the long side direction of the sheet and the radial direction of the winding core to the maximum thickness T6 of the second sandwich portion is greater than 2.

5.

7. The roll according to any one of claims 1 to 6, wherein: The sheet has a resin film.

8. The roll according to any one of claims 1 to 6, wherein: The sheet material includes acrylic resin, polyester resin, and cycloolefin polymer resin.

9. The roll according to any one of claims 1 to 6, wherein: The sheet has a thickness of 15 μm or more and 300 μm or less.

10. The roll according to any one of claims 1 to 6, wherein: The sheet is a laminate having a substrate and one or more functional layers laminated on the substrate.

11. The roll according to any one of claims 1 to 6, wherein: The sheet is used for an optical film, a polarizing plate, or a display device.